Multitargeted metabarcoding and morphological identification reveal practice-specific soil biodiversity outcomes in Mediterranean cropping systems - Lur Epelde; Ninon Delcourt; Jérôme Cortet; Anders Lanzén; Carlos Garbisu; José Luis Lavín; Luigi P. D'Acqui; Sara Di Lonardo; Martina Grattacaso; Eliana L. Tassi; Fatima-Zahraa El Balghiti; Leila Benidire; et al. (Soil Biology and Biochemistry, 2026)

Follicular growth and atresia at the time of oocyte aspiration differentially affect in vitro embryo production in mares - Thadeu de Castro; Alejandro de la Fuente; Kazuki Takahashi; Katarzyna Malin; Soledad Martin-Pelaez; Paulo Sérgio Gomes; Victória Ferreira Gurian; Matheus de Castro Azevedo; Lauren Riley Ofer; Erin L. Oberhaus; Eduardo L. Gastal; Carlos Ramires Neto; et al. (Theriogenology, 2026)

Natural deep eutectic solvents (NADES): dual functionality in the extraction and stabilization of polyphenols, terpenoids and nitrogen compounds - Gerardo Valles-Salas; Juliana Morales-Castro; Claudia I. Gamboa-Gómez; Blanca E. Morales-Contreras; Walfred Rosas-Flores; L. Araceli Ochoa-Martínez; Juan C. Contreras-Esquivel; Ana M. Ávila-Galván; Orlando A. Manzanares-Meza (Food Chemistry, 2026)

Detection by PCR of Borrelia theileri in ticks and anti-rGlpQ antibodies in cattle from Guanajuato, Mexico - Sofía L. Luna-Rojas; José Luis Gutiérrez-Hernández; Edwin Vázquez-Guerrero; Jose Alberto Hernández-Martínez; Rigoberto Hernández-Castro; Paulina Estrada-de los Santos; J. Antonio Ibarra (Veterinary Research Communications, 2026)

Kogia Records in Brazilian Equatorial and Southwestern Atlantic Oceans - Joao Pedro M. Mura; Raphael B. Machado; Yasmin P. Viana; Natalia Rodrigues‐Soares; Giovanne A. Ferreira; Larissa Kelmer L. Kascher; Barbara S. Silva; Lucia O. Alencar; Gabrieli M. Rodrigues; Franciele R. de Castro; Daniela F. Godoy; Jose L. Pizzorno; et al. (Marine Mammal Science, 2026)
The pygmy ( Kogia breviceps ) and dwarf ( Kogia sima ) sperm whales are cryptic cetaceans characterized by inconspicuous surfacing behavior, small group sizes, and deep‐diving habits, making visual detection particularly challenging. Here, we present the first broad‐scale passive acoustic monitoring (PAM) assessment of Kogia spp. occurrence along the Brazilian coast, spanning both the Equatorial Atlantic Ocean (EAO) and Southwestern Atlantic Ocean (SWAO). Across 25 survey campaigns, 504 survey days, and more than 6441 h of acoustic recordings, 94 acoustic detections were identified, predominantly within the Brazilian Equatorial Margin (BEM), resulting in substantially higher detection‐per‐unit‐effort values in the EAO than in the SWAO. Two rare visual‐acoustic encounters of Kogia sima were also documented, including one detection incorporated into the dataset. A total of 2796 echolocation clicks were analyzed, exhibiting the characteristic narrow‐band high‐frequency acoustic profile of Kogia spp. (mean peak frequency = 126.2 ± 3.8 kHz; mean −3 dB bandwidth = 4.7 ± 2.56 kHz; mean inter‐click interval = 141 ± 97 ms). Detections occurred across a broad bathymetric range (9–4411 m), and kernel density analyses revealed spatial heterogeneity in occurrence patterns, with recurrent detection areas concentrated within the BEM. Collectively, these findings demonstrate the effectiveness of PAM for studying elusive deep‐diving cetaceans and provide an important baseline for future ecological monitoring, impact assessment, and conservation efforts targeting Kogia spp. in the western Atlantic.

Stress state assessment through focal mechanism inversion in the San Salvador Metropolitan Area and its volcanic edifices, El Salvador - R.A. García-Castro; J.A. Álvarez-Gómez; C.E. Reinoza; L. Munguía; E. Glowacka; A. Staller (Tectonophysics, 2026)

Divergent PXR Function in Seals: Endocrine Adaptation or Functional Loss? - Inês Amorim; Diogo Oliveira; L. Filipe C. Castro; Raquel Ruivo; Mónica Marques (Environmental Toxicology and Pharmacology, 2026)

Photocatalytic caffeine degradation and toxicity reduction using reduced graphene oxide-modified zinc telluride - A. J. Vilvert; P. D. Macruz; R. P. Nippes; H. C. L. Geraldino; L. V. de Castro-Hoshino; I. R. Bautitz; J. C. G. Moraes (International Journal of Environmental Science and Technology, 2026)
The occurrence of emerging pollutants in aquatic matrices has raised environmental concern because of their persistence and potential toxicity. This study assessed caffeine degradation and toxicity reduction using zinc telluride functionalized with reduced graphene oxide as heterogeneous photocatalyst. The catalysts were synthesized by the wet impregnation method with excess solvent, and characterized by physicochemical and optical techniques. The results indicated zinc telluride nanoparticles distributed on the surface of reduced graphene oxide sheets, together with changes in textural and optical properties, including a lower band gap for the composites. Photocatalytic tests were performed using a mercury vapor lamp emitting ultraviolet–visible radiation, with the main emission at 365 nm. The effects of reduced graphene oxide content, catalyst loading, initial caffeine concentration, and pH variation were evaluated. Under the tested experimental conditions, the composite containing 1.0% reduced graphene oxide showed the highest degradation performance, reaching 93% caffeine degradation in 85 min. The degradation profile was best described by the half-order kinetic model. The reduced photoluminescence intensity suggests lower electron–hole recombination, although direct confirmation of reactive species requires complementary analyses. Toxicity tests indicated lower Artemia salina mortality and improved Lactuca sativa germination after treatment with the 1.0% reduced graphene oxide-modified zinc telluride catalyst. The results indicate that reduced graphene oxide incorporation can improve caffeine photodegradation and reduce toxicity under the evaluated conditions.

Evaluation of water quality from tubular wells in Brazil - G. G. O. de Souza; J. W. G. Castro; R. S. da Cadorso; E. M. de Lima; J. F. L. de Pereira; M. P. da Silva; Y. T. C. da Santos; F. G. Rodriguês; J. G. M. da Costa; H. D. M. Coutinho; G. B. Brito (International Journal of Energy and Water Resources, 2026)

Back to the Future of qEEG: Lifespan Normative Modeling of Spectral Ratios and Functional Indices with Potential Applications to Therapeutic Monitoring - J. Bosch-Bayard; J. Guerrero-Sauzameda; R. I. Bosch-Bayard; R. Pérez-Elvira; A. Bosch-Castro; J. Sánchez-Rodríguez; A. Flores; K. Flores; E Resendiz-Flores; A. Ferrando; P. Ferrando; L. Galán-García; et al. (Brain Topography, 2026)
Quantitative EEG (qEEG) provides objective, millisecond-resolution measures of brain dynamics. Despite decades of methodological advances, clinically relevant derived indices—spectral power ratios, cognitive-emotional state markers, and physiological parameters—are typically reported as raw values without the normative context required for individualized clinical inference. To develop the first systematic age-dependent normative models for this family of derived qEEG indices using a multinational database, enabling probabilistic Z-score interpretation at the individual level with potential applications in objective therapeutic monitoring. Normative modeling was applied to the HarMNqEEG database ( n = 1,564 neurologically healthy participants, ages 5–97, 9 countries, eyes-closed resting state). Electrode-level Spectral Normalization (ESN) removed inter-individual and inter-device amplitude variability while preserving the neurophysiological interpretability of each index. Age-dependent normative trajectories were estimated using Generalized Additive Models for Location, Scale, and Shape (GAMLSS) with P-splines on log(age), allowing conditional mean and variance to vary non-linearly across the lifespan. GAMLSS modeling revealed significant non-linear age-dependent trajectories for all indices. Slow-wave-dominated ratios showed steep decreases from childhood to early adulthood, consistent with cortical maturation; alpha-dominated indices increased during adolescence before stabilizing. ESN normalization yielded well-calibrated normative residuals across the full age range for all indices, except Valence. For the Valence index, a quantile regression model is provided as the recommended normative reference due to its spike-and-slab marginal distribution. These normative models provide a principled, age-adjusted probabilistic framework for individual-level qEEG interpretation, based on eyes closed resting state recordings, laying the methodological groundwork for future clinical validation in diagnostic and therapeutic monitoring applications. The ESN strategy requires no knowledge of recording equipment, ensuring broad applicability across clinical and research settings.

Calibration and validation of the safer evapotranspiration model using Landsat 8 and eddy covariance data in vineyards - Anderson L. S. Safre; Alfonso Torres-Rua; Joao Carlos Cury Saad; Antônio Heriberto de Castro Teixeira (Irrigation Science, 2026)
Accurate estimates of actual evapotranspiration (ET a ) are essential for irrigation management in vineyards. This study locally calibrated and validated the Simple Algorithm for Evapotranspiration Retrieving (SAFER) model for California vineyard systems using Landsat 8 imagery and multi-year eddy covariance (EC) measurements collected between 2013 and 2016 in the Central Valley of California. Two calibration approaches were implemented: k-fold cross-validation and a split-sample (two-year) strategy. SAFER performance was evaluated using both closed and unclosed energy balance EC fluxes to assess the influence of energy balance closure on model calibration and validation. Energy balance closure ratios ranged from 0.67 to 0.95, with moderate interannual variability and lower closure observed during some periods. Local calibration of SAFER resulted in regression coefficients that differed substantially from the original parametrization. Compared to the original coefficients, root mean square error (RMSE) was reduced by approximately 71–77%, with values below 0.70 mm d − 1 for both calibration approaches. Model validation showed strong agreement between SAFER ET a and EC observations after calibration. RMSE ranged from 0.57 to 0.71 mm d − 1 and mean absolute error (MAE) ranged from 0.46 to 0.55 mm d − 1 . Overall, the results indicate that SAFER provides reliable estimates of daily vineyard ET a when locally calibrated, supporting its application for field-scale irrigation management in perennial cropping systems.

On-Demand Hospital Manufacturing of Baclofen Lozenges Using Pharmaceutical 3D Printing - Daniel Grandal-Gonzalez; Carlos Bendicho-Lavilla; Eduardo Diaz-Torres; Rocio Sanin-Fontela; María L. Couce; María José de Castro-López; Isabel Gonzalez-Alvarez; Marta Gonzalez-Alvarez; Alejandro Ruiz-Picazo; Marival Bermejo; Pedro Garcia-Salom; Abdul W. Basit; et al. (Pharmaceutical Research, 2026)
Purpose Dysphagia in neurological patients complicates oral drug administration. Manual preparation of lozenges/troches lacks precision and scalability. This study investigates the feasibility of implementing a pharmaceutical 3D printer in a hospital pharmacy for the automated production of personalized baclofen troches. Methods Baclofen troches were manufactured in a hospital pharmacy setting, both manually and via pharmaceutical 3D printer. Quality was evaluated using Process Analytical Technologies (PAT). Performance was assessed through European Pharmacopoeia (EP) tests for drug content, mass uniformity, in vitr o dissolution, disintegration, and a six-month stability study. Results Printed troches complied with all EP acceptance criteria for drug content and mass uniformity, whereas manual formulations failed, particularly at the lowest dose. Printed troches demonstrated immediate drug release, consistent quality across batches, and remained stable for six months. 3D printing showed superior precision over traditional manual compounding. Conclusions This research describes the first successful implementation of an automated blister-filling workflow using a pharmaceutical 3D printer within a hospital pharmacy setting, spanning from manufacturing and dispensing to direct patient administration. The automated approach provides a significant advancement in personalized medicine, ensuring safer, more accurate, and efficient treatment options for patients with specific needs like dysphagia.

Functional venom activity and antivenom neutralization in rattlesnakes across Baja California and Gulf of California islands - Samuel R. Hirst; Edgar Neri-Castro; Emiliano Vázquez-García; Vanessa Zarzosa; Felipe Olvera; Cameron M. VanHorn; Alejandro Alagón; Hector Franz-Chávez; Gamaliel Castañeda-Gaytán; Christopher L. Parkinson; Jason L. Strickland; Miguel Borja; et al. (Toxicon, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

Mn/Co-modified CaO pellets bound with mesoporous γ-Al2O3 for thermochemical energy storage: balancing energy-storage density, mechanical strength and solar absorptance - D. Castro-Yáñez; A. Peral; J. González-Aguilar; M. Romero; E.S. Sanz-Pérez; L. Briones; J.M. Escola (Journal of Cleaner Production, 2026)

Dynamic remodeling in lipophilic metabolites during Coffea canephora maturation: A lipidomic study - Marcos V.V. Lyrio; João V.M. de Almeida; Eric C. Gier; Samuel G. Moore; Henzo P. Salvador; Fábio L. Partelli; Facundo M. Fernández; Wanderson Romão; Eustáquio V.R. de Castro (Food Chemistry, 2026)

Impacts of bottom trawl fishing in the Juan Fernández ridge, Chile - I. Petit; J.M. Tapia-Guerra; C.F. Gaymer; J. Sellanes; M. Castro-Contreras; M.-A. Gallardo; E.E. Easton; L. Watling; I. Payá (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Printed PEDOT:PSS/Ti3C2Tx MXene composite transistor biosensor enables stable low-voltage detection of aflatoxin B1 in complex matrices - Gajanan A. Bodkhe; Subramanian Siva; Chenhao Cong; Ian John L. Castro; Long Ma; Se Hyun Kim; Myunghee Kim (Chemical Engineering Journal, 2026)

Fisetin attenuates glutamate-induced excitotoxicity and modulates neural progenitor cell dynamics in vitro - Sergio Martínez-Ortega; Bruno I. Benincasa; Felipe G. Nishimura; Ana L. Fachin; Renata Dellalibera-Joviliano; Pedro Nunez-Abades; Carmen Castro; Rene O. Beleboni (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Neurodegenerative diseases (NDs) are characterized by progressive neuronal loss associated with excitotoxicity, oxidative stress, neuroinflammation, and impaired neuroplasticity. Fisetin, a naturally occurring flavonoid, has emerged as a potential neuroprotective compound due to its antioxidant and anti-inflammatory properties. In this study, we investigated the effects of fisetin in cellular models of glutamate-induced excitotoxicity and neural progenitor differentiation. Differentiated PC-12 cells were exposed to 13 mM glutamate and treated with fisetin. Cell viability was assessed using the MTT assay, reactive oxygen species (ROS) production by dihydroethidium assay, and TNF-α levels by ELISA. In parallel, subventricular zone (SVZ)-derived neurosphere cultures were used to evaluate proliferation and differentiation. Fisetin significantly attenuated glutamate-induced cytotoxicity, reduced ROS production, and decreased TNF-α levels. In neurosphere cultures, fisetin reduced neurosphere size without altering neurosphere number, suggesting modulation of progenitor cell dynamics without affecting neural stem cell self-renewal. Moreover, fisetin increased β-III-tubulin-positive neuroblasts without affecting GFAP-positive glial cells. These findings support the pharmacological potential of fisetin in modulating key pathological features of NDs and encourage further in vivo validation and molecular pathway analysis.

Erratum to “Hospital food management: a multi-objective approach to reduce waste and costs” [Waste Manag. 175 (2024) 12–21] - Mariana Arriz-Jorquiera; Jorge A. Acuna; Marian Rodríguez-Carbó; José L. Zayas-Castro (Waste Management, 2026)

Long-term deformation prediction of a tropical railway sub-ballast soil in heavy-haul tracks using a high-cycle accumulation model - G. Castro; R. Motta; A. Paixão; E. Moura; E. Fortunato; L. Bernucci (Transportation Geotechnics, 2026)

Using paradata to improve data quality: A case study on post-wildfire restoration - Ana Castro-Atanes; Maria L. Loureiro (Forest Policy and Economics, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

A novel hunting‐by‐riding association of reef fishes mediated by habitat complexity - Guilherme M. Castro; Ivan M. Carneiro; Fernando C. Cardoso; Rodrigo L. Moura (Ecology, 2026)

Non‐Stationary Dry‐Spell Hazard Probabilities for Spain - S. M. Vicente‐Serrano; S. Beguería; A. Royo; A. El Kenawy; M. Franquesa; A. Halifa‐Marin; M. Adell‐Michavila; A. Crespillo; D. Pérez‐Pajuelo; F. Domínguez‐Castro; C. Azorin‐Molina; L. Gimeno; et al. (International Journal of Climatology, 2026)
This study provides a comprehensive assessment of long‐term changes in dry‐spell dynamics across Spain for the period 1961–2024, using both classical non‐parametric methods and a novel non‐stationary probabilistic framework applied to exceedance series of dry‐spell durations. Using daily precipitation data from a dense network of quality‐controlled stations, dry‐spells were identified based on four thresholds (0.1, 1, 5, and 10 mm) to characterize their duration statistics, and generalized Pareto distributions (GPDs) were fitted under both stationary and non‐stationary specifications. A systematic percentile‐based evaluation was performed to determine optimal exceedance thresholds, and a bootstrap‐based significance test was applied to compare stationary and non‐stationary return levels. Complementary analyses examined trends in annual frequency, mean duration, and maximum dry‐spell length. Results consistently reveal that dry‐spell behaviour across Spain is dominantly stationary. Only a very small fraction of stations show significant non‐stationary effects in the GPD location parameter, whereas non‐stationary scale, shape, or full‐parameter models provide no robust improvement and introduce substantial uncertainty. Traditional trend analyses corroborate this finding: most stations (> 70%–85%, depending on threshold) exhibit no statistically significant changes in dry‐spell frequency, mean duration, or maximum duration. Spatial patterns of change are weak, and return levels associated with long recurrence periods (e.g., 50 years) remain highly stable throughout 1961–2024. Overall, these results support long‐term stationarity in the probability of extreme dry‐spells across Spain.

Digoxin Derivative BD-8 Attenuates Oxidative Stress and Neuroinflammation in an LPS-Induced Experimental Model - Vitória Karolina Brandão Souza; Davi Azevedo Ferreira; Antônio Pereira Ribeiro Arantes; Elton de Sá Figueiredo; Millena Ferreira Rodrigues Fonseca; Pâmela Yasmin de Oliveira Ferreira; Martina Raissa Ribeiro; Paulo César Ghedini; Andreza Amália de Freitas Ribeiro; José Augusto Ferreira Perez Villar; Maira de Castro Lima; Israel José Pereira Garcia; et al. (Cell Biochemistry and Biophysics, 2026)
Chronic neuroinflammation contributes to neuronal damage through oxidative stress and inflammatory mediators, highlighting the need for novel therapeutic strategies. This study evaluated the cytotoxicity and neuroprotective effects of BD-8, a digoxin-derived cardiosteroid, in vitro and in vivo. BD-8 showed lower cytotoxicity than digoxin, with CC₅₀ values of 7.4 µM in SH-SY5Y cells and 8.5 µM in BV-2 cells, while digoxin presented a CC₅₀ of 33 nM in SH-SY5Y cells. In vivo, BD-8 did not alter cardiac, hepatic, or renal biochemical markers, supporting its systemic safety profile. In the open-field test, BD-8 prevented LPS-induced locomotor impairment, significantly increasing total crossings at 0.56 mg/kg (62.07 ± 3.269; P < 0.05) and 1.12 mg/kg (66.31 ± 5.282; P < 0.001) compared to the LPS group. BD-8 also reduced lipid peroxidation levels in the cortex at 0.56 mg/kg (14.38 ± 0.5568; P < 0.001) and 1.12 mg/kg (13.94 ± 0.8372; P < 0.001), and in the hippocampus at 1.12 mg/kg (14.04 ± 0.5223; P < 0.001). Additionally, BD-8 modulated antioxidant enzyme activities, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), in both the cortex and hippocampus and reduced IL-6 levels in these brain regions without altering BDNF (Brain Derived Neurotrophic Factor) levels. These findings support BD-8 as a promising candidate for neuroinflammatory disorders.

Heparin-incorporated whey protein isolate-derived hydrogels with an intended dual function as snakebite wound dressings and drug delivery systems inhibit spitting cobra venom-induced cytotoxicity - Matthew J. Gray; Daniel K. Baines; Gabrielle De Castro; Thomas Cobb; Layla A. Tyrrell; Sam J. Hyam; Alan M. Smith; Nicholas R. Casewell; Sarah L. Allinson; Timothy E.L. Douglas; Steven R. Hall (Toxicon, 2026)

Cystic endometrial hyperplasia in dairy goats: morphological changes and expressions of estrogen receptor-α and progesterone receptor - Agustín Avellaneda-Cáceres; Laura S. Aguirre; Gabriela V. Sandoval; Diego M. Medina; Ana L. Quintana; Francisco Acuña; Gimena Gomez Castro; Claudio G. Barbeito; Juan F. Micheloud (Research in Veterinary Science, 2026)

The first transcriptome of the diaphanous deep-sea hatchetfish Sternoptyx diaphana Hermann, 1781 (Teleostei: Sternoptychidae) - André Gomes-dos-Santos; Daniel Moita; David Barros-García; André M. Machado; Ana Matos; Nair Vilas-Arrondo; L. Filipe C. Castro; Elsa Froufe (Marine Genomics, 2026)

Impact of dispersion techniques and spray-drying on whey protein isolate powders properties - M.A. Aranda-Chávez; L. Alamilla-Beltrán; F. Villalobos-Castillejos; D.E. Leyva-Daniel; S.C. Pereyra-Castro; H. Hernández-Sánchez; G.F. Gutiérrez-López (Journal of Food Engineering, 2026)

Fucoidans from the brown seaweeds Undaria pinnatifida and Fucus vesiculosus as inhibitors of coagulant and phospholipase A2 activities of pit viper Lachesis muta venom and purified enzymes - Camila Castro-Pinheiro; Eladio F. Sanchez; Corinna A. Dwan; Barbara C. Wimmer; Alan T. Critchley; André L. Fuly (Journal of Applied Phycology, 2026)
Snakebite envenomation is a neglected tropical disease and incidents of the pit viper Lachesis muta cause hemorrhage, muscle damage, blood coagulation disturbances, and even death; the proteases and phospholipase A 2 (PLA 2 ) of snake venoms contribute to such toxic effects. This work evaluated the inhibitory effect of commercial fucoidans from two species of brown seaweeds Fucus vesiculosus (FVF) and Undaria pinnatifida (UPF) against the coagulant and PLA 2 activity of Lachesis muta venom and two purified enzymes, a thrombin-like enzyme and PLA 2 , denoted TLE–1 and LM-PLA 2 –I, respectively. Fucus vesiculosus and U. pinnatifida fucoidans were incubated with L. muta venom and enzymes for 5 min at 37 °C, followed by assays, including the plasma and fibrinogen coagulation, hydrolysis of the substrates of proteases (S–2238 and S–2288), and hydrolysis of the substrate of PLA 2 enzymes, NBD-PC. Fucus vesiculosus and U. pinnatifida fucoidans inhibited the plasma coagulation of L. muta venom, but not the coagulation of TLE–1. However, both fucoidans fully prevented the coagulation of fibrinogen caused by L. muta venom and TLE–1. Fucus vesiculosus and U. pinnatifida fucoidans inhibited 60% and 40% hydrolysis of S–2238 of L. muta venom and TLE–1, respectively. Using the substrate S–2288, the fucoidans did not affect the hydrolysis of L. muta venom and inhibited 40% of hydrolysis caused by TLE–1. Fucus vesiculosus and U. pinnatifida fucoidans inhibited 40% and 20% of the PLA 2 activity of L. muta venom and LM-PLA 2 –I, respectively. These two fucoidans should be investigated as complementary or potential adjuvants for SBE inflicted by L. muta venom in more detail.

Sex‐Specific Atlantic Salmon Upstream Passage and Fallback at a Natural Cascade After Dam Removal - Kurt C. Heim; Jonah L. Withers; William R. Ardren; Laurie A. Earley; David Minkoff; Theodore Castro‐Santos (Fisheries Management and Ecology, 2026)
In the Boquet River (NY, USA) a low‐head dam set above a ~200‐m bedrock cascade was removed in 2015. We used radio‐telemetry to assess landlocked Atlantic salmon passage at the remaining cascade (2020, 2022). Across years, 52% of males (13/25) attempted cascade passage whereas females made no discernable attempts (0/11). Attempt probability increased with stream discharge and decreased with fish size, though overall passage success was low (1/36). Shallow depths—likely owing to an artificially widened channel—appear to be limiting passage. Additionally, we transported fish upstream but observed high fallback (72%) that was associated with fish size and energetic status. Following dam removal, this cascade continues to limit upstream passage resulting in increased vulnerability to angling during migratory delay. Overall, we highlight the importance of follow‐up studies after dam removal, and that further modifications at this site may be required to improve passage.

Managing biological invasions in ports: A model for assessing the risk of species introduction through ballast water and hull biofouling - Nicolás Battini; Karen L. Castro; Mariana Abelando; Alejandro Bortolus; Evangelina Schwindt (Marine Pollution Bulletin, 2026)

Supplementation with rumen-protected fats reduces rectal temperature and improves productive performance of fattening lambs under heat stress - Alma B. Jaramillo-Castro; Marco A. López-Santiago; Sandra P. Maciel-Torres; Pablo Arenas-Báez; L. Danilo Granados-Rivera; Juan González-Maldonado; Jorge A. Maldonado-Jáquez (Journal of Thermal Biology, 2026)

In vivo evaluation of the anti-inflammatory efficacy of liposomes loaded with Echinacea purpurea roots extracts - Sara F. Vieira; Diana Fonseca-Rodrigues; Daniel Mendanha; Vânia I. B. Castro; Ricardo A. Pires; Rui L. Reis; Filipa Pinto-Ribeiro; Helena Ferreira; Nuno M. Neves (Drug Delivery and Translational Research, 2026)
WHO ranked chronic inflammatory diseases as the most significant cause of death. The current therapeutic approach is the constant administration of clinically available anti-inflammatory drugs; however, this strategy presents severe side effects. New entities derived from plants have shown their potential for developing safe and effective therapies. Particularly, Echinacea purpurea extracts have demonstrated strong anti-inflammatory properties. Therefore, dichloromethanolic extracts of E. purpurea roots (DE-R), rich in alkylamides, were used to produce an anti-inflammatory formulation. To increase therapeutic efficacy, DE-R were loaded into liposomes (LPs), which were also engineered to actively target M1 macrophages via surface functionalization with folic acid (FLPs). The developed formulations were homogeneous, with a mean particle size of ≈114 nm. The liposomes were cytocompatible at all tested concentrations and strongly reduced IL-6 production in LPS-stimulated macrophages. As expected, FLPs + DE-R were 6.3 times better than LPs + DE-R, and 9.7 times greater than free DE-R. The anti-inflammatory activity of free DE-R and DE-R-loaded FLPs was assessed in an experimental rat model of inflammation. A single intra-articular injection of the FLPs + DE-R promoted a significant reduction of edema, inflammatory pain, and immune cell infiltration, particularly of CD68 + macrophages, as well as IL-6 expression. This formulation reduced synovial inflammation more efficiently than free DE-R. We also demonstrated that the developed formulation was safe, as no welfare changes or harmful toxicity to major organs were observed. Therefore, E. purpurea roots extracts loaded in liposomes can be used as a natural, innovative, and powerful new formulation to treat chronic inflammatory diseases. Graphical Abstract

Wildfire causes in mainland Portugal: Municipal-scale hotspots and non-stationary spatial drivers - A.N. Nunes; L. Lourenço; Meira Castro A. C. (Journal of Environmental Management, 2026)

An integrated model to assess the psychosocial determinants of the intention to adopt organic farming practices - Sandra M. Sánchez-Cañizares; L. Javier Cabeza-Ramírez; Miguel González-Mohino; José Antonio López-Castro (Journal of Environmental Management, 2026)

Polysaccharide-mediated stabilization of bacterial nanocellulose dispersions: Experimental and molecular dynamics study - Ricardo Silva-Carvalho; Daniela Martins; Tarsila G. Castro; Ana Cristina Rodrigues; Bruna Costa; Paula Parreira; Artur Cavaco-Paulo; Fernando Dourado; M. Cristina L. Martins; Miguel Gama (Food Hydrocolloids, 2026)

The dynamics of coastal macroalgal assemblages after the Fundão dam disaster: challenges and lessons from impact assessment - Ivan M. Carneiro; Guilherme M. Castro; Fernando C. Cardoso; Julia P. Curvêllo; Rodrigo T. Carvalho; Leonardo T. Salgado; Julia Kaiser; Paulo S. Salomon; Rodrigo L. Moura (Environmental Monitoring and Assessment, 2026)
Anthropogenic marine disasters impair biodiversity, ecosystem services provisioning, and socioeconomic development, with long-lasting consequences. Robust impact assessment, however, depends on understanding the spatiotemporal variability of the indicators used to detect change. Here, we present the results of a monitoring program (2018–2025) targeted at two Coastal and Marine Protected Areas located 40 km south of the Doce River mouth (Eastern Brazil), which were affected by the discharge of iron ore tailings from the Fundão dam collapse in 2015. Besides assessing the dynamics of the benthic assemblages, we revealed a high variability among sampling units (residual), along with relevant variability across seasons, sites, and their interactions. Wave height and distance from rivers were the most influential drivers explaining assemblage variability. Before–after contrasts based on pre-disaster data from the literature indicate shifts in the assemblage structure. However, because baseline data are limited, the observed changes cannot be conclusively attributed to the disaster. An overview of marine areas under long-term ecological monitoring in Brazil revealed a concerning mismatch with the distribution of mining, oil and gas, port, and nuclear activities. Rethinking funding for baseline data collection and monitoring of disaster-prone marine areas, primarily from industries that are often responsible for marine disasters, constitutes a necessary step toward effective solutions.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Community interventions drive support for fisheries regulations and influence compliance: Lessons from the Philippines - Sarah Lindley Smith; Rachel Zuercher; Nygiel B. Armada; Joan L. Castro; Recamar Guiñares; Enrique G. Oracion; Andre Jon Uychiaoco; Elin Torell (Ocean & Coastal Management, 2026)

Minimizing food waste and costs in hospital environments through a chance-constrained stochastic programming model - Mariana Arriz-Jorquiera; Jorge A. Acuna; José L. Zayas-Castro (Resources, Conservation and Recycling, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Molecularly imprinted polymer-based field-effect transistor for real-time, highly selective, and sensitive aflatoxin B1 monitoring in food - Ian John L. Castro; Subramanian Siva; Gajanan A. Bodkhe; Chenhao Cong; Se Hyun Kim; Myunghee Kim (Food Chemistry, 2026)

Seek in ports and you shall find them: Monitoring marine invasions over time using combined standard assessment methods - Karen L. Castro; Clara B. Giachetti; Nicolás Battini; Enrique M. Morsan; Evangelina Schwindt (Estuarine, Coastal and Shelf Science, 2026)

Influence of almond’s canopy-induced shadows on actual evapotranspiration estimation by the TSEB model using sUAS multispectral and thermal imagery - M. R. Duran-Gomez; A. Torres-Rua; L. Hipps; W. Kustas; N. E. Bambach; K. Knipper; I. Wright; A. J. McElrone; J. H. Prueger; J. G. Alfieri; C. Coopmans; K. Meza; et al. (Irrigation Science, 2026)
Over the past decade, the estimation of water requirements in almond orchards has improved through the application of remote sensing models like the Two-Source Energy Balance (TSEB) model using various remote sensing platforms. However, there is limited understanding of how canopy-induced shadows influence surface reflectance and thermal infrared (TIR) signals particularly from small Unmanned Aircraft System (sUAS) imagery in energy balance models, and the effect on Latent Heat Flux (LE) estimations. This study evaluates LE estimates from the Priestley-Taylor TSEB model (TSEB-PT) with and without shadow filtering using sUAS-based multispectral and TIR imagery. It establishes a baseline for the impact of shadow filtering on model inputs and performance. Datasets were collected in 2021 and 2022, as part of the USDA led Tree-crop Remote sensing of Evapotranspiration eXperiment (T-REX) in almonds orchards across California. LAI-2200 C Plant Canopy Analyzer measurements facilitated the calibration of an empirical Leaf Area Index (LAI) model based on canopy fractional cover (FC) and NDVI (R 2 = 0.68). Shadow filtering caused land surface temperature (LST) differences up to 5 °C in young to semi-mature orchards (FC 0.40–0.80). In contrast, mature orchards (FC > 0.80) showed minimal influence due to the limited shadow occurrence on the imagery. Shadows appeared to reduce surface albedo (α alb ), mainly in interrow areas, thereby affecting the absorption of radiation and the partitioning of energy balance components. Their presence in sUAS imagery also hindered canopy delineation, impacting the accuracy of key TSEB inputs derived from canopy physical characteristics. Thus, the influence of shadow on TSEB estimated LE was more significant in lower fractional tree covers. While LE estimated by TSEB-PT without shadow filtering showed better agreement with observations, combining instantaneous TIR imagery with solar-noon shortwave data is recommended for accurate ETa assessment using sUAS datasets. These baseline results can be improved with more advanced formulations, supporting continued research on E/T partitioning and water stress in almond orchards under varying environmental conditions, particularly when there is advection of hot dry air.

Integrated policy and AI-assisted technologies to address extreme heat and enhance urban resilience - Johanne Rei R. Castro; Laurence L. Delina (Journal of Environmental Studies and Sciences, 2026)
Cities are increasingly facing extreme heat due to rising temperatures from accelerating climate change and the heat island effect caused by rapid urban expansions. In response to this emerging hazard, cities are developing and implementing policies aimed at mitigating the impacts of extreme heat, including initiatives to increase public awareness and enhance adaptive capacities. Additionally, many cities are leveraging artificial intelligence (AI)-assisted technologies to forecast heatwaves, develop evidence-based mitigation strategies, and optimize infrastructure development in anticipation of these challenges. Previous studies have identified the vulnerabilities and risks associated with extreme heat in cities, quantified its impacts, and evaluated the probable outcomes of adaptation and mitigation measures utilizing AI-assisted technologies. However, most of this research has concentrated on cities in developed regions such as the USA, Europe, and Australia. There has been limited exploration of the synergistic effects of policy and AI-assisted technology responses to extreme heat. To address these gaps, we employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol to scope studies exploring the integration of heat-related policies and AI-assisted technologies. This approach revealed strategic methods, underlying motivations, and key stakeholders involved. Our review offers insights into future research needs, particularly in bridging the geographical gaps in urban overheating studies and enhancing the integration of policy and AI-assisted technologies in cities.

Physiological, biochemical, and cytotoxic characterization of two UV-C mutant strains of the microalga Porphyridium purpureum (Rhodophyta): An indoor and outdoor study - Pablo Castro-Varela; Roberto Teófilo Abdala-Díaz; Félix L. Figueroa; Patricia I. Gómez (Algal Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Extracellular vesicle microRNAs as an epigenetic biosignature of arsenic-associated diabetes in the Strong Heart Study - Christian K. Dye; Allison Kupsco; Gabriela L. Jackson; Ronald A. Glabonjat; Abbas Hakim; Anelizze Castro-Martinez; Louise C. Laurent; Jason G. Umans; Walter Goessler; Shelley A. Cole; Andrea A. Baccarelli; Ana Navas-Acien; et al. (Environmental Research, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Seasonal variations in biofiltration efficiency of fish farm effluents using Ulva spp. - Cristina Rodríguez; N. L. Arroyo; M. C. Castro; A. Hernández de Rojas; X. Moreno-Ventas (Journal of Applied Phycology, 2026)
Intensive aquaculture generates nutrient-rich effluents that contribute to eutrophication if discharged untreated. Seaweed cultivation offers a sustainable approach to mitigate this impact while producing valuable biomass. This study evaluated the seasonal biofiltration efficiency and biomass production of Ulva spp. under simulated flatfish aquaculture effluent conditions using two experimental designs: parallel tanks and serial tanks with varying hydraulic retention times (HRTs). Ulva spp. showed higher nutrient removal and growth in summer compared to winter. In the parallel system, ammonium and phosphate removal exceeded 70% in summer but dropped below 50% in winter. In the serial system, nutrient removal peaked at a 24 h HRT, with ammonium and phosphate removal above 90%, while longer retention (36 h) did not improve performance. Biomass production followed a similar seasonal pattern, with higher yields in spring and summer. These results demonstrate that Ulva spp. are effective biofilters for aquaculture effluents, with performance strongly influenced by season and HRT. A two-tank serial configuration with 24 h HRT optimizes nutrient removal without compromising biomass production, providing useful insights for the design of sustainable seaweed-based biofiltration systems.

Glycerol-supplemented medium promotes transition of Cupriavidus necator from heterotrophic to lithoautotrophic growth - I. Castro Gonzalez; N. Gorret; L. Lauterbach; S. E. Guillouet (Biotechnology Letters, 2026)

Strategies to build trustworthiness and increase diversity in colorectal cancer biospecimen research: a multi-phase, multi-site qualitative study - Kristi L. Roybal; Brett Nava-Coulter; Jane Roberts; Destiny Harden; Saul Castro; Anna Revette; Maria Connolly; Gina Johnson; Jennifer A. Rountree; Suzanne Brodney; Kimberly Schoolcraft; David A. Drew; et al. (Journal of Community Genetics, 2026)

Wastewater analysis as a global toxicovigilance tool for the monitoring of new psychoactive substances - Dhayaalini Nadarajan; Maria Laimou-Geraniou; Andrew Chappell; Christine Baduel; Lubertus Bijlsma; Tim Boogaerts; Daniel A. Burgard; Sara Castiglioni; Nicola Ceolotto; Erin M. Driver; Fernando Fabriz Sodre; Despo Fatta Kassinos; et al. (Water Research, 2026)

Laboratory investigation and modelling of alternative materials for sub-ballast and formation rehabilitation in a heavy haul railway line - G. Castro; J. Saico; R. Motta; E. Moura; R. Costa; L. Bernucci; A. Paixão; E. Fortunato (Transportation Geotechnics, 2026)

The ornithine-arginine cycle supported a toxic, metalimnic Planktothrix rubescens bloom - Brittany N. Zepernick; David J. Niknejad; Emily E. Chase; Blessing A. Abiodun; Meaghan J. Adler; Katelyn A. Houghton; Jason L. Olavesen; Qudus Sarumi; Alexander R. Truchon; Jillian L. Walton; Jack H. Cheshire; Keara Stanislawczyk; et al. (Harmful Algae, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Interactions Between Microplastics and Trace Metals: Ecotoxicological Implications for Tropical Marine invertebrates, Mussel Perna Perna (Linnaeus, 1758) and Sea Urchin Echinometra Lucunter (Linnaeus, 1758) - Maria Fernanda Palanch; Letícia Albanit França; Pedro Henrique Paixão de Moura; Felipe Teixeira Santana; Camila Martins Prieto; João Vítor Castro; Murilo Vieira Guimarães; Vinícius Gonçalves Pereira; Otto Muller Patrão de Oliveira; Andre L. Belem; Caio Cesar-Ribeiro (Bulletin of Environmental Contamination and Toxicology, 2026)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Developing science-informed maps and climate service for extreme rainfall in Spain - S. M. Vicente-Serrano; S. Beguería; F. Reig; A. Royo; M. Arretxea; M. Gil; B. Latorre; A. El Kenawy; M. Franquesa; A. Halifa-Marin; M. Adell-Michavila; A. Crespillo; et al. (Natural Hazards, 2025)
This study introduces the first high-resolution hazard probability maps of extreme precipitation for Spain, marking a significant step toward a national climate service for hydrometeorological extremes. Using long-term daily precipitation records from a dense network of stations and incorporating topographic data, the methodology combines the Generalized Pareto distribution with universal kriging to spatially interpolate distribution parameters. These maps offer reliable estimates of extreme precipitation quantiles, validated against station-level observations, and are based on a stationary modelling framework—an approach supported by recent findings showing the temporal stability of such extremes in Spain and considered more robust than non-stationary alternatives. Distinct spatial patterns emerge, with intense daily precipitation distributed mainly along the Mediterranean coast and high total event precipitation in the northwest and southwest, reflecting the influence of varied weather systems. To support decision-making, the study aggregates these high-resolution data at the provincial level, aligning risk information with administrative boundaries, and enhancing its relevance for policy and planning. Furthermore, the maps are made accessible via an interactive online platform ( https://retornolluvias.csic.es ), enabling users to explore localized hazard probabilities, thereby supporting adaptation in water management and civil protection, among others.

Frontal lobe intra-axial schwannoma harboring a CHD7::VGLL3 fusion and heterozygous TSC2 p.F1510del mutation in a young child - Anthony V. Nguyen; Blaine H. Berger; Zied Abdullaev; Samuel Gearhart; Eduardo Castro-Echeverry; Kenneth Aldape; Eric Trumble; Norman L. Lehman (Molecular Biology Reports, 2025)

Phylogenetic Relationships of the Moles and their Relatives (Talpidae): Insights from Mitogenomes - Sara Sampaio; André Gomes-dos-Santos; L. Filipe C. Castro; Jonathan J. Hughes; Ivan N. Bolotov; Viatcheslav V. Rozhnov; Marina V. Rutovskaya; Ilia G. Meschersky; Joana Paupério; Paulo C. Alves; Jeremy B. Searle; Manuel Lopes-Lima (Evolutionary Biology, 2025)

Vermicompost, hydrogel, and beneficial soil microorganisms promote vetiver growth and microbial activity in Cu-impacted tailings - Sofia I. A. Pereira; Ana Faria; Ana S. S. Sousa; Nadine Sousa; Paula M. L. Castro; Helena Moreira (Environmental Sustainability, 2025)

Valorization of wastewater-derived biopolymers for use as soil amendments in agriculture - Catarina Miranda; Sofia I. A. Pereira; Ana S. S. Sousa; Philipp Wilfert; Mark van Loosdrecht; António Martins; Paula M. L. Castro; Catarina L. Amorim (Environmental Science and Pollution Research, 2025)

Soil fertilization potential and nutrient dynamics of organic fertilizers derived from sugarcane residues under techno-economic and environmental assessment - Thais G. Carpanez; Livia M.C. Castro; Bruna L. Moreira; Julia B.L.S. Carneiro; Eduarda V.S. Gomes; Marcelo H. Otenio; Jonathas B.G. Silva; Julio C. Balarini; Fernanda R.C. Damasceno; Miriam C.S. Amaral; Victor Rezende Moreira (Chemosphere, 2025)

Molecular docking and antitumor evaluation of liposomal nanoformulations containing citrinin - Ag-Anne Pereira Melo de Menezes; Michely Laiany Vieira Moura; José Williams Gomes de Oliveira Filho; Maria Luisa Lima Barreto do Nascimento; Juan Carlos Ramos Gonçalves; Marianna Vieira Sobral; Karinne Kelly Gadelha Marques; Felipe Cavalcanti Carneiro da Silva; Guilherme Barroso L. De Freitas; Vladimir Costa Silva; Shamya Gabriella Corrêa Coêlho; Marjorie Pereira Gualter; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Gibberellin Regulates Sugar Metabolism and Modifies Cell Wall Composition in Soybean (Glycine max L. Merrill) - Raysa M. J. Sousa; Juliane M. Henschel; Diego S. Batista; Tatiane D. Silva; Sérgio H. S. Felipe; Gabriela Torres-Silva; Paulo V. L. Souza; Silvio A. Cândido-Sobrinho; Kristhiano Chagas; Kamila M. Castro; Evandro A. Fortini; Ludmila N. F. Correia; et al. (Journal of Plant Growth Regulation, 2025)

Pilot-scale production of high-purity struvite fertilizer from livestock waste: Outcomes of the RE-LIVE WASTE project in Cyprus - Nomiki I. Kallikazarou; Olympia Nisiforou; Despoina A. Kokkinidou; Loukas Koutsokeras; Christodoulos Michael; José L. Castro; Andreas S. Anayiotos; Georgios Constantinides; George Botsaris; Ioannis A. Fotidis; Maria G. Antoniou (Journal of Environmental Management, 2025)

Consumption of yogurts containing buriti pulp and fermented milks containing orange bagasse increases the response of the endogenous antioxidant system and the expression of heat shock proteins in healthy rats - Juliana S. Graça; Bruna G. Castro; Caroline Heckler; Patrícia B. Batista; Rafael L. Camargo; Marianna M. Furtado; Luísa Freire; Mayra F. Melo; Maria Paula M.B.B. Gonçalves; Amanda M.T.M. Moya; Cínthia B.B. Cazarin; Tatiana C. Pimentel; et al. (Food Research International, 2025)

Wildlife of tidal forested wetlands in the southeastern Atlantic United States - James T. Anderson; Andrew P. Hopkins; Crystal Anderson; Miriam Boucher; Rene Brown; Aruã de Castro; Sindupa De Silva; Robert M. Greco; Jordan E. McCall; Oluwatobi Emmanuel Olaniyi; Christopher Pettengill; Akshit R. Suthar; et al. (Estuarine, Coastal and Shelf Science, 2025)

Transcriptomic resilience to heat stress in a wide-spread Acropora coral - Declan J. A. Stick; W. Jason Kennington; Carolina Castro-Sanguino; Shannon L. Duffy; Dean Z. Tysdale; James P. Gilmour; Luke Thomas (Coral Reefs, 2025)
As climate change progresses and severe disturbances become routine, understanding rates and mechanisms of recovery in habitat-forming species is central to predicting the broader response of ecosystems to climate change. Here, we combined acute experimental heat stress and RNA sequencing to explore patterns of transcriptome plasticity and resilience to heat stress in a common Acropora coral from the World Heritage-listed Ningaloo Reef. Our data showed that corals subjected to sub-bleaching temperatures (33 ℃) elicited a large transcriptional response during heat stress, but quickly recovered to baseline levels of expression 16 h after temperatures returned to pre-treatment conditions, with no evidence of bleaching. In contrast, corals exposed to a one degree increase (34 ℃) from the sub-bleaching heat treatment, mounted a transcriptional response nearly twice that of the sub-bleaching temperature, showed a lingering stress response in their transcriptome, and eventually bleached. Moreover, variation in the severity of bleaching among colonies was linked to patterns of transcriptome recovery—individuals that bleached heavily showed a larger lag in transcriptional recovery than those with lower levels of bleaching. Together, these findings provide new insight into the genetic mechanisms of heat stress recovery in coral and highlight the role of transcriptional plasticity in the resilience of coral to increasing disturbances.

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

P06-20 Citidin Deaminase as a Predictive Biomarker of Antineoplastic Toxicity: Genotyping and Phenotyping - P. Castro-Sanchez; A. Corno Caparros; L. Pitaluga Poveda; A. Cardona Llorens; M.J. Prieto Castello; D. Marhuenda Amorós (Toxicology Letters, 2025)

P06-16 Impact of citidin deaminase genetic variants on capecitabine toxicity - P. Castro-Sanchez; A. Corno-Caparrós; L. Pitaluga-Poveda; A. Cardona-Llorens; D. Marhuenda-Amorós; M.J. Prieto-Castelló (Toxicology Letters, 2025)

Multi-tissue transcriptome of Brycon amazonicus (Spix & Agassiz, 1829): insights into lipid metabolism in an Amazonian fish - Renato Barbosa Ferraz; Elsa Froufe; L. Filipe C. Castro; Manuel Nande; Karine Vasconcelos Costa; Raimundo de Jesus Tavares Diniz Neto; Óscar Monroig; André Gomes-dos-Santos (Marine Genomics, 2025)

COMBINA: coastal ocean marine biosecurity international network of the Americas - Gregory M. Ruiz; Antonio Brante; James T. Carlton; Amy L. Freestone; Inti Keith; Brenda M. Soler-Figueroa; Mark E. Torchin; Alejandro Bortolus; Ricardo Coutinho; Maria Cecilia Trindade de Castro; Thomas Wayne Therriault; Sergio Andrés Benavides Avendaño; et al. (Biological Invasions, 2025)

Impact of Novel Diets on the Distribution of Mucosal Immune Cells in the Digestive System of High-Growth Genetically Selected Gilthead Seabream (Sparus aurata) in a Long-Term Feeding Trial - Sirine Abdeljaouad; Paula Sarmiento; Rafael Ginés; Gabriela Duque; Pedro L. Castro (Fishes, 2025)
An alternative fish feed (ALT) replacing 50% of the fishmeal with poultry byproduct meal and insect meal and total fish oil with microalgae, poultry, and salmon byproducts oils was tested for 300 days on 900 gilthead seabream (Sparus aurata) with an initial body weight of 17.1 ± 1.8 g (mean ± SD) of unselected (REF) and selected (HG) genotypes. Using in situ, histochemistry, and immunohistochemistry techniques, we assessed the immune response by characterizing IgT and IgM immunoglobulins, CD3ε+ T lymphocytes, and eosinophilic granular cells (EGCs) along the digestive system. IgT mRNA+ cells were concentrated in the second part of the digestive tract, while IgM+ predominated in the first and occasionally showed intraepithelial localization. CD3ε+ and EGCs were most prominent in the midgut. The diet affected IgT and IgM mRNA+ cells mainly in the initial part of the digestive tract. For CD3ε+, the diet only affected the initial and final parts, while the ALT diet increased EGC abundance across the middle compartments. Genetic selection had minimal effect on IgT+ and CD3ε+ cells, affecting only the first compartments. The REF group showed higher IgM+ cell abundance in specific regions, while EGCs differed between genotypes, favoring anterior accumulation in HG and ileocecal abundance in the REF group.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

The social, technological, economic, and political roles of information and communication technologies in extreme heat adaptation in urban Southeast Asia - Johanne Rei R. Castro; Laurence L. Delina (Urban Climate, 2025)

Validating a landscape metric to map fire exposure to hazardous fuels in Portugal - Sidra Ijaz Khan; Maria Conceição Colaço; Ana Catarina Sequeira; Francisco Castro Rego; Jennifer L. Beverly (Natural Hazards, 2025)
Assessing wildfire hazard at the landscape level in Portugal with low-cost and time-saving methods is necessary to guide land and fire managers and protect communities at risk. This study applied a landscape metric developed in Canada to map wildfire exposure in Mainland Portugal between 1995 and 2018. The wildfire exposure metric was computed and validated by examining exposure within subsequently burned areas over five years: 1995, 2007, 2010, 2015, and 2018. Landscape fire exposure was computed by the proportion of neighborhood cells in a 100 m resolution grid that include hazardous fuel types. The resultant exposure metric analyzes the amount of land cover type in the area of a site that will either aid or prevent fire spread. The distribution of exposure levels remained relatively stable over time, decreasing just 0.5% from 1995 to 2018. Approximately 80% of burned areas occurred in sites with substantial exposure (i.e., ≥ 80%). This exposure metric, originally developed in Canada, aligned well with wildfires modulated by Portuguese climate and vegetation, leading to its successful validation. This study uses a simple, time-saving method to show high and low wildfire exposure areas, allowing managers to plan mitigation efforts at different scales, with potential applications for other countries facing large wildfire events.

Association of Aeromonas spp. with mortality and Perivisceral adipose tissue necrosis in redtail catfish (Phractocephalus hemioliopterus) - L. Caballero-Hernández; A. Castro-Alonso; M.J. Caballero; Á. Curros-Moreno; G. Montero-Hernández; D. Padilla; L. Marrero-Ponce; E. Montesdeoca-Morales (Journal of Comparative Pathology, 2025)

Retrospective characterization of viral induced skin and genital proliferative lesions in stranded cetaceans off the coasts of Spain - M.A. Jimenez Martinez; L. Sanchez Gil; I. Vargas Castro; J. Luis Crespo; M. Fayos Martinez; D. Garcia Parraga; J. Manuel Sanchez Vizcaino (Journal of Comparative Pathology, 2025)

Fatal necrotic-haemorrhagic pancreatitis associated with vibrio harveyi infection in a spiny butterfly ray (Gymnura altavela) - G. Montero-Hernández; A. Castro-Alonso; M.J. Caballero; Á. Curros-Moreno; D. Padilla; L. Caballero-Hernández; E. Montesdeoca-Morales; A. Fernández (Journal of Comparative Pathology, 2025)

Pathological study of a traumatic anthropogenic injury in the skeleton of a spiny butterfly ray (Gymnura altavela) - G. Montero-Hernández; A. Castro-Alonso; M.J. Caballero; Á. Curros-Moreno; C.M. Suárez-Santana; M.A. Rivero; L. Caballero-Hernández; M. Encinoso; A. Fernández (Journal of Comparative Pathology, 2025)

Lower inoculum sizes of phosphorus-solubilizing bacteria benefit maize growth and soil enzyme activity in P-fertilized soils - Sofia I. A. Pereira; Ana S. S. Sousa; Aldo B. Felpeto; Andreia Miguel; João C. Pinto; Paula M. L. Castro; Helena Moreira (Symbiosis, 2025)

Habitat Preference of Risso's Dolphins ( Grampus griseus ) off the South Coast of Portugal - Miguel P. Martins; Fábio L. Matos; André Cid; Guilherme Estrela; Alicia Quirin; Francisco O. Borges; Joana Castro (Marine Mammal Science, 2025)
Information on the occurrence and ecology of Risso's dolphins off the southern coast of Portugal is limited and poorly understood. This study investigated the occurrence of this species in the Algarve via presence‐absence models. In total 63 Risso's dolphin sightings were recorded with an average group size of 10 animals and a presence of immature animals in most groups (73.02%). Generalized Additive Models were fitted to test how static and dynamic oceanographic variables affected Risso's dolphin occurrence between 2010 and 2020, from a presence‐absence dataset. The optimal model showed that Risso's dolphins' probability of occurrence was higher close to the coast, and positively related to sea surface temperature, reaching a maximum presence probability between 22°C and 24°C. A positive but nonsignificant relationship between chlorophyll‐a concentration with 1 month time lag and Risso's dolphin presence was also detected. This study provides a first step to understanding habitat preference of Risso's dolphins in the south of Portugal and identifies this area's importance for the species.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

The fingerprint of pesticides in agricultural used polyethylene - Gabriela Castro; Victoria Fernández-Fernández; Miguel Cobo-Golpe; María Ramil; Enrique Blázquez-Blázquez; María L. Cerrada; I. Bernabé; J. Martínez Urreaga; M.U. de la Orden; Isaac Rodriguez (Waste Management, 2025)

Role of growth conditions and physicochemical factors controlling the removal and biomineralization of U(VI) by Stenotrophomonas bentonitica BII-R7 - Maria Pinel-Cabello; Miguel A. Ruiz-Fresneda; Iván Sánchez-Castro; Hannes Brinkmann; Henry Moll; Andrea Cherkouk; Margarita López-Fernández; Mohamed L. Merroun (Environmental Pollution, 2025)

Body development, ingestive behaviour, and physiological responses of Nelore and Crossbred heifers - C. S. Santos; A. R. D. L. Souza; A. L. J. Ferraz; F. A. M. Sterza; R. V. Rohod; M. F. Castro; L. S. Amorim; M. C. E. Queiroz; G. B. Almeida; M. V. M. Oliveira; A. R. D. Santos; D. M. Oliveira (Tropical Animal Health and Production, 2025)

Novelties from the Amazon rainforest: Froesiochloa hopkinsiana, a new herbaceous bamboo from northern Brazil, and notes on the placement of this rare genus within Olyreae (Poaceae: Bambusoideae) - Iasmin Laiane De Castro Oliveira; Kaio Vinicius A. Vidal; Pedro L. Viana; Lynn G. Clark; Reyjane P. Oliveira (Plant Systematics and Evolution, 2025)

Exopolysaccharides of Ganoderma lucidum Activate the NLRP3 Inflammasome, Modulating Phagocytes and the Response of Mice to Infection with Cryptococcus neoformans - Pedro H. M. Bürgel; Raffael J. A. de Castro; Angelina M. Basso; Luísa C. Coelho; Clara L. F. Marina; Isaque M. Siqueira; Alysia V. Gonzales; Pavel Kucheryavy; Vitor H. Pomin; Elaine Rosechrer Carbonero; Aldo H. Tavares; Anamélia Lorenzetti Bocca (Mycopathologia, 2025)

Wastewater-Based Epidemiology for Analysis of Human Papillomavirus Infections in a Uruguayan Urban Area - C. Fernandez-Sabatella; G. Corrales; L. Monzon; E. Andrade; N. Sica; E. Cardozo; N. Baccardatz; J. Jacques; S. Castro; M. Castells; M. Victoria; R. Colina (Food and Environmental Virology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Effects of dietary supplementation with slow-release urea coated with carnauba wax on intake, ingestive behavior, selectivity, ruminal parameters, performance and carcass traits of lambs - Tainan da Silva Batista; Leilson R. Bezerra; Pedro H.S. Mazza; Analivia M. Barbosa; Beatriz S.C. de Castro; Melissa D. Ferrer; Ana Carolina Ferreira; Jasiel S. de Morais; Edson C. da Silva Filho; Ronaldo L. Oliveira (Small Ruminant Research, 2025)

PD-based ADRC using time-varying gains: An application to microalgal-based bioprocess - Viyils Sangregorio-Soto; Edgar Yesid Mayorga Lancheros; Gianfranco Mazzanti; Claudia L. Garzón-Castro (Journal of Theoretical Biology, 2025)

Aerobic bioremediation of selenite in marine and freshwater environments via intracellular selenium nanoparticle formation by Pseudomonas frigusceleri MPC6 in glycerol-fed continuous bioreactors - Matias Orellana-Saez; Yeney Lauzurique; Pablo Donoso-Garcia; Manuel Carmona; Andrea Carvajal; Ana L. Riveros; Marcelo J. Kogan; Daniela F. Báez; Ignacio Poblete-Castro (Journal of Environmental Management, 2025)

Porcine circovirus type 2 (PCV2) in Brazil in the past 55 years (1967-2022): evolutionary rates and patterns - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; B. V. Lago; R. L. Silveira; T. X. Castro (Archives of Virology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

Mictlan-D3: A novel medium sized RGD-Disintegrin obtained from Crotalus mictlantecuhtli venom, in vitro tested against human breast Cancer and endothelial cells - E. Rivas-Mercado; E. Neri-Castro; V. Zarzosa; L. Hernández-Orihuela; F. Olvera-Rodríguez; J.D. Torres-Garza; L. Garza-Ocañas (Toxicology in Vitro, 2025)

A “light in the darkness”: First transcriptomic data from deep-sea spiny eels (Notacanthus, Notacanthiformes) - André Gomes-dos-Santos; André M. Machado; Francisco Baldó; Juan Carlos Arronte; L. Filipe C. Castro; David Barros-García (Marine Genomics, 2025)

Microbiome adaptation of aerobic granular sludge allows process resilience during the treatment of seawater-based wastewater with pharmaceuticals - Catarina Miranda; Alexandra S. Maia; Maria Elizabeth Tiritan; Paula M.L. Castro; Catarina L. Amorim (Journal of Water Process Engineering, 2025)

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Valorization of residual ashes from boiler combustion process into activated carbon for adsorption of food industry wastewater - L. E. N. Castro; L. R. Matheus; W. G. Sganzerla; L. M. S. Colpini (International Journal of Environmental Science and Technology, 2025)

Mold in, mold out: Harvest bins harbor viable inoculum that can be reduced using novel sanitation methods to manage blue mold decay of apples - Dianiris Luciano-Rosario; Johanny Castro; Kari A. Peter; Kerik D. Cox; Jorge M. Fonseca; Verneta L. Gaskins; Wayne M. Jurick (Postharvest Biology and Technology, 2025)

Trade-offs for healthy and sustainable diets in Europe: Social-ecological dynamics in an intensive agricultural system - A. Jiménez-Aceituno; M.D. López-Rodríguez; A.J. Castro; S. Cortés-Calderón; D. Collste; G. Aparicio; L. Rölfer; M.A. Bote; L. Marín; M.A. Gómez-Tenorio; B. González-Martín (Global Food Security, 2025)

Cost-effective alternatives to facilitate biomonitoring and bioassessment of neotropical streams - Francisco Valente-Neto; Renato B. Dala-Corte; Almir M. Cunico; André L.B. Magalhães; Bruno S. Godoy; Cecília G. Leal; Diego M.P. Castro; Diego R. Macedo; Dilermando P. Lima-Junior; Éder A. Gubiani; Fabio de O. Roque; Fabrício B. Teresa; et al. (Science of The Total Environment, 2025)

The role of photooxidation and organic matter in Cr(III) and Cr(VI) interactions with poly(lactic acid) microplastics in aqueous solution - Ricardo H.P. Pedroza; Calin David; José L. Barriada; Carlos Rey-Castro; Pablo Lodeiro (Science of The Total Environment, 2025)

Adaptative biological response of aerobic granular sludge to events of single or combined wastewater related stressors - Marta Alves; Isabel Henriques; Paula M.L. Castro; Catarina L. Amorim (Process Safety and Environmental Protection, 2025)

Baseline matters: Challenges and implications of different marine heatwave baselines - Kathryn E. Smith; Alex Sen Gupta; Dillon Amaya; Jessica A. Benthuysen; Michael T. Burrows; Antonietta Capotondi; Karen Filbee-Dexter; Thomas L. Frölicher; Alistair J. Hobday; Neil J. Holbrook; Neil Malan; Pippa J. Moore; et al. (Progress in Oceanography, 2025)

Phosphorus acquisition by plants: Challenges and promising strategies for sustainable agriculture in the 21st century - Tamara GÓMEZ-GALLEGO; Iván SÁNCHEZ-CASTRO; Lázaro MOLINA; Carmen TRASAR-CEPEDA; Carlos GARCÍA-IZQUIERDO; Juan L. RAMOS; Ana SEGURA (Pedosphere, 2025)

Nowhere to hide: massive corals’ mortality after cumulative heat stress in a putative climate change refugium - Fernando C. Cardoso; Ivan M. Carneiro; Guilherme M. Castro; Gabriel O. Cardoso; Aline Shimada; Myllena S. Pereira; Livia B. Villela; Paulo S. Salomon; Rodrigo L. Moura (Coral Reefs, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Biosynthesis of long-chain polyunsaturated fatty acids in the nereid polychaete Hediste diversicolor: Molecular cloning and functional characterisation of three fatty acyl elongases and two front-end desaturases - Andrea Villena-Rodríguez; Juan C. Navarro; Francisco Hontoria; L. Filipe C. Castro; Arne M. Malzahn; Andreas Hagemann; Óscar Monroig (Aquaculture, 2025)

Evaluating the suitability of large-scale datasets to estimate nitrogen loads and yields across different spatial scales - Andrés Felipe Suárez-Castro; Dale M. Robertson; Bernhard Lehner; Marcelo L. de Souza; Michael Kittridge; David A. Saad; Simon Linke; Rich W. McDowell; Mohammad Hassan Ranjbar; Olivier Ausseil; David P. Hamilton (Water Research, 2025)

Beyond the threshold - Different accumulation of organochlorine compounds in common dolphins (Delphinus delphis) inhabiting continental and insular ecosystems in the Northeast Atlantic - Raul Valente; Nara de Oliveira-Ferreira; Rita Ferreira; Ana M. Correia; Bárbara M.R. Manhães; Ágatha Gil; Annalisa Sambolino; Elitieri B. Santos-Neto; L. Filipe C. Castro; Haydée A. Cunha; Alexandre F. Azevedo; Ana Dinis; et al. (Environmental Pollution, 2025)

Novel combination of 3D-printing and electrochemical deposition to design and prepare metallic honeycomb supported catalysts for dry reforming of methane - O. Bazta; F.J. Botana; J.J. Calvino; M.A. Cauqui; J.M. Gatica; H. Vidal; L. González-Rovira; J. López-Castro; M.P. Yeste; G. Blanco; J.C. Hernández-Garrido (Chemical Engineering Journal, 2025)

Evaluating the precise grapevine water stress detection using unmanned aerial vehicles and evapotranspiration-based metrics - V. Burchard-Levine; I. Borra-Serrano; J. M. Peña; W. P. Kustas; J. G. Guerra; J. Dorado; G. Mesías-Ruiz; M. Herrezuelo; B. Mary; L. M. McKee; A. I. de Castro; S. Sanchez-Élez; et al. (Irrigation Science, 2025)
Precise irrigation management requires accurate knowledge of crop water demand to adequately optimize water use efficiency, especially relevant in arid and semi-arid regions. While unoccupied aerial vehicles (UAV) have shown great promise to improve the water management for crops such as vineyards, there still remains large uncertainties to accurately quantify vegetation water requirements, especially through physically-based methods. Notably, thermal remote sensing has been shown to be a promising tool to evaluate water stress at different scales, most commonly through the Crop Water Stress Index (CWSI). This work aimed to evaluate the potential of a UAV payload to estimate evapotranspiration (ET) and alternative ET-based crop water stress indices to better monitor and detect irrigation requirements in vineyards. As a case study, three irrigation treatments within a vineyard were implemented to impose weekly crop coefficient (Kc) of 0.2 (extreme deficit irrigation), 0.4 (typical deficit irrigation) and 0.8 (over-irrigated) of reference ET. Both the original Priestley-Taylor initialized two-source energy balance model (TSEB-PT) and the dual temperature TSEB (TSEB-2T), which takes advantage of high-resolution imagery to discriminate canopy and soil temperatures, were implemented to estimate ET. In a first step, both ET models were evaluated at the footprint level using an eddy covariance (EC) tower, with modelled fluxes comparing well against the EC measurements. Secondly, in-situ physiological measurements at vine level, such as stomatal conductance (g st ), leaf (Ψ leaf ) and stem (Ψ stem ) water potential, were collected simultaneously to UAV overpasses as plant proxies of water stress. Different variants of the CWSI and alternative metrics that take advantage of the partitioned ET from TSEB, such as Crop Transpiration Stress Index (CTSI) and the Crop Stomatal Stress Index (CSSI), were also evaluated to test their statistical relationship against these in-situ physiological indicators using the Spearman correlation coefficient ( ρ ). Both TSEB-PT and TSEB-2T CWSI related similarly to in-situ measurements (Ψ leaf : ρ ~ 0.4; Ψ stem : ρ ~ 0.55). On the other hand, stress indicators using canopy fluxes (i.e. CTSI and CSSI) were much more effective when using TSEB-2 T (Ψ leaf : ρ = 0.45; Ψ stem : ρ = 0.62) compared to TSEB-PT (Ψ leaf : ρ = 0.18; Ψ stem : ρ = 0.49), revealing important differences in the ET partitioning between model variants. These results demonstrate the utility of physically-based models to estimate ET and partitioned canopy fluxes, which can enhance the detection of vine water stress and quantitatively assess vine water demand to better manage irrigation practices.

Optical immunosensor panel using quantum dot-antibody conjugates for highly sensitive detection of carbohydrate antigen 19–9 (CA19-9) - Daniela Oliveira; Pedro Oliveira; Ana Xu; Eduarda Rodrigues; Susana G. Guerreiro; Rafael C. Castro; David S.M. Ribeiro; João L.M. Santos; Ana Margarida L. Piloto (Analytica Chimica Acta, 2025)

Environmental factors determining the distribution of Limnoperna fortunei and its impact on benthic communities in the reservoirs of the Rio Negro (Uruguay)) - L. Capurro; J. Pereira; M. Castro; C. Ferrer; D. Fabián; P. Muniz; E. Brugnoli (Biological Invasions, 2025)

Distance From Nest and Climate Explain Geographical Trends of Harvester Ant's Food Resource Use: A Multi‐Species Approach - Diego Anjos; Pedro Luna; Kleber Del‐Claro; Rodrigo G. Pol; Javier Lopez de Casenave; Helena Maura Torezan‐Silingardi; Martha L. Baena; Florencia Baudino; Judie Bronstein; Melissa Burt; Eduardo Calixto; Ana Laura Cao; et al. (Journal of Biogeography, 2025)
Main Animals not only forage for abundant and nearby resources, but their diets can also be influenced by abiotic and geographic factors. This often results in non‐random interactions among species. We investigate how seed density, distance from nest, abiotic (e.g., climate stability, temperature, precipitation) and geographic factors (e.g., latitude, elevation and continental hemisphere) influence the removal of food items (i.e., seeds and dead arthropods) by Pogonomyrmex species. Location South and North America, from Patagonia to the Rocky Mountains. Taxon Genus Pogonomyrmex (Formicidae: Hymenoptera). Methods Conducting standardised experiments, we performed a seed removal experiment and an assessment of the items retrieved by ant workers of 160 nests from eight Pogonomyrmex spp. at 16 sites extending the American continent. Results Pogonomyrmex ants native to North America removed more seeds than their South American counterpart. In general, results align with optimal foraging theory, indicating a higher probability of seed removal near ant nests. High climate stability correlated with lower seed predation rates, emphasising seed consumption's significance in historically arid environments. Increased precipitation and temperature led to reduced removal of food resources, suggesting reduced water availability and lower mean temperatures increases the consumption of seeds by harvester ants. Conclusions Overall, Pogonomyrmex ants' food resource use is influenced by a combination of factors such as region, distance from the nest and climate. This study underscores harvester ants' potential impact on plant distribution over large spatial scales consuming seeds from the immediate proximity of their nest and preventing establishment.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A Probabilistic View of Forbidden Links: Their Prevalence and Their Consequences for the Robustness of Plant–Hummingbird Communities - François Duchenne; Elisa Barreto; Esteban A. Guevara; Holger Beck; Carolina Bello; Rafaela Bobato; Daniela Bôlla; Emanuel Brenes; Nicole Büttner; Ana P. Caron; Nelson Chaves‐Elizondo; María J. Gavilanes; et al. (Ecology Letters, 2025)
The presence in ecological communities of unfeasible species interactions, termed forbidden links, due to physiological or morphological exploitation barriers has been long debated, but little direct evidence has been found. Forbidden links are likely to make ecological communities less robust to species extinctions, stressing the need to assess their prevalence. Here, we used a dataset of plant–hummingbird interactions, coupled with a Bayesian hierarchical model, to assess the importance of exploitation barriers in determining species interactions. We found evidence for exploitation barriers between flowers and hummingbirds across the 32 studied communities; however, the proportion of forbidden links changed drastically among communities because of changes in trait distributions. The higher the proportion of forbidden links, the more they decreased network robustness because of constraints on interaction rewiring. Our results suggest that exploitation barriers are not rare in plant–hummingbird communities and have the potential to limit the rescue of species experiencing partner extinction.

Exploring the potential of a waste-derived bone char for pharmaceuticals adsorption in saline-based wastewater - Catarina Miranda; Francesca Scalera; Andreana Piancastelli; Robert C. Pullar; Maria Elizabeth Tiritan; Clara Piccirillo; Paula M.L. Castro; Catarina L. Amorim (Sustainable Chemistry and Pharmacy, 2024)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Monitoring macroplastics in aquatic and terrestrial ecosystems: Expert survey reveals visual and drone-based census as most effective techniques - L. Gallitelli; P. Girard; U. Andriolo; M. Liro; G. Suaria; C. Martin; A.L. Lusher; K. Hancke; MCM Blettler; O. Garcia-Garin; I.E. Napper; L. Corbari; et al. (Science of The Total Environment, 2024)

Novel synthetic UV screen compounds inspired in mycosporine-like amino acids (MAAs): Antioxidant capacity, photoprotective properties and toxicity - Félix L. Figueroa; Pablo Castro-Varela; Julia Vega; Raúl Losantos; Beatriz Peñín; Leonardo López-Cóndor; María Jesús Pacheco; Sofía Latorre Redoli; Manuel Marí-Beffa; Roberto Abdala-Díaz; Diego Sampedro (Journal of Photochemistry and Photobiology B: Biology, 2024)

Harnessing the power of microalgae consortia for sustainable crop production: case study on lettuce (Lactuca sativa L.) - Luis Eduardo Díaz; Juan David Gonzalez; Maria Paula Morales-Gonzalez; Claudia L. Garzón-Castro (Journal of Applied Phycology, 2024)
Due to global food demand and need to protect the environment, improving crop productivity while reducing agrochemical use has become crucial. Microalgae offer a potential solution as they exhibit biostimulant and biofertilizer effects, improving both crop and soil quality. This study aimed to assess the impact of suspensions of freeze-dried Chlorella vulgaris (UTEX 265), Scenedesmus obliquus (UTEX 393), and Haematococcus pluvialis (UTEX 2505) biomass in distilled water on lettuce ( Lactuca sativa L.) germination and development. Different microalgae treatments, individually and mixtures, were applied. The study evaluated various plant growth parameters and the concentration of nutritional constituents, including reducing sugars, total polyphenols, antioxidant capacity, and chlorophyll a . In the first stage (germination), microalgae treatments ( C. vulgaris 2 g (CV2),; C vulgaris 0.66 g, S. obliquus 0.66 g and H. pluvialis 0.7 g (CV0.7:SO0.7:HP0.7) and C. vulgaris 1.5 g and S. obliquus 1.5 g (CV1.5:SO1.5) increased L. sativa seed germination rate and the number of germinated seeds. Significant changes were observed in growth-related variables such as height (CV0.7:SO9.7:HP0.7), stem diameter ( C. vulgaris 3 g (CV3)), root length ( S. obliquus 3 g (SO3)), and leaf area (CV1.5:SO1.5). In the second stage (plant development), microalgae treatments significantly increased dry weight from 2.71% (CV1.5:SO1.5) to 48.52% (SO3), reduced sugars from 3.20% (CV3) to 59.05% (CV1.5:SO1.5), total polyphenols from 7.99% (CV3) to 40.15% (CV1.5:SO1.5), antioxidant capacity from 0.77% (CV0.7:SO9.7:HP0.7) to 17.40% (CV1:HP1), and chlorophyll a from 23.01% (CV1.5:SO1.5) ( p ≤ 0.05). C. vulgaris and S. obliquus in blending were identified as the main microalgae promoting positive effects on L. sativa development. This study confirms that microalgae, particularly C. vulgaris and S. obliquus , can enhance crop quality, specifically in L. sativa . These findings demonstrate the potential of microalgae as biostimulants, supporting their application to improve crop productivity and emphasizing their role in sustainable agriculture.

Polymorphic pseudogenes in the human genome - a comprehensive assessment - Mónica Lopes-Marques; M. João Peixoto; David N. Cooper; M. João Prata; Luísa Azevedo; L. Filipe C. Castro (Human Genetics, 2024)
Background: Over the past decade, variations of the coding portion of the human genome have become increasingly evident. In this study, we focus on polymorphic pseudogenes, a unique and relatively unexplored type of pseudogene whose inactivating mutations have not yet been fixed in the human genome at the global population level. Thus, polymorphic pseudogenes are characterized by the presence in the population of both coding alleles and non-coding alleles originating from Loss-of-Function (LoF) mutations. These alleles can be found both in heterozygosity and in homozygosity in different human populations and thus represent pseudogenes that have not yet been fixed in the population. Results: A methodical cross-population analysis of 232 polymorphic pseudogenes, including 35 new examples, reveals that human olfactory signalling, drug metabolism and immunity are among the systems most impacted by the variable presence of LoF variants at high frequencies. Within this dataset, a total of 179 genes presented polymorphic LoF variants in all analysed populations. Transcriptome and proteome analysis confirmed that although these genes may harbour LoF alleles, when the coding allele is present, the gene remains active and can play a functional role in various metabolic pathways, including drug/xenobiotic metabolism and immunity. The observation that many polymorphic pseudogenes are members of multigene families argues that genetic redundancy may play a key role in compensating for the inactivation of one paralogue. Conclusions: The distribution, expression and integration of cellular/biological networks in relation to human polymorphic pseudogenes, provide novel insights into the architecture of the human genome and the dynamics of gene gain and loss with likely functional impact.

Magmatic and rock-leaching contributions to the metal load in hydrothermal fluids at þeistareykir, Iceland - Marion Saby; Vincent van Hinsberg; Daniele L. Pinti; Kim Berlo; Bjarni Gautason; Ásgerður Sigurðardóttir; M. Clara Castro (Applied Geochemistry, 2024)

Analysis of the pharyngeal structure of the genus Oreochromis for species identification through geometric morphometrics in the Aguamilpa reservoir, Nayarit, Mexico - Breidy L. Cuevas-Rodríguez; Wally K. Rubio-Gómez; Jasmín Granados-Amores; Jesús J. Dueñas-Romero; Francisco J. Valdez-González; Eduardo Sandoval-Castro; Claudia A. González-Huerta; Juan P. González-Hermoso; Oscar I. Zavala-Leal (Zoologischer Anzeiger, 2024)

Novel PCR assay for the identification of two transmissible cancers in Cerastoderma edule - Martín Santamarina; Alicia L. Bruzos; Ana Pequeño-Valtierra; Jorge Rodríguez-Castro; Seila Díaz; Jose M.C. Tubio (Journal of Invertebrate Pathology, 2024)

Assessment of endogenous and exogenous silver nanoparticles effects on the microalgae Chlorella vulgaris - Natalí Romero; Adrianne Brito; Horacio E. Troiani; Iseli L. Nantes; Guillermo R. Castro; Ana M. Gagneten (World Journal of Microbiology and Biotechnology, 2024)

Pinus cembroides, and P. orizabensis grafts, a viable option for pink pine nut production - Sandra L. Castro-Garibay; Omegar Cruz-Arvizu; Isaí Monroy-González; Alma D. Abarca-Cervantes; Iris J. Cruz-Larios; Marcelina Arguello-Hernández (New Forests, 2024)

Influence of Dolphin-Watching Tourism Vessels on the Whistle Emission Pattern of Common Dolphins and Bottlenose Dolphins - Ana A. Silva; Joana Castro; André Cid; Sérgio M. Jesus; Fábio L. Matos (Oceans, 2024)
Recent years have seen a notable rise in dolphin-watching boat activities along the Algarve coast in Portugal, potentially affecting the common dolphin (Delphinus delphis) and bottlenose dolphin (Tursiops truncatus) local populations. This study examines the impact of increasing underwater noise levels from these boats on dolphin vocalizations. Field recordings were conducted from June to September 2022, analyzing dolphin whistles in various boat presence scenarios. The results indicate significant changes in whistle-frequency characteristics with boat presence, including increased start, low, and high frequencies, alongside a decrease in the number of inflection points in modulated whistles. The changes might negatively impact dolphin populations viability, underscoring the need for further research. Additionally, improved mitigation strategies may be necessary to reduce the potential negative effects of dolphin watching on cetacean communication and behavior in the Algarve region.

Evolution of the transtensional Barreirinhas pull-apart system in the Brazilian Equatorial margin and its correlation with the African conjugate counterpart - David L. de Castro; Diógenes C. Oliveira; Francisco H.R. Bezerra (Tectonophysics, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Efficient photocatalytic activity and selective adsorption of UiO-67 (Zr)/g-C3N4 composite toward a mixture of parabens - K.I. Bautista-Cano; L. Hinojosa-Reyes; E.J. Ruiz-Ruiz; E. Díaz Barriga-Castro; J.L. Guzmán-Mar; A. Hernández-Ramírez (Environmental Research, 2024)

Protease inhibitors characterisation by SDS-PAGE and MALDI-TOF from Alocasia macrorrhizos and their modulation of macrophage immune-inflammatory properties - Isac H. Cordeiro; Nerilson M. Lima; Elaine C. Scherrer; Gabriela P. Carli; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Marcone A. L. de Oliveira; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2024)

Periorbital necrotizing fasciitis: clinical perspectives on nine cases - David Oliver-Gutierrez; R. L. P. van der Veen; Elena Ros-Sánchez; Gloria Segura-Duch; Tirso Alonso; Alejandra Herranz-Cabarcos; Jessica Matas; Roberto Castro Seco; Miguel Ángel Arcediano; Miguel Ángel Zapata; Joan Oliveres (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

P13-07 Uranium and kidney cancer: insights from genetically engineered mouse models in the UKCAN project - L. De Castro; O. Claude; M. Brisset; C. Gillot; A. Manoury; A. Sache; F. Voyer; D. Suhard; V. Monceau; C. Bouvier-Capely; C. Ibanez; Y. Guéguen (Toxicology Letters, 2024)

Detection and molecular characterization of a novel mitovirus associated with Passiflora edulis Sims - Yam Sousa Santos; Andreza Henrique Vidal; Emanuel Felipe Medeiros Abreu; Isadora Nogueira; Fábio Gelape Faleiro; Cristiano Castro Lacorte; Fernando L. Melo; Magnólia de Araújo Campos; Rafael Reis de Rezende; Tulio Morgan; Arvind Varsani; Poliane Alfenas-Zerbini; et al. (Archives of Virology, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Comparison of direct and indirect soil organic carbon prediction at farm field scale - C. Segura; A.L. Neal; L. Castro-Sardiňa; P. Harris; M.J. Rivero; L.M. Cardenas; J.G.N. Irisarri (Journal of Environmental Management, 2024)

Management of non-indigenous species in Macaronesia: Misconceptions and alerts to decision-makers - Nuno Castro; Pedro M. Félix; Ignacio Gestoso; José L. Costa; João Canning-Clode (Marine Pollution Bulletin, 2024)

Organic petrology and geochemistry data reveal depositional and thermal history of coal in the Guaduas formation, Colombian Eastern Cordillera - L. Camacho-Aristizabal; L. Burnaz; L. Castro-Vera; L. Mojica Silva; R. Littke (International Journal of Coal Geology, 2024)

Synthesis of GO-Fe3O4/Ag and its Evaluation in the Aqueous Removal of Pb (II) and Methylene Blue - L. G. García; R. Pérez; Nicolás Cayetano-Castro; G. Rosas (Water, Air, & Soil Pollution, 2024)

Assessing the dynamics of common dolphin ( Delphinus delphis ) mother‐calf pairs along the south coast of Portugal using unmanned aerial vehicles - Joana Castro; André Cid; Alicia Quirin; Fábio L. Matos; Rui Rosa; Heidi C. Pearson (Marine Mammal Science, 2024)
Maternal grouping dynamics involve trade‐offs between: (1) infant protection from predation (predation hypothesis), (2) infant protection from male harassment (infant safety hypothesis), and (3) reducing scramble competition for prey resources (foraging‐type scramble competition hypothesis). Using unmanned aerial vehicles, we assessed grouping dynamics in common dolphin ( Delphinus delphis ) groups containing mother‐calf pairs to address these hypotheses. We analyzed social aspects and structural group elements using generalized additive mixed models and modeled group formation using multinomial generalized estimating equations. Calf proportion was higher in very compact groups and in groups of 10–20 individuals but decreased in larger groups. The frequency of socio‐sexual behaviors increased in larger groups and decreased in groups with higher calf proportion. Calf distance to its nearest neighbor decreased with increasing group size and cohesion. With a higher proportion of calves, scatter (versus parallel) formation was less frequent. A calf's nearest neighbor was most often (55.4%) a nonmother. Calves showed a preference for being in the front center of the group. These results offer strong support for the predation and infant safety hypotheses and partial support for the foraging‐type scramble competition hypothesis. This work provides insight into the adaptive function of maternal strategies in a small delphinid.

A multi-tissue de novo transcriptome assembly and relative gene expression of the vulnerable freshwater salmonid Thymallus ligericus - Giulia Secci-Petretto; Steven Weiss; André Gomes-dos-Santos; Henri Persat; André M. Machado; Inês Vasconcelos; L. Filipe C. Castro; Elsa Froufe (Genetica, 2024)
Freshwater ecosystems are among the most endangered ecosystems worldwide. While numerous taxa are on the verge of extinction as a result of global changes and direct or indirect anthropogenic activity, genomic and transcriptomic resources represent a key tool for comprehending species' adaptability and serve as the foundation for conservation initiatives. The Loire grayling, Thymallus ligericus , is a freshwater European salmonid endemic to the upper Loire River basin. The species is comprised of fragmented populations that are dispersed over a small area and it has been identified as a vulnerable species. Here, we provide a multi-tissue de novo transcriptome assembly of T. ligericus . The completeness and integrity of the transcriptome were assessed before and after redundancy removal with lineage-specific libraries from Eukaryota, Metazoa, Vertebrata, and Actinopterygii. Relative gene expression was assessed for each of the analyzed tissues, using the de novo assembled transcriptome and a genome-based analysis using the available T. thymallus genome as a reference. The final assembly, with a contig N50 of 1221 and Benchmarking Universal Single-Copy Orthologs (BUSCO) scores above 94%, is made accessible along with structural and functional annotations and relative gene expression of the five tissues (NCBI SRA and FigShare databases). This is the first transcriptomic resource for this species, which provides a foundation for future research on this and other salmonid species that are increasingly exposed to environmental stressors.

Optimizing biological and physicochemical properties of acidic mine tailings through combined organo-mineral amendments and topsoil application - Atika Madline; Leila Benidire; Sofia I. A. Pereira; Hicham El khalil; Adam Michalski; Paula M. L. Castro; Przemysław Charzyński; Ali Boularbah (Journal of Soils and Sediments, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Assessment of water stress impact on olive trees using an accurate determination of the endocarp development - Marta Sánchez-Piñero; Mireia Corell; Laura L. de Sosa; Alfonso Moriana; Noemí Medina-Zurita; Engracia Madejón; Ignacio Girón; Pedro Castro-Valdecantos; María José Martín-Palomo; David Pérez-López (Irrigation Science, 2024)
When considering deficit irrigation, the most resistant period to water stress in olive crops is during the pit hardening. However, the determination of this period and the impact that water stress has on its onset or duration have not been clearly established. The aim of this work is to describe the impact of water stress on three processes that determine fruit development: fruit growth, endocarp hardening, and oil accumulation. This experiment was conducted between 2021 and 2022, in a plot with olive trees that were 3 years old at the beginning of the experiment. The young trees were of cv Manzanilla de Sevilla and were planted in a 4 × 1.5 m frame. The treatments were: Control, irrigated close to what is considered the optimum level in which the water status of the crop ensures the absence of water stress; RDI, with a moderate stress during the pit hardening stage; Rainfed and Traditional Rainfed. This latter was included only in 2022 using a 7 × 5 m frame. Traditional Rainfed was included to compare with Rainfed, these were similar in the maximum level of water stress but not in the duration. The fruit growth, oil accumulation, and endocarp hardness were measured for a period of 2 years. The hardness curves fit accurately established Period II which was the one with the fast hardness increases. The water potential was measured periodically on leaves at midday, whereby the minimum and average potential and the stress integral were obtained for each of the periods indicated before using pit hardness measurements. The results suggest that endocarp hardening was the process most resistant to water stress, as it showed very little variation from the seasonal pattern, despite the high levels of stress achieved. The fruit growth process was the most sensitive to water stress, but the recovery was fast in conditions of moderate water stress level. The oil accumulation started slowly during Period II, but its rate increased at the end of the period. This later process was moderately resistant to water stress. However, although the accumulation rate was faster during Period III, it was influenced by the water status during Period II. Cumulative water stress was related with fruit growth and oil accumulation processes. Endocarp development could be useful for determining a/the deficit irrigation period because of its almost constant pattern. These periods would permit water management optimization according to final use of the fruit (oil or table). However, continuous monitoring of water stress would be needed.

Enhancing Fish Auction with Deep Learning and Computer Vision: Automated Caliber and Species Classification - Javier Jareño; Guillermo Bárcena-González; Jairo Castro-Gutiérrez; Remedios Cabrera-Castro; Pedro L. Galindo (Fishes, 2024)
The accurate labeling of species and size of specimens plays a pivotal role in fish auctions conducted at fishing ports. These labels, among other relevant information, serve as determinants of the objectivity of the auction preparation process, underscoring the indispensable nature of a reliable labeling system. Historically, this task has relied on manual processes, rendering it vulnerable to subjective interpretations by the involved personnel, therefore compromising the value of the merchandise. Consequently, the digitization and implementation of an automated labeling system are proposed as a viable solution to this ongoing challenge. This study presents an automatic system for labeling species and size, leveraging pre-trained convolutional neural networks. Specifically, the performance of VGG16, EfficientNetV2L, Xception, and ResNet152V2 networks is thoroughly examined, incorporating data augmentation techniques and fine-tuning strategies. The experimental findings demonstrate that for species classification, the EfficientNetV2L network excels as the most proficient model, achieving an average F-Score of 0.932 in its automatic mode and an average F-Score of 0.976 in its semi-automatic mode. Concerning size classification, a semi-automatic model is introduced, where the Xception network emerges as the superior model, achieving an average F-Score of 0.949.

Organophosphate ester additives and microplastics in benthic compartments from the Loire estuary (French Atlantic coast) - J. Castro-Jiménez; Y. Aminot; N. Bely; C. Pollono; B.I.T. Idjaton; L. Bizzozero; O. Pierre-Duplessix; N.N. Phuong; J. Gasperi (Marine Pollution Bulletin, 2024)

An historical “wreck”: A transcriptome assembly of the naval shipworm, Teredo navalis Linnaeus, 1978 - André Gomes-dos-Santos; Marcos Domingues; Raquel Ruivo; Elza Fonseca; Elsa Froufe; Diana Deyanova; João N. Franco; L. Filipe C. Castro (Marine Genomics, 2024)

A whole-body transcriptome assembly of the annelid worm Hediste diversicolor - André M. Machado; Rodrigo Samico; Marcos Domingues; Andreas Hagemann; Luísa M.P. Valente; Arne M. Malzahn; André Gomes-dos-Santos; Raquel Ruivo; Juan Carlos Navarro; Óscar Monroig; L. Filipe C. Castro (Marine Genomics, 2024)

Polyhydroxyalkanoates production from a waste-derived feedstock driven by the reactor operating conditions: The role of biomass microbiome and its reactivation capacity - Eliana C. Guarda; Catarina L. Amorim; Gabriele Pasculli; Paula M.L. Castro; Claudia F. Galinha; Anouk F. Duque; Maria A.M. Reis (Journal of Cleaner Production, 2024)

The key role played by mesoporous alumina as binder for obtaining ultra-hard CaO based pellets for thermochemical heat storage leveraging the CaO/CaCO3 cycle - D. Castro-Yáñez; M. Erans; A. Peral; R. Sanz; J. González-Aguilar; M. Romero; L. Briones; E.S. Sanz-Pérez; J.M. Escola (Journal of Cleaner Production, 2024)

Synthesis of ultramicroporous zeolitic imidazolate framework ZIF-8 via solid state method using a minimum amount of deionized water for high greenhouse gas adsorption: A computational modeling - C.H. Belgacem; N. Missaoui; M.A.H. Khalafalla; G. Bouzid; H. Kahri; A.H. Bashal; A. Dhahri; L. Nouar; F.J. Melendez; M.E. Castro; H. Ghalla; Y. Zhou (Journal of Environmental Chemical Engineering, 2024)

Bio-based superabsorbent hydrogels for nutrient release - Alessandra B. Ribeiro; Helena Moreira; Sofia I.A. Pereira; Mariana Godinho; Ana Sofia da Silva Sousa; Paula Castro; Carla F. Pereira; Francisca Casanova; Ricardo Freixo; Manuela E. Pintado; Óscar L. Ramos (Journal of Environmental Chemical Engineering, 2024)

Unravelling the main immune repertoire of Paracentrotus lividus following Vibrio anguillarum bath challenge - Sergio Fernández-Boo; André Machado; L. Filipe C. Castro; Rita Azeredo; Benjamin Costas (Fish & Shellfish Immunology, 2024)

Near-slope turbulence in a Rockall canyon - Hans van Haren; Gunnar Voet; Matthew H. Alford; Bieito Fernández-Castro; Alberto C. Naveira Garabato; Bethan L. Wynne-Cattanach; Herlé Mercier; Marie-José Messias (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Retrospective sub-seasonal forecasts of extreme precipitation events in the Arabian Peninsula using convective-permitting modeling - Christoforus Bayu Risanto; Hsin-I. Chang; Thang M. Luong; Hari P. Dasari; Raju Attada; Christopher L. Castro; Ibrahim Hoteit (Climate Dynamics, 2024)

R-phycoerythrin alginate/shellac beads by external gelation: Process optimization and the effects of gastrointestinal digestion for nutraceutical applications - Pablo Castro-Varela; Mónica Rubilar; Antonio Martínez-Férez; David Fuentes-Ríos; Juan Manuel López-Romero; Claudio Alarcón; Roberto Abdala-Díaz; Félix L. Figueroa (Algal Research, 2024)

Hospital food management: a multi-objective approach to reduce waste and costs - Mariana Arriz-Jorquiera; Jorge A. Acuna; Marian Rodríguez-Carbó; José L. Zayas-Castro (Waste Management, 2024)

Leucaena leucocephala toxicity in Brazilian horses - Mizael Machado; Cintia R.R. Queiroz-Machado; Dale R. Gardner; Márcio B. Castro; Antônio Carlos L. Câmara; Luciano A. Pimentel; Glauco J.N. Galiza; Franklin Riet-Correa (Toxicon, 2024)

What makes a cyanobacterial bloom disappear? A review of the abiotic and biotic cyanobacterial bloom loss factors - Ted D. Harris; Kaitlin L. Reinl; Marzi Azarderakhsh; Stella A. Berger; Manuel Castro Berman; Mina Bizic; Ruchi Bhattacharya; Sarah H. Burnet; Jacob A. Cianci-Gaskill; Lisette N. de Senerpont Domis; Inge Elfferich; K. Ali Ger; et al. (Harmful Algae, 2024)

Effects of parity, seasonal heat stress, and colostrum collection time postpartum on colostrum quality of Holstein cattle in an arid region - L. Avendaño-Reyes; U. Macías-Cruz; M. A. Sánchez-Castro; F. Anzures-Olvera; R. Vicente-Pérez; M. Mellado; R. Zamorano-Algándar; P. H. Robinson; V. J. Castañeda-Bustos; A. López-Baca (International Journal of Biometeorology, 2024)

Reinforcement of alkali-activated cements based matrices using olive pruning fibres as an alternative to traditional fibres - M.A. Gómez-Casero; L. Pérez-Villarejo; E. Castro; D. Eliche-Quesada (Sustainable Chemistry and Pharmacy, 2024)

Precision and accuracy of common coral reef sampling protocols revisited with photogrammetry - Ivan M. Carneiro; João A. Sá; Pamela M. Chiroque-Solano; Fernando C. Cardoso; Guilherme M. Castro; Paulo S. Salomon; Alex C. Bastos; Rodrigo L. Moura (Marine Environmental Research, 2024)

Bacterial nanocellulose spheres coated with meta acrylic copolymer: Vaccinium meridionale swartz extract delivery for colorectal cancer chemoprevention - M. Osorio; L. Posada; E. Martínez; V. Estrada; G. Quintana; Maria E. Maldonado; S. Peresin; J. Orozco; C. Castro (Food Hydrocolloids, 2024)

Towards quantifying atmospheric dispersion of pesticide spray drift in Yuma County Arizona - Sunyi Yuan; Avelino F. Arellano; Lauren Knickrehm; Hsin-I Chang; Christopher L. Castro; Melissa Furlong (Atmospheric Environment, 2024)

Terminalia catappa L. leaf extract interferes with biofilm formation of Vibrio parahaemolyticus and enhances immune response of Penaeus vannamei against acute hepatopancreatic necrosis disease (AHPND) - Sheila D.A. Mantaring; Jan Rotsen Kyle Delos Santos; Romulo Estrella; John Paulo G. Jose; Ian John L. Castro; Ursela G. Bigol; John Paul Matthew D. Guzman (Aquaculture, 2024)

Beyond fish oil: Assessing the implications of alternative dietary lipid sources for turbot (Scophthalmus maximus) on growth, nutrient utilization and muscle quality - M. Monteiro; A. Marques; R.S. Costa; M.A. Salgado; C. Castro; L. Conceição; L.M.P. Valente (Aquaculture, 2024)

Vertically distinct sources modulate stable isotope signatures and distribution of Mesozooplankton in central Patagonia: The Golfo de Penas - Baker Channel connection and analogies with the Beagle Channel - Leonardo R. Castro; Samuel Soto-Mendoza; Luciana Riccialdelli; María L. Presta; Pamela Barrientos; Humberto E. González; Giovanni Daneri; Marcelo Gutiérrez; Paulina Montero; Italo Masotti; Beatriz Díez (Journal of Marine Systems, 2024)

Enzymatic de-esterification and depolymerization of apple pomace (Malus domestica var. Blanca de Asturias) pectin impacts lipid digestion in vitro - B.E. Morales-Contreras; L. Wicker; W. Rosas-Flores; J.A. Gallegos-Infante; J.C. Contreras-Esquivel; J. Morales-Castro (Food Hydrocolloids, 2024)

Removing color while lowering toxicity: the case for decolorization of textile dyes and simulated effluents with yeasts - M. Mendes; A. C. Cassoni; S. Alves; P. Moreira; M. E. Pintado; P. M. L. Castro (International Journal of Environmental Science and Technology, 2024)

How complex is the hidden species diversity of the teleost Plotosus genus? - Elsa Froufe; André Gomes-dos-Santos; Ana Matos; Jonathan Wilson; Salman Malakpourkolbadinezhad; Daniel D. Pereira; Randal Singer; L. Filipe C. Castro (Ichthyological Research, 2024)
The striped eel catfish, Plotosus lineatus was first described by Thunberg in 1787 from the Indo-Pacific region in the East Indian Ocean. Since then, the species has been recorded in various marine and brackish habitats in Japan, southern Korea, the Ogasawara Islands, Australia, Lord Howe Island, Palau and Yap in Micronesia, East Africa to Samoa, Madagascar, Red Sea and the Persian Gulf. Occurrences of this species have also been registered in the Mediterranean Sea, a non-native location, indicating a possible biological invasion event. Despite its long history, the taxonomic status of the P. lineatus species complex remains puzzling and uncertain. Here, we analysed all the available mitochondrial cytochrome c oxidase subunit 1 sequences (NCBI and BOLD) from specimens covering the current known distribution range, in an attempt to clarify the evolutionary relationships of different lineages within this species. We deduce nine monophyletic Lineages - I–IX , of P. lineatus with Kimura-2P distances ranging from 2% to 16%, with a mean intraspecific distance of 6%. Strikingly, Lineage V is composed uniquely of Mediterranean-captured individuals, with an unknown evolutionary origin. These findings strongly suggest the need for a careful species taxonomic reassessment. Some Lineages are composed of individuals from specific geographic locations (e.g., Australia and Indonesia), while others include specimens from broader geographic areas (e.g., almost all Indo-Pacific coastline). Additionally, several deposited sequences are most likely the result of morphology-based misidentifications. Due to the biological invasive potential, as well as the use of the species as a valuable physiology model, the P. lineatus species complex requires further attention. Overall our study offers a clear framework for future comparative studies of striped eel catfish individuals captured from different ecosystems.

Immunohistochemical characterisation of the adult Nothobranchius furzeri intestine - Janina Borgonovo; Camilo Allende-Castro; Danilo B. Medinas; Deyanira Cárdenas; María Paz Cuevas; Claudio Hetz; Miguel L. Concha (Cell and Tissue Research, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Capillary electrophoresis–mass spectrometry-based approaches for food analysis and food metabolomics - María Castro-Puyana; María L Marina (Current Opinion in Food Science, 2023)

Variation in the fatty acid composition of microalgal lipids due to the effect of the extraction method - F. V. Pérez-Barradas; L. A. Ortega-Clemente; I. A. Pérez-Legaspi; M. I. Jiménez-García; A. A. Huerta-Heredia; R. Quintana-Castro (Journal of Applied Phycology, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Altered E-cadherin/β-catenin expression in feline cutaneous squamous cell carcinomas - Berenice L. Sanz Ressel; Gimena Gomez Castro; Adriana R. Massone; Claudio G. Barbeito (Journal of Comparative Pathology, 2023)

Reconstructing depositional environments through cave interior facies: The case of Galería Complex (Sierra de Atapuerca, Spain) - I. Campaña; A. Benito-Calvo; A. Pérez-González; A.I. Ortega; A. Álvaro-Gallo; L. Miguens-Rodríguez; J. Iglesias-Cibanal; J.M. Bermúdez de Castro; E. Carbonell (Geomorphology, 2023)

Basking in the sun: how mosses photosynthesise and survive in Antarctica - Hao Yin; Alicia V. Perera-Castro; Krystal L. Randall; Johanna D. Turnbull; Melinda J. Waterman; Jodie Dunn; Sharon A. Robinson (Photosynthesis Research, 2023)
The Antarctic environment is extremely cold, windy and dry. Ozone depletion has resulted in increasing ultraviolet-B radiation, and increasing greenhouse gases and decreasing stratospheric ozone have altered Antarctica’s climate. How do mosses thrive photosynthetically in this harsh environment? Antarctic mosses take advantage of microclimates where the combination of protection from wind, sufficient melt water, nutrients from seabirds and optimal sunlight provides both photosynthetic energy and sufficient warmth for efficient metabolism. The amount of sunlight presents a challenge: more light creates warmer canopies which are optimal for photosynthetic enzymes but can contain excess light energy that could damage the photochemical apparatus. Antarctic mosses thus exhibit strong photoprotective potential in the form of xanthophyll cycle pigments. Conversion to zeaxanthin is high when conditions are most extreme, especially when water content is low. Antarctic mosses also produce UV screening compounds which are maintained in cell walls in some species and appear to protect from DNA damage under elevated UV-B radiation. These plants thus survive in one of the harshest places on Earth by taking advantage of the best real estate to optimise their metabolism. But survival is precarious and it remains to be seen if these strategies will still work as the Antarctic climate changes.

Trophic ecology of common bottlenose dolphins in a pelagic insular environment inferred by stable isotopes - Ester Dias; Morgane Dromby; Rita Ferreira; Ágatha Gil; Raquel Tejerina; L. Filipe C. Castro; Massimiliano Rosso; Isabel Sousa-Pinto; Joel C. Hoffman; Maria A. Teodósio; Ana Dinis; Filipe Alves (Hydrobiologia, 2023)
The common bottlenose dolphin ( Tursiops truncatus ) is a top marine predator widely dispersed in coastal and pelagic habitats and with a generalist feeding behavior. Yet, information on the trophic ecology of animals inhabiting pelagic environments is still scarce. Using carbon (δ 13 C: 13 C/ 12 C) and nitrogen (δ 15 N: 15 N/ 14 N) stable isotope ratios, we identified and quantified the main groups of prey assimilated by bottlenose dolphins inhabiting an oceanic habitat (Madeira Island, East Atlantic). Bottlenose dolphins assimilated pelagic, schooling fish (such as blue jack mackerel, Trachurus picturatus ) and mesopelagic and demersal squids, which reinforces the pelagic dietary composition of insular/oceanic dolphins. Also, intra-seasonal differences were found in their stable isotope ratios, which suggest intraspecific variability in the feeding behavior among individuals living in the same area. Sex was not the main factor contributing to these differences, suggesting the lack of trophic niche segregation between adult males and females in this offshore environment. Nonetheless, further studies including different life stages and information on the ecophysiological requirements are necessary to disclose the factors responsible for the observed variability. This study showed that insular dolphins fed primarily on economically important pelagic prey, highlighting the need of developing management strategies that integrate conservation in fisheries plans.

Ontogenetic change in the venom composition of one Mexican black-tailed rattlesnake (Crotalus molossus nigrescens) from Durango, Mexico - Miguel Borja; Edgar Neri-Castro; Arelí Gutiérrez-Martínez; Richard Bledsoe; Vanessa Zarzosa; Bruno Rodriguez-López; Jason L. Strickland; Jorge Becerra-López; Sara Valenzuela-Ceballos; Christopher L. Parkinson; Alejandro Alagón; Gamaliel Castañeda-Gaytán (Toxicon, 2023)

Biosimilars approvals by thirteen regulatory authorities: A cross-national comparison - Fernanda Lacerda da Silva Machado; Martín Cañás; Svetlana V. Doubova; Martín A. Urtasun; Gustavo H. Marín; Claudia Garcia Serpa Osorio-de-Castro; Flavia Caixeta Albuquerque; Tatiane Bonfim Ribeiro; Lisa Pont; José Crisóstomo Landeros; Juan Roldán Saelzer; Dino Sepúlveda Viveros; et al. (Regulatory Toxicology and Pharmacology, 2023)

Multi-analytical characterization of an oncoid from a high altitude hypersaline lake using techniques employed in the Mars2020 and Rosalind Franklin missions on Mars - J. Huidobro; J.M. Madariaga; D. Carrizo; J.L. Laserna; F. Rull; J. Martínez-Frías; J. Aramendia; L. Sánchez-García; L. García-Gómez; F.A. Vignale; M.E. Farías; M. Veneranda; et al. (Analytica Chimica Acta, 2023)

Experimental nest cooling reveals dramatic effects of heatwaves on reproduction in a Mediterranean bird of prey - Alejandro Corregidor‐Castro; Jennifer Morinay; Susan E. McKinlay; Samuele Ramellini; Giacomo Assandri; Gaia Bazzi; Alexandra Glavaschi; Enrico L. De Capua; Alessandro Grapputo; Andrea Romano; Michelangelo Morganti; Jacopo G. Cecere; et al. (Global Change Biology, 2023)
Future climatic scenarios forecast increases in average temperatures as well as in the frequency, duration, and intensity of extreme events, such as heatwaves. Whereas behavioral adjustments can buffer direct physiological and fitness costs of exposure to excessive temperature in wild animals, these may prove more difficult during specific life stages when vagility is reduced (e.g., early developmental stages). By means of a nest cooling experiment, we tested the effects of extreme temperatures on different stages of reproduction in a cavity‐nesting Mediterranean bird of prey, the lesser kestrel ( Falco naumanni ), facing a recent increase in the frequency of heatwaves during its breeding season. Nest temperature in a group of nest boxes placed on roof terraces was reduced by shading them from direct sunlight in 2 consecutive years (2021 and 2022). We then compared hatching failure, mortality, and nestling morphology between shaded and non‐shaded (control) nest boxes. Nest temperature in control nest boxes was on average 3.9°C higher than in shaded ones during heatwaves, that is, spells of extreme air temperature (>37°C for ≥2 consecutive days) which hit the study area during the nestling‐rearing phase in both years. Hatching failure markedly increased with increasing nest temperature, rising above 50% when maximum nest temperatures exceeded 44°C. Nestlings from control nest boxes showed higher mortality during heatwaves (55% vs. 10% in shaded nest boxes) and those that survived further showed impaired morphological growth (body mass and skeletal size). Hence, heatwaves occurring during the breeding period can have both strong lethal and sublethal impacts on different components of avian reproduction, from egg hatching to nestling growth. More broadly, these findings suggest that the projected future increases of summer temperatures and heatwave frequency in the Mediterranean basin and elsewhere in temperate areas may threaten the local persistence of even relatively warm‐adapted species.

P19-01: Prenatal exposure to mixtures of potentially toxic and essential metals decreased DNA repair capacity in newborns from a polluted area - M. Paz-Sabillón; N. Montes-Castro; L.M. Del Razo; L. Torres-Sánchez; B. Quintanilla-Vega (Toxicology Letters, 2023)

An Inter-professional Plant-based Culinary Medicine Program for Nutrition and Medical Students - L. Castro; S. Joshi; M. McMacken; K. Woolf (Journal of the Academy of Nutrition and Dietetics, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Environmental approach for the design of raw milk collection routes with a heterogeneous fleet - Luis Francisco López-Castro; Elyn L. Solano-Charris; Adela Pagès-Bernaus (Computers and Electronics in Agriculture, 2023)

Environmental contours based on imprecise probability distributions - Rubisel Pérez-Castro; Francisco L. Silva-González (Ocean Engineering, 2023)

Development of a NASA roadmap for planetary protection to prepare for the first human missions to Mars - Bette Siegel; J.Andy Spry; James Broyan; Sarah L. Castro-Wallace; Kevin Sato; Erin Mahoney; Julie Robinson (Life Sciences in Space Research, 2023)

Impact of Primary Container Closure System on PS80 Oxidation and the Mechanistic Understanding - Ryan Mould; Peter William Sargent; Yining Huang; Allison L. Fields; Lin Zhang; Fabian Castro Herbert; Stephanie Lynn Stewart; Tingting Wang (Pharmaceutical Research, 2023)

Decay of Skin-Specific Gene Modules in Pangolins - Bernardo Pinto; Raul Valente; Filipe Caramelo; Raquel Ruivo; L. Filipe C. Castro (Journal of Molecular Evolution, 2023)
The mammalian skin exhibits a rich spectrum of evolutionary adaptations. The pilosebaceous unit, composed of the hair shaft, follicle, and the sebaceous gland, is the most striking synapomorphy. The evolutionary diversification of mammals across different ecological niches was paralleled by the appearance of an ample variety of skin modifications. Pangolins, order Pholidota, exhibit keratin-derived scales, one of the most iconic skin appendages. This formidable armor is intended to serve as a deterrent against predators. Surprisingly, while pangolins have hair on their abdomens, the occurrence of sebaceous and sweat glands is contentious. Here, we explore various molecular modules of skin physiology in four pangolin genomes, including that of sebum production. We show that genes driving wax monoester formation, Awat1/2 , show patterns of inactivation in the stem pangolin branch, while the triacylglycerol synthesis gene Dgat2l6 seems independently eroded in the African and Asian clades. In contrast, Elovl3 implicated in the formation of specific neutral lipids required for skin barrier function is intact and expressed in the pangolin skin. An extended comparative analysis shows that genes involved in skin pathogen defense and structural integrity of keratinocyte layers also show inactivating mutations: associated with both ancestral and independent pseudogenization events. Finally, we deduce that the suggested absence of sweat glands is not paralleled by the inactivation of the ATP-binding cassette transporter Abcc11 , as previously described in Cetacea. Our findings reveal the sophisticated and complex history of gene retention and loss as key mechanisms in the evolution of the highly modified mammalian skin phenotypes.

Testing differences of marine non-indigenous species diversity across Macaronesia using a standardised approach - Nuno Castro; Ignacio Gestoso; Patrício Ramalhosa; Evandro Lopes; Corrine Almeida; Ana Costa; Manuela Parente; Eva Cacabelos; Rogélio Herrera; José L. Costa; João Canning-Clode (Marine Pollution Bulletin, 2023)

Machine learning performance comparison for main propulsive shafting systems alignment - Diego L. Magalhães; Dionísio Henrique C. de S.S. Martins; Brenno M. Castro; Luiz A. Vaz; Ulisses A. Monteiro; Ricardo H.R. Gutiérrez (Ocean Engineering, 2023)

Review of tectonic inversion of sedimentary basins in NE and N Brazil: Analysis of mechanisms, timing and effects on structures and relief - Francisco H. Bezerra; Fernando O. Marques; David L. Vasconcelos; Dilce F. Rossetti; Aline C. Tavares; Rubson P. Maia; David L. de Castro; Francisco C.C. Nogueira; Reinhardt A. Fuck; Walter E. Medeiros (Journal of South American Earth Sciences, 2023)

Epigenetic regulation of collagen in the mare's placenta: putative relationship with maternal age - Manuel A. Vasconcelos; Yat Wong; Joana Alpoim-Moreira; Maria R. Rebordão; Maria J. Fradinho; Ana L. Costa; Miguel Bliebernicht; Fidel O. Castro; Elisabete Silva; Graça M. Ferreira-Dias (Journal of Equine Veterinary Science, 2023)

Efficacy of progressive versus severe energy restriction on body composition and strength in concurrent trained women - Salvador Vargas-Molina; Diego A. Bonilla; Jorge L. Petro; Leandro Carbone; Manuel García-Sillero; José Manuel Jurado-Castro; Brad J. Schoenfeld; Javier Benítez-Porres (European Journal of Applied Physiology, 2023)
Purpose This study evaluated the concurrent training (CT) effect in combination with either progressive energy restriction (PER) or severe energy restriction (SER) on body composition and strength-related variables in resistance-trained women. Methods Fourteen women (29.5 ± 3.8 years; 23.8 ± 2.8 kg·m −2 ) were randomly assigned to a PER ( n = 7) or SER ( n = 7) group. Participants performed an 8-week CT program. Pre- and post-intervention measures of fat mass (FM) and fat-free mass (FFM) were assessed by dual-energy X-ray absorptiometry and strength-related variables were assessed through 1-repetition maximum (in the squat and bench press) and countermovement jump. Results Significant reductions in FM were observed in PER and SER (Δ = − 1.7 ± 0.4 kg; P = < 0.001; ES = − 0.39 and Δ = − 1.2 ± 0.6 kg; P = 0.002; ES = − 0.20, respectively). After correcting FFM for fat-free adipose tissue (FFAT), no significant differences for this variable were found either in PER (Δ = − 0.3 ± 0.1; P = 0.071; ES = − 0.06) or in SER (Δ = − 0.2 ± 0.1; P = 0.578; ES = − 0.04). There were no significant changes in the strength-related variables. No between-group differences were found in any of the variables. Conclusion A PER has similar effects to a SER on body composition and strength in resistance-trained women performing a CT program. Given that PER is more flexible and thus may enhance dietary adherence, it might be a better alternative for FM reduction compared to SER.

A sequential recovery extraction and biological activity of water-soluble sulfated polysaccharides from the polar red macroalgae Sarcopeltis skottsbergii - Pablo Castro-Varela; Mónica Rubilar; Bruna Rodrigues; María Jesús Pacheco; Candela T. Caneda-Santiago; Manuel Marí-Beffa; Félix L. Figueroa; Roberto Abdala-Díaz (Algal Research, 2023)

Quantification of Wood Biomass in an Area of Sustainable Annual Production in the Brazilian Semiarid Region Aiming at Generating Renewable Energy - R. C. Santos; F. G. C. Pareyn; C. P. S. Santos; D. Minini; S. M. G. Rocha; F. J. O. Souza; L. F. C. Cezario; A. F. Dias Júnior; R. V. O. Castro (BioEnergy Research, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Diet rather than temperature determines the biochemical composition of the ragworm Hediste diversicolor (OF Müller, 1776) (Annelida: Nereidae) - Arne M. Malzahn; Andrea Villena-Rodríguez; Óscar Monroig; Åsmund Johansen; L. Filipe C. Castro; Juan C. Navarro; Andreas Hagemann (Aquaculture, 2023)

How diverse a genus can be: An integrated multi-layered analysis into Desmonostoc (Nostocaceae, Cyanobacteriota) - Allan Victor M. Almeida; Marcelo Gomes Marçal Vieira Vaz; Naira Valle de Castro; Diego Bonaldo Genuário; Jean Coutinho Oder; Pedro Augusto Marazzo de Souza; Sandy Bastos Martins; Mariana Machado; Adriano Nunes-Nesi; Wagner L. Araújo (Systematic and Applied Microbiology, 2023)

Genomic evidences of gulls as reservoirs of critical priority CTX-M-producing Escherichia coli in Corcovado Gulf, Patagonia - Danny Fuentes-Castillo; Daniela Castro-Tardón; Fernanda Esposito; Ingrith Neves; Larissa Rodrigues; Herrison Fontana; Bruna Fuga; José L. Catão-Dias; Nilton Lincopan (Science of The Total Environment, 2023)

Spring plankton energy content by size classes in two contrasting environments of a high latitude ecosystem: The Beagle Channel - Daniel O. Bruno; Constanza Valencia-Carrasco; María A. Paci; Ezequiel Leonarduzzi; Leonardo Castro; Luciana Riccialdelli; Clara M. Iachetti; Andreana Cadaillon; Ricardo Giesecke; Irene R. Schloss; Carla F. Berghoff; Jacobo Martín; et al. (Journal of Marine Systems, 2023)

Bacillus subtilis KM0 Impacts gut Microbiota Profile and Transcription of Genes Related to Transcellular Transport in Zebrafish (Danio rerio) - Caroline G. Castro; Marcela G. Meirelles; Raíza Azevedo; Jeferson V. Ramos; Tony L. R. da Silveira; Bruna F. Nornberg; Luis F. Marins (Current Microbiology, 2023)

The effect of nitrogen limitation on carbohydrates and β-glucan accumulation in Nannochloropsis oculata - M.E. Morales-Plasencia; L. Ibarra-Castro; J.M. Martínez-Brown; M. Nieves-Soto; J.F. Bermúdez-Lizárraga; A.H. Rojo-Cebreros (Algal Research, 2023)

Sulfolipid substitution ratios of Microcystis aeruginosa and planktonic communities as an indicator of phosphorus limitation in Lake Erie - Robbie M. Martin; Maddie K. Denney; Helena L. Pound; Justin D. Chaffin; George S. Bullerjahn; R. Michael L. McKay; Arthur Zastepa; Katarina A. Jones; Hector F. Castro; Shawn R. Campagna; Steven W. Wilhelm (Limnology and Oceanography, 2023)
Phosphorus (P) availability frequently limits primary production in lakes, influences the physiology of phytoplankton, shapes community structure, and can stimulate or constrain the formation of cyanobacterial blooms. Given the importance of P, numerous methods are available to assess P stress in phytoplankton communities. Marine phytoplankton are known to substitute sulfolipids for phospholipids in response to P limitation. We asked whether sulfolipid substitution might serve as an additional indicator of P stress in freshwater phytoplankton communities. The question was addressed using cultures of Microcystis aeruginosa , Lake Erie microcosms, and surveys of lipid profiles in Lake Erie during a Microcystis spp. bloom. Peak area response ratios of the intact polar lipids sulfoquinovosyldiacylglycerol (SQDG) to phosphatidylglycerol (PG) were used as the metric of lipid substitution. In cultures of M. aeruginosa NIES‐843, the SQDG : PG ratio increased from ~ 0.9 to ~ 3.3 with decreasing P concentration. In P‐limited communities, the SQDG : PG ratio increased from ~ 6 to ~ 11 after 48 h in microcosm controls, while P amendments reduced the ratio to ~ 3. In Lake Erie surveys, the SQDG : PG ratio ranged from ~ 0.4 to ~ 7.4 and was negatively correlated (Pearson r = −0.62) with total dissolved P. The SQDG : PG ratio was not correlated with concentrations of chlorophyll a , soluble reactive P, or N : P molar ratios. These results demonstrated that M. aeruginosa and Microcystis ‐dominated communities remodel lipid profiles in response to P scarcity, providing a potential short‐term, time‐integrated biomarker of nutrient history and P stress in fresh waters.

Metabolic profiling by LC-DAD-MS, FTIR, NMR and CE-UV of polyphenols with potential against skin pigmentation disorder - Isac H. Cordeiro; Nerilson M. Lima; Elaine C. Scherrer; Gabriela P. Carli; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Marcone A. L. de Oliveira; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2023)

Bioremediation of coastal aquaculture effluents spiked with florfenicol using microalgae-based granular sludge – a promising solution for recirculating aquaculture systems - Ana S. Oliveira; Marta Alves; Frederico Leitão; Marta Tacão; Isabel Henriques; Paula M.L. Castro; Catarina L. Amorim (Water Research, 2023)

First Confirmed Record of the Smalltooth Sand Tiger, Odontapis Ferox, in Galicia (NW Spain) - Gonzalo Mucientes; Nair Vilas-Arrondo; Giulia Secci-Petretto; Uxía Vázquez; Xabier Pin; Alfredo López; L. Filipe C. Castro; Elsa Froufe (Thalassas: An International Journal of Marine Sciences, 2023)
The smalltooth sand tiger shark Odontaspis ferox (Risso, 1810) appears to have an extensive and fragmented distribution in tropical and warm-temperate worldwide oceans. One female of O. ferox was caught and released by a small-scale fishery vessel in Ría de Arousa (Northwest of Spain), subsequently stranded still alive on the coast (42°33’18.4"N 8°49’18.3"O) after a few hours. The individual (336 cm total length, weight ~ 300 kg) was identified based on a collection of features including the characteristic dentition, body morphology and by molecular assignment. This is the first confirmed record of O. ferox in Galician waters. This finding complements the knowledge of the geographic distribution and occurrence of this rare and sparse species in the Northeastern Atlantic.

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Acaricidal action of ozone on larvae and engorged females of Rhipicephalus microplus: a dose-dependent relationship - R. A. Castro; O. P. Neto; A. L. S. Mendes; L. H. Moreira (Experimental and Applied Acarology, 2023)

Combined coagulation-electrocoagulation process using biocoagulant from the Opuntia ficus-indica for treatment of cheese whey wastewater - Hugo G. J. Pacheco; Naysha Y. Elguera; Midwar Ancco; Antonio E. L. F. Castro; Maria E. B. Meza; Vitor C. Almeida (Environmental Monitoring and Assessment, 2023)

Evaluation of lead exposition length on the liver and intestinal histoarchitecture of eared dove (Zenaida auriculata) - Verónica P. Filippa; Emilce L. Tabares; Ana C. Castro-Guijarro; Juan G. Chediack; Fabricio D. Cid (Environmental Science and Pollution Research, 2023)

Characterization of proteases in the seminal plasma and spermatozoa of llama - L. Sari; X. Castro-González; R. Zampini; S. Apichela; M. Ratto; M. Argañaraz (Theriogenology, 2023)

Changing risk of arboviral emergence in Catalonia due to higher probability of autochthonous outbreaks - L. López; C. Dommar; A. San José; L. Meyers; S. Fox; L. Castro; X. Rodó (Ecological Modelling, 2023)

Karstified zone interpretation using deep learning algorithms: Convolutional neural networks applications and model interpretability with explainable AI - Marcos V.G. Jacinto; Adrião D. Doria Neto; David L. de Castro; Francisco H.R. Bezerra (Computers & Geosciences, 2023)

Population dynamics and movements of Atlantic tarpon, Megalops atlanticus, in the Parnaíba Delta Protected Area, Brazil: challenges for local fishery management planning - Cezar A. F. Fernandes; Francisca E. A. Cunha; Carlos E. L. S. Silva; Alan C. S. Araújo; Rafael L. Pereira; Daniel F. Viana; Werlanne M. S. Magalhães; M. A. P. Gondolo; Daniel M. P. de Castro; Aaron Adams; Jiangang Luo; Jerald S. Ault; et al. (Environmental Biology of Fishes, 2023)

Comparative study, homology modelling and molecular docking with cancer associated glycans of two non-fetuin-binding Tepary bean lectins - Iovanna Torres-Arteaga; Alejandro Blanco-Labra; Elizabeth Mendiola-Olaya; Teresa García-Gasca; Cesar Aguirre-Mancilla; Alondra L. Ortega-de-Santiago; Mariana Barboza; Carlito B. Lebrilla; José Luis Castro-Guillén (Glycoconjugate Journal, 2023)

Assessing the ability of satellite sea surface temperature analyses to resolve spatial variability – The northwest tropical Atlantic ATOMIC region - Gary A. Wick; Darren L. Jackson; Sandra L. Castro (Remote Sensing of Environment, 2023)

Chitosan-carbamoylcarboxylic acid grafted polymers for removal of metal ions in wastewater - Christian L. Castro-Riquelme; Eduardo A. López-Maldonado; Adrián Ochoa-Terán; Eleazar Alcántar-Zavala; Balter Trujillo-Navarrete; Sergio Pérez-Sicairos; Valentín Miranda-Soto; Arturo Zizumbo-López (Chemical Engineering Journal, 2023)

Breathing modulates gamma synchronization across species - Joaquín González; Matias Cavelli; Alejandra Mondino; Santiago Castro-Zaballa; Jurij Brankačk; Andreas Draguhn; Pablo Torterolo; Adriano B. L. Tort (Pflügers Archiv - European Journal of Physiology, 2023)

Mothers of children with Down syndrome: a clinical and epidemiological study - Joissy Aprigio; Carolina M. L. de Castro; Marcelo A. Costa Lima; Márcia G. Ribeiro; Iêda M. Orioli; Márcia R. Amorim (Journal of Community Genetics, 2022)

Anatomical traits in pine stems, the first step to define grafting combinations? - Sandra L. Castro-Garibay; Teresa Terrazas; Javier López-Upton; Lourdes Arévalo-Galarza; Manuel Sandoval-Villa; Ángel Villegas-Monter (Brazilian Journal of Botany, 2022)

Identification of SNP Markers Associated to Protein and Oil Content in Doubled Haploid Maize Lines Derived from Subtropical Breeding Populations - Juan P. Valenzuela-Apodaca; Abraham Cruz-Mendívil; Grethel P. Gaytán-Pinzón; Hervey Rodríguez-González; Luis A. Peinado-Fuentes; Eduardo Sandoval-Castro; Carlos L. Calderón-Vázquez (Tropical Plant Biology, 2022)

Revision of TD1 and TD2 stratigraphic sequence of Gran Dolina cave (Sierra de Atapuerca, Spain) - I. Campaña; A. Benito-Calvo; A. Pérez-González; A. Álvaro-Gallo; L. Miguens-Rodríguez; J. Iglesias-Cibanal; J. M. Bermúdez de Castro; E. Carbonell (Journal of Iberian Geology, 2022)
Gran Dolina is a cavity infilled by at least 25 m of Pleistocene sediments divided into 12 lithostratigraphic units and 19 sedimentary facies. These sedimentary facies have been divided into allochthonous facies, defined as sediment inputs from the outside, and autochthonous facies, defined as sediments generated within the karst; but this division has been challenged in recent works. In this study, TD1 and TD2 units of Gran Dolina have been detailed studied and the use of autochthonous facies has been assessed. For that purpose, we have studied the stratigraphic excavation profile, combining field observation with laboratory sedimentary analysis (sieving, laser diffraction, and XRD) to characterize the texture and structure of the sediments. Based on these studies, a total of 8 sedimentary facies have been identified. Consequently, TD1 unit has been separated into two sub-units and 13 layers, while the TD2 unit has been divided into three sub-units. The facies associations indicate a succession of phreatic and vadose phases that would define together epiphreatic conditions inside the cave, related to the transition between Arlanzón valley terraces T3 and T4. Interior facies (and entrance facies for allochthonous facies) is proposed to define Gran Dolina's sediments since the facies analyses indicate transport by underground flows.

Gastrointestinal colonization by OXA-48-producing Enterobacterales: risk factors for persistent carriage - O. Lima; A. Sousa; A. Filgueira; M. Carmen González-Novoa; Celina Domínguez-López; M. Ávila-Nuñez; M. Represa; P. Rubiñán; L. Martínez-Lamas; Sonia Pérez-Castro; M. Rubianes; M. T. Pérez-Rodríguez (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Aridity drives the loss of dung beetle taxonomic and functional diversity in three contrasting deserts - Pablo Castro Sánchez‐Bermejo; Indradatta deCastro‐Arrazola; Eva Cuesta; Adrian L. V. Davis; Claudia E. Moreno; Francisco Sánchez‐Piñero; Joaquín Hortal (Journal of Biogeography, 2022)
Aim Aridity gradients are of great interest for understanding the responses of biodiversity to water availability and water stress. However, little is known about the responses of many animal groups, which are crucial for assessing the effects of climate change. Here, we study the effects of aridity on dung beetle communities, a group with well‐known responses to large‐scale environmental gradients. Location Sahara, Kalahari and Chihuahuan deserts. Taxa Dung beetles of the family Scarabaeidae. Methods We conducted standardized surveys along approximately 400 km aridity gradients in each of the three deserts, and measured species richness, abundance, evenness and three aspects of trait‐based functional diversity (functional richness, functional evenness and functional dispersion). By using randomization tests and linear mixed models, we compared observed with expected values for functional diversity indices from null models that hierarchically incorporate additional assembly constraints. Results Overall, we found a decrease of both taxonomic richness and functional dispersion along the three aridity gradients. Also, aridity seems to have mild effects on functional richness and functional evenness. Besides these general trends, we identified differences between deserts in the responses of both taxonomic and functional diversity. Main conclusions Aridity shows greater importance than competition and other processes of limiting similarity or stochastic processes in community assembly. Also, the functional hypervolume of dung beetle desert communities decreases with aridity not only due to species loss, but also because of selection of a few distinct phenotypes under harsh environmental conditions. Last, we observed that the different regional pools respond to aridity in different ways. Therefore, understanding future responses of dung beetle communities to the progressive decreases in water availability driven by climate change requires determining how the characteristics of the species in the regional pool interact with aridity‐driven assembly processes.

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Growth, biofiltration and photosynthetic performance of Ulva spp. cultivated in fishpond effluents: An outdoor study - Thaís Fávero Massocato; Víctor Robles-Carnero; Bruna Rodrigues Moreira; Pablo Castro-Varela; Lorena Pinheiro-Silva; Willian da Silva Oliveira; Julia Vega; Antonio Avilés; José Bonomi-Barufi; Leonardo Rubi Rörig; Félix L. Figueroa (Frontiers in Marine Science, 2022)
Anthropogenic impacts on water resources, especially by ​​nutrient discharge, is a worldwide problem in marine coastal areas. In this context, seaweed cultivation in aquaculture wastewater can be considered as an alternative for effluent mitigation, where the biomass becomes a source of valuable compounds. The current study examined the potential use of the seaweeds Ulva pseudorotundata and Ulva rigida to remove nutrients to treat effluents from the culture of Chelon labrosus . Two experiments were conducted under pilot-scale conditions to evaluate the nutrient uptake, photosynthetic activity, and biomass production of the seaweed species cultivated under 50 and 100% effluent concentrations. Photosynthetic parameters were determined by in vivo chlorophyll a fluorescence associated to photosystem II 3 times a day to estimate photosynthetic performance and seaweed physiology throughout the experiment: optimal quantum yield ( F v /F m ), in situ and ex situ electron transport rate (ETR), photosynthetic efficiency (α ETR ), saturation irradiance ( E k ), and the maximum non-photochemical quenching (NPQ max ). To evaluate seaweed metabolism and biomass compounds, elemental and biochemical composition were analyzed in the beginning and end of each experiment. Results regarding the nutrient source showed that both species removed more than 65% of ammonium after 3 hours of experimentation. At the end of the experiments, up to 94.8% of the initial ammonium was sequestered from the effluent. Additionally, after 5 days of cultivation under 50% fish effluent both Ulva species were able to remove more than 85% of the nitrate. Although a decrease in uptake efficiency was observed in cultures with 100% fish effluent, at the end of the experiment more than 440 µmol L -1 of nitrate was removed, considering all treatment conditions. The biomass values showed that growth rates of seaweed cultivated in 100% effluent were higher than those obtained in 50% effluent. Moreover, when cultivated in the 100% effluent concentration, a significant increment in protein content was detected in both Ulva species. Our results contribute to the understanding of biofiltration and photosynthetic performance of two different Ulva species in order to improve growth optimization, enhancement of biofiltration capacity and also to boost management practices of seaweed cultivation in aquaculture effluent treatment systems.

Performance of Sentinel-2 SAFER ET model for daily and seasonal estimation of grapevine water consumption - Anderson L. S. Safre; Ayman Nassar; Alfonso Torres-Rua; Mayhar Aboutalebi; João C. C. Saad; Rodrigo L. Manzione; Antonio Heriberto de Castro Teixeira; John H. Prueger; Lynn G. McKee; Joseph G. Alfieri; Lawrence E. Hipps; Hector Nieto; et al. (Irrigation Science, 2022)

Inter-annual variability of land surface fluxes across vineyards: the role of climate, phenology, and irrigation management - N. Bambach; W. Kustas; J. Alfieri; F. Gao; J. Prueger; L. Hipps; L. McKee; S. J. Castro; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Irrigation and other agricultural management practices play a key role in land surface fluxes and their interactions with atmospheric processes. California’s Central Valley agricultural productivity is strongly linked to water availability associated with conveyance infrastructure and groundwater, but greater scrutiny over agricultural water use requires better practices particularly during extended and severe drought conditions. The future of irrigated agriculture in California is expected to be characterized neither by perpetual scarcity nor by widespread abundance. Thus, further advancing irrigation technologies and improving management practices will be key for California’s agriculture sustainability. In this study, we present micrometeorological observations from the Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project. Daily, seasonal, and inter-seasonal surface flux patterns and relationships across five vineyards over three distinct California wine production regions were investigated. Vineyard actual evapotranspiration showed significant differences at the sub-daily and daily scale when comparisons across wine production regions and varieties were performed. Water use in vineyards in the Central Valley was about 70% greater in comparison to the vineyards at the North Coast area due to canopy size, atmospheric demand, and irrigation inputs. Inter-annual variability of surface fluxes was also significant, even though, overall weather conditions (i.e., air temperature, vapor pressure deficit, wind speed, and solar radiation) were not significantly different. Thus, not only irrigation but also other management practices played a key role in seasonal water use, and given these differences, we conclude that further advancing ground-based techniques to quantify crop water use at an operational scale will be key to facing California’s agriculture present and future water challenges.

Evapotranspiration uncertainty at micrometeorological scales: the impact of the eddy covariance energy imbalance and correction methods - N. Bambach; W. Kustas; J. Alfieri; J. Prueger; L. Hipps; L. McKee; S. J. Castro; J. Volk; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Under ideal conditions, evapotranspiration ( ET ) fluxes derived through the eddy covariance (EC) technique are considered a direct measure of actual ET . Eddy covariance flux measurements provide estimates at a temporal frequency that allows examining sub-daily, daily, and seasonal scale processes and relationships between different surface fluxes. The Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project has collected micrometeorological and biophysical data to ground-truth new remote sensing tools for fine-tuning vineyard irrigation management across numerous sites since 2013. This rich dataset allows us to quantify the impact of different approaches to estimate daily ET fluxes, while accounting for energy imbalance. This imbalance results from the lack of agreement between the total available energy and turbulent fluxes derived by the EC technique. We found that different approaches to deal with this energy imbalance can lead to uncertainty in daily ET estimates of up to 50%. Over the growing season, this uncertainty can lead to considerable biases in crop water use estimates, which in some cases were equivalent to ~ 1/3rd of the total growing season applied irrigation We analyzed ET uncertainty relative to atmospheric meteorological, stability, and advective conditions, and highlight the importance of recognizing limitations of micrometeorological observational techniques, considered state of the art, to quantify ET for model validation and field-scale monitoring. This study provides a framework to quantify daily ET estimates’ uncertainty and expected reliability when using the eddy covariance technique for ground-truthing or model validation purposes.

Common dolphin (Delphinus delphis) fission–fusion dynamics in the south coast of Portugal - Joana Castro; Cláudia Faustino; André Cid; Alicia Quirin; Fábio L. Matos; Rui Rosa; Heidi C. Pearson (Behavioral Ecology and Sociobiology, 2022)

Morita–Baylis–Hillman adducts derived from thymol: synthesis, in silico studies and biological activity against Giardia lamblia - Francisco J. S. Xavier; Andressa B. Lira; Gabriel C. Verissimo; Fernanda S. de S. Saraiva; Abrahão A. de Oliveira Filho; Elaine M. de Souza-Fagundes; Margareth de F. F. M. Diniz; Maria A. Gomes; Aleff C. Castro; Fábio P. L. Silva; Claudio G. Lima-Junior; Mário L. A. A. Vasconcellos (Molecular Diversity, 2022)

Physicochemical and computational analysis of the melamine resin derivative for the glyphosate absorption from water using Langmuir-type model - L. Morales-Quintana; D. Bustos; J. Gallego; O. Valdes; L. Guzmán; F. M. Nachtigall; A. Marican; E. W. Hernández-Rodríguez; F. Avila-Salas; W. Bueno-Silva; L. S. Santos; R. I. Castro (International Journal of Environmental Science and Technology, 2022)

Correction to: Numerical Analysis of Infiltration in One‑Dimensional Unsaturated Soil–Geotextile Column - G. B. Castro; A. T. Siacara; A. Nardelli; L. Lenzi; M. M. Futai (Geotechnical and Geological Engineering, 2022)

Numerical Analysis of Infiltration in One-Dimensional Unsaturated Soil–Geotextile Column - G. B. Castro; A. T. Siacara; A. Nardelli; L. Lenzi; M. M. Futai (Geotechnical and Geological Engineering, 2022)

A zebrafish pparγ gene deletion reveals a protein kinase network associated with defective lipid metabolism - Yan Zhao; L. Filipe C. Castro; Óscar Monroig; Xiaojuan Cao; Yonghua Sun; Jian Gao (Functional & Integrative Genomics, 2022)

Enzymatic browning and genome-wide polyphenol oxidase gene identification in three contrasting avocado accessions - Jesús M. Higuera-Rubio; Enrique Ibarra-Laclette; Miguel A. Reyes-López; Eduardo Sandoval-Castro; Abraham Cruz-Mendívil; Misael O. Vega-García; Carlos L. Calderón-Vázquez (Plant Biotechnology Reports, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Plant growth-promoting and non-promoting rhizobacteria from avocado trees differentially emit volatiles that influence growth of Arabidopsis thaliana - Roberto Gamboa-Becerra; Damaris Desgarennes; Jorge Molina-Torres; Enrique Ramírez-Chávez; Ana L. Kiel-Martínez; Gloria Carrión; Randy Ortiz-Castro (Protoplasma, 2022)

Highly Efficient Water-Based Extraction of Biliprotein R-Phycoerythrin From Marine the Red-Macroalga Sarcopeltis skottsbergii by Ultrasound and High-Pressure Homogenization Methods - Pablo Castro-Varela; Paula S.M. Celis-Pla; Felix L. Figueroa; Monica Rubilar (Frontiers in Marine Science, 2022)
Sarcopeltis skottsbergii is an endemic species of the southern region of South America, with R-phycoerythrin (R-PE) as an accessory photosynthetic pigment. The production of S. skottsbergii is around twenty thousand tons of dry alga per year. The evaluation of (R-PE) in a biorefinery model is still incipient in the algal biotechnology area and will be used in the food, pharmaceutical, cosmeceutical, and nutraceutical industries. This work evaluated the cell disruption and separation processes by using two green technologies, ultrasound-assisted extraction (UAE) and high-pressure homogenization (HPH), to obtain an R-phycoerythrin enriched extract from S. skottsbergii . Two-levels three-factor central composite design (CCD) and response surface methodology (RSM) were carried out to optimize the extraction conditions, including the factors for UAE (time, amplitude, and solvent) and HPH (Pressure, number of passes, and solvent). Additionally, a second-order polynomial fit was performed to fit the experimental data by the green method. HPH method was the most efficient extraction method under the conditions obtained of 100-400 MPa pressure power, 2-3 number of passes, and distilled water as solvent. Furthermore, the experimental extraction yields ranged from 4.4-5.7 mg of PE g -1 of dry biomass under the optimal extraction conditions (400 MPa; 2 passes), which agreed with the predictive yield of 4.6-5.5 mg g -1 DW. The ultrafiltration membrane used for the separation process for both methods exhibited a rejection of R-phycoerythrin concentrated at 30 KDa. Furthermore, R-phycoerythrin showed a positive correlation between the antioxidant capacity (ORAC) in the best-selected extractions. After the extraction, the same pattern was observed in Chlorophyll a and total carotenoids with DPPH. Thus, it was an attractive non-aggressive extraction alternative with biological activity of interest for formulating biotechnological products for the food industry is suggested.

Setting Performance Indicators for Coastal Marine Protected Areas: An Expert-Based Methodology - Mariana Cardoso-Andrade; Henrique Queiroga; Mafalda Rangel; Inês Sousa; Adela Belackova; Luís Bentes; Frederico Oliveira; Pedro Monteiro; Nuno Sales Henriques; Carlos M. L. Afonso; Ana F. Silva; Bernardo R. Quintella; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) require effective indicators to assess their performance, in compliance with the goals of relevant national and international commitments. Achieving and prioritizing shortlists of multidisciplinary indicators demands a significant effort from specialists to depict the multiple conservation and socioeconomic interests, and the large complexity of natural systems. The present paper describes a structured expert-based methodology (process and outputs) to co-define a list of multidisciplinary MPA performance indicators. This work was promoted by the management authority of coastal MPAs in mainland Portugal to gather a consensual and feasible list of indicators that would guide the design of a future national monitoring program. Hence, Portuguese coastal MPAs served as a case study to develop such a process between 2019 and 2020. In the end, participants (1) agreed on a shortlist of prioritized indicators ( i.e. , environmental, governance, and socioeconomic indicators) and (2) defined minimum monitoring frequencies for the indicators in this list, compatible with the potential replicability of the associated survey methods. The present approach recommends that management plans incorporate monitoring procedures and survey methods, with a validated list of indicators and associated monitoring periodicity, agreed among researchers, MPA managers and governance experts. The proposed methodology, and the lessons learned from it, can support future processes aiming to define and prioritize MPA performance indicators.

Actinobacteria isolated from wastewater treatment plants located in the east-north of Algeria able to degrade pesticides - Oumeima Boufercha; Irina S. Moreira; Paula M. L. Castro; Allaoueddine Boudemagh (World Journal of Microbiology and Biotechnology, 2022)

Interrelationship between diseases and calving season and their impact on reproductive parameters and milk production of tropical dairy cows - Joaquín M. Castro-Montoya; F. L. González; M. V. Mendoza; K. Harper; E. E. Corea (Tropical Animal Health and Production, 2022)

Mapping Lioz Limestone in Monuments at Rio de Janeiro, Brazil - Amanda G. S. Mozer; Nuria F. Castro; Kátia L. Mansur; Roberto Carlos C. Ribeiro (Geoheritage, 2022)

Do telemetry harnesses affect giant anteater (Myrmecophaga tridactyla) behavior and welfare? - Alessandra Bertassoni; Daniela Caixeta-Oliveira; Juliana Macedo Magnino Silva; Victor Gonçalves de Castro; Guilherme Lopes do Amaral; Débora Regina Yogui; Danilo Kluyber; Arnaud L. J. Desbiez (European Journal of Wildlife Research, 2022)

Jasmonates promote enhanced production of bioactive caffeoylquinic acid derivative in Eclipta prostrata (L.) L. hairy roots - Geveraldo Maciel; Adriana Aparecida Lopes; Charles L. Cantrell; Suzelei de Castro França; Bianca Waleria Bertoni; Miriam Verginia Lourenço (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Do CMIP models capture long-term observed annual precipitation trends? - S. M. Vicente-Serrano; R. García-Herrera; D. Peña-Angulo; M. Tomas-Burguera; F. Domínguez-Castro; I. Noguera; N. Calvo; C. Murphy; R. Nieto; L. Gimeno; J. M. Gutierrez; C. Azorin-Molina; et al. (Climate Dynamics, 2022)
This study provides a long-term (1891–2014) global assessment of precipitation trends using data from two station-based gridded datasets and climate model outputs evolved through the fifth and sixth phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively). Our analysis employs a variety of modeling groups that incorporate low- and high-top level members, with the aim of assessing the possible effects of including a well-resolved stratosphere on the model’s ability to reproduce long-term observed annual precipitation trends. Results demonstrate that only a few regions show statistically significant differences in precipitation trends between observations and models. Nevertheless, this pattern is mostly caused by the strong interannual variability of precipitation in most of the world regions. Thus, statistically significant model-observation differences on trends (1891–2014) are found at the zonal mean scale. The different model groups clearly fail to reproduce the spatial patterns of annual precipitation trends and the regions where stronger increases or decreases are recorded. This study also stresses that there are no significant differences between low- and high-top models in capturing observed precipitation trends, indicating that having a well-resolved stratosphere has a low impact on the accuracy of precipitation projections.

Evidence of multiple paternity for the endemic Xingu River stingray - Yan Torres; Patricia Charvet; Vicente V. Faria; Andrey L. F. de Castro (Journal of Fish Biology, 2022)
Multiple paternity (MP) is a phenomenon observed for more than 30 elasmobranch species. The Batoidea is more specious than the Selachii, but only three studies of MP have been conducted on batoids. The occurrence of MP in freshwater stingrays was tested using microsatellite markers, which were developed for Potamotrygon leopoldi . Six mothers and their litters were genotyped, providing the first evidence of MP for Potamotrygonidae, with an MP frequency of 33%.

RI75, a curcumin analogue, inhibits tumor necrosis factor-α and interleukin-6 production and exhibits antiallodynic and antiedematogenic activities in mice - Sarah O. A. M. Costa; Ianny B. Rodrigues; Alysson V. Braga; Bárbara C. M. Barbosa; Roger R. L. Silva; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela Í. Morais; Brenda F. M. Castro; Armando S. Cunha Júnior; Vinícius G. Maltarollo; Renata B. Oliveira; et al. (Inflammopharmacology, 2022)

Sea Ice and Substratum Shape Extensive Kelp Forests in the Canadian Arctic - Karen Filbee-Dexter; Kathleen A. MacGregor; Camille Lavoie; Ignacio Garrido; Jesica Goldsmit; Laura Castro de la Guardia; Kimberly L. Howland; Ladd E. Johnson; Brenda Konar; Christopher W. McKindsey; Christopher J. Mundy; Robert W. Schlegel; et al. (Frontiers in Marine Science, 2022)
The coastal zone of the Canadian Arctic represents 10% of the world’s coastline and is one of the most rapidly changing marine regions on the planet. To predict the consequences of these environmental changes, a better understanding of how environmental gradients shape coastal habitat structure in this area is required. We quantified the abundance and diversity of canopy forming seaweeds throughout the nearshore zone (5–15 m) of the Eastern Canadian Arctic using diving surveys and benthic collections at 55 sites distributed over 3,000 km of coastline. Kelp forests were found throughout, covering on average 40.4% (±29.9 SD) of the seafloor across all sites and depths, despite thick sea ice and scarce hard substrata in some areas. Total standing macroalgal biomass ranged from 0 to 32 kg m –2 wet weight and averaged 3.7 kg m –2 (±0.6 SD) across all sites and depths. Kelps were less abundant at depths of 5 m compared to 10 or 15 m and distinct regional assemblages were related to sea ice cover, substratum type, and nutrient availability. The most common community configuration was a mixed assemblage of four species: Agarum clathratum (14.9% benthic cover ± 12.0 SD), Saccharina latissima (13% ± 14.7 SD), Alaria esculenta (5.4% ± 1.2 SD), and Laminaria solidungula (3.7% ± 4.9 SD). A. clathratum dominated northernmost regions and S. latissima and L. solidungula occurred at high abundance in regions with more open water days. In southeastern areas along the coast of northern Labrador, the coastal zone was mainly sea urchin barrens, with little vegetation. We found positive relationships between open water days (days without sea ice) and kelp biomass and seaweed diversity, suggesting kelp biomass could increase, and the species composition of kelp forests could shift, as sea ice diminishes in some areas of the Eastern Canadian Arctic. Our findings demonstrate the high potential productivity of this extensive coastal zone and highlight the need to better understand the ecology of this system and the services it provides.

Correction to: Valorization of wastewater from food industry: moving to a circular bioeconomy - Carolina F. F. A. Costa; Catarina L. Amorim; Anouk F. Duque; Maria A. M. Reis; Paula M. L. Castro (Reviews in Environmental Science and Bio/Technology, 2022)

Valorization of wastewater from food industry: moving to a circular bioeconomy - Carolina F. F. A. Costa; Catarina L. Amorim; Anouk F. Duque; Maria A. M. Reis; Paula M. L. Castro (Reviews in Environmental Science and Bio/Technology, 2022)

Impact of Dietary Condensed Tannins and Haemonchus contortus Infection in Growing Sheep: Effects on Nutrient Intake, Digestibility, and the Retention of Energy and Nitrogen - F. A. Méndez-Ortiz; C. A. Sandoval-Castro; L. A. Sarmiento-Franco; J. Ventura-Cordero; P. G. González-Pech; J. J. Vargas-Magaña; J. F. J. Torres-Acosta (Acta Parasitologica, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

Efficacy of high-intensity interval- or continuous aerobic-training on insulin resistance and muscle function in adults with metabolic syndrome: a clinical trial - Jaime Gallo-Villegas; Leonardo A. Castro-Valencia; Laura Pérez; Daniel Restrepo; Oscar Guerrero; Sergio Cardona; Yeliana L. Sánchez; Manuela Yepes-Calderón; Luis H. Valbuena; Miguel Peña; Andrés F. Milán; Maria C. Trillos-Almanza; et al. (European Journal of Applied Physiology, 2022)

A new species of Hoplias malabaricus species complex ( Characiformes: Erythrinidae ) from the Crepori River , Amazon basin, Brazil - Karen L. A. Guimarães; Juan J. Rosso; Mariano González‐Castro; Mendelsohn F. B. Souza; Juan M. Díaz de Astarloa; Luís R. R. Rodrigues (Journal of Fish Biology, 2022)
A new species belonging to the Hoplias malabaricus complex from the Amazon basin, Brazil, is described. The new species is characterized by 15–16 predorsal scales, 37–39 lateral‐line scales, 5 scales from dorsal fin to lateral line, 38–39 vertebrae, iii‐iv, 7–8 anal‐fin rays, ii‐iv, 12–15 caudal‐fin rays, last vertical series of scales on the base of caudal‐fin rays forming a straight line, 6–7 dark bands in anal fin and no distinctive dark bands or blotches on flanks. The new species is also distinguished from other congeners of the H. malabaricus species‐group by means of landmark‐based morphometrics and DNA Barcoding ( Cytochrome c Oxidase I gene ). An identification key to species of the H. malabaricus species complex is provided.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Resistance exercise intervention on muscular strength and power, and functional capacity in acute hospitalized older adults: a systematic review and meta-analysis of 2498 patients in 7 randomized clinical trials - Marcelo A. S. Carneiro; Cristiane M. C. Franco; Alan L. Silva; Pâmela Castro-e-Souza; Gabriel Kunevaliki; Mikel Izquierdo; Edilson S. Cyrino; Camila S. Padilha (GeroScience, 2021)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

In vitro and in vivo evaluation of anti-inflammatory activity and free radical scavenging potential of leaves extract from Anadenanthera colubrina - Oswaldo Cardoso Junior; Nerilson M. Lima; Marcos G. A. Silva; Virgilio B. Aguiar; Gabriela P. Carli; Elaine C. Scherrer; Sandra B. R. Castro; Caio C. Souza Alves; Marcone A. L. Oliveira; Alessandra P. Carli (Natural Product Research, 2021)

A network-based approach to identify protein kinases critical for regulating srebf1 in lipid deposition causing obesity - Shouxiang Sun; Xiaojuan Cao; L. Filipe C. Castro; Óscar Monroig; Jian Gao (Functional & Integrative Genomics, 2021)

First Assessment of the Impacts of the COVID-19 Pandemic on Global Marine Recreational Fisheries - Pablo Pita; Gillian B. Ainsworth; Bernardino Alba; Antônio B. Anderson; Manel Antelo; Josep Alós; Iñaki Artetxe; Jérôme Baudrier; José J. Castro; Belén Chicharro; Karim Erzini; Keno Ferter; et al. (Frontiers in Marine Science, 2021)
This work is the result of an international research effort to determine the main impacts of the COVID-19 pandemic on marine recreational fishing. Changes were assessed on (1) access to fishing, derived from lockdowns and other mobility restrictions; (2) ecosystems, because of alterations in fishing intensity and human presence; (3) the blue economy, derived from alterations in the investments and expenses of the fishers; and (4) society, in relation to variations in fishers’ health and well-being. For this, a consultation with experts from 16 countries was carried out, as well as an international online survey aimed at recreational fishers, that included specific questions designed to capture fishers’ heterogeneity in relation to behavior, skills and know-how, and vital involvement. Fishers’ participation in the online survey (5,998 recreational fishers in 15 countries) was promoted through a marketing campaign. The sensitivity of the fishers’ clustering procedure, based on the captured heterogeneity, was evaluated by SIMPER analysis and by generalized linear models. Results from the expert consultation highlighted a worldwide reduction in marine recreational fishing activity. Lower human-driven pressures are expected to generate some benefits for marine ecosystems. However, experts also identified high negative impacts on the blue economy, as well as on fisher health and well-being because of the loss of recreational fishing opportunities. Most (98%) of the fishers who participated in the online survey were identified as advanced , showing a much higher degree of commitment to recreational fishing than basic fishers (2%). Advanced fishers were, in general, more pessimistic about the impacts of COVID-19, reporting higher reductions in physical activity and fish consumption, as well as poorer quality of night rest, foul mood, and raised more concerns about their health status. Controlled and safe access to marine recreational fisheries during pandemics would provide benefits to the health and well-being of people and reduce negative socioeconomic impacts, especially for vulnerable social groups.

Functional or Vestigial? The Genomics of the Pineal Gland in Xenarthra - Raul Valente; Filipe Alves; Isabel Sousa-Pinto; Raquel Ruivo; L. Filipe C. Castro (Journal of Molecular Evolution, 2021)

Exploring genetic diversity of lowland avocado (Persea americana Mill.) as a genetic reservoir for breeding - Eduardo Sandoval-Castro; Ayesha Y. Peraza-Magallanes; Richard S. Dodd; Vanessa E. T. M. Ashworth; Abraham Cruz-Mendívil; Carlos L. Calderón-Vázquez (Genetic Resources and Crop Evolution, 2021)

Sediments in the mangrove areas contribute to the removal of endocrine disrupting chemicals in coastal sediments of Macau SAR, China, and harbour microbial communities capable of degrading E2, EE2, BPA and BPS - Irina S. Moreira; Alexandre Lebel; Xianzhi Peng; Paula M. L. Castro; David Gonçalves (Biodegradation, 2021)

Global forest restoration opportunities to foster coral reef conservation - Andrés F. Suárez‐Castro; Hawthorne L. Beyer; Caitlin D. Kuempel; Simon Linke; Pasquale Borrelli; Ove Hoegh‐Guldberg (Global Change Biology, 2021)
Sediment runoff from disturbed coastal catchments is a major threat to marine ecosystems. Understanding where sediments are produced and where they are delivered enables managers to design more effective strategies for improving water quality. A management strategy is targeted restoration of degraded terrestrial areas, as it provides opportunities to reduce land‐based runoff from coastal areas and consequently foster coral reef conservation. To do this strategically, a systematic approach is needed to identify watersheds where restoration actions will provide the highest conservation benefits for coral reefs. Here, we develop a systematic approach for identifying global forest restoration opportunities that would also result in large decreases in the flux of sediments to coral reefs. We estimate how land‐use change affects sediment runoff globally using high‐resolution spatial data and determine the subsequent risk of sediment exposure on coral reefs using a diffusion‐based ocean transport model. Our results reveal that sediment export is a major issue affecting 41% of coral reefs globally. The main coastal watersheds with the highest sediment export are predominantly located in Southeast Asian countries, with Indonesia and the Philippines accounting for 52% of the sediment export in coastal areas near coral reefs. We show how restoring forest across multiple watersheds could help to reduce sediment export to 63,000 km 2 of coral reefs. Although reforestation opportunities in areas that discharge onto coral reefs are relatively small across watersheds, it is possible to achieve large sediment reduction benefits by strategically targeting watersheds located in regions with a high density of corals near to the coast. Thus, reforestation benefits on coral reefs do not necessarily come from the watersheds that produce the highest sediment export. These analyses are key for generating informed action to support both international conservation policy and national restoration activities.

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Association of NFκβ, TNFα, IL-6, IL-1β, and LPL Polymorphisms with Type 2 Diabetes Mellitus and Biochemical Parameters in a Mexican Population - O. C. Martínez-Ramírez; D. A. Salazar-Piña; Ramos-García M. de Lorena; C. Castro-Hernández; L. Casas-Ávila; J. A. Portillo-Jacobo; J. Rubio (Biochemical Genetics, 2021)

Detection of porcine circovirus type 2 (PCV2) in the Philippines and the complexity of PCV2-associated disease diagnosis - Agnes dela Cruz; Chiara Palmieri; Rachel Azul; Christina Legaspi; Suzan Lola; Tamsin S. Barnes; Christopher R. Parke; Conny Turni; John I. Alawneh; Augusto S. Baluyut; Voltaire G. Basinang; Jose E. David; et al. (Tropical Animal Health and Production, 2021)

Correction to: Importance of evaluating protein glycosylation in pluripotent stem cell‑derived cardiomyocytes for research and clinical applications - Maia I. Kelly; Mustafa Albahrani; Chase Castro; Ellen Poon; Bin Yan; Jack Littrell; Matthew Waas; Kenneth R. Boheler; Rebekah L. Gundry (Pflügers Archiv - European Journal of Physiology, 2021)

Importance of evaluating protein glycosylation in pluripotent stem cell-derived cardiomyocytes for research and clinical applications - Maia I. Kelly; Mustafa Albahrani; Chase Castro; Ellen Poon; Bin Yan; Jack Littrell; Matthew Waas; Kenneth R. Boheler; Rebekah L. Gundry (Pflügers Archiv - European Journal of Physiology, 2021)
Proper protein glycosylation is critical to normal cardiomyocyte physiology. Aberrant glycosylation can alter protein localization, structure, drug interactions, and cellular function. The in vitro differentiation of human pluripotent stem cells into cardiomyocytes (hPSC-CM) has become increasingly important to the study of protein function and to the fields of cardiac disease modeling, drug testing, drug discovery, and regenerative medicine. Here, we offer our perspective on the importance of protein glycosylation in hPSC-CM. Protein glycosylation is dynamic in hPSC-CM, but the timing and extent of glycosylation are still poorly defined. We provide new data highlighting how observed changes in hPSC-CM glycosylation may be caused by underlying differences in the protein or transcript abundance of enzymes involved in building and trimming the glycan structures or glycoprotein gene products. We also provide evidence that alternative splicing results in altered sites of glycosylation within the protein sequence. Our findings suggest the need to precisely define protein glycosylation events that may have a critical impact on the function and maturation state of hPSC-CM. Finally, we provide an overview of analytical strategies available for studying protein glycosylation and identify opportunities for the development of new bioinformatic approaches to integrate diverse protein glycosylation data types. We predict that these tools will promote the accurate assessment of protein glycosylation in future studies of hPSC-CM that will ultimately be of significant experimental and clinical benefit.

Reactive Orange 16 dye degradation in anaerobic and aerobic MBBR coupled with ozonation: addressing pathways and performance - F. D. Castro; J. P. Bassin; T. L. M. Alves; G. L. Sant’Anna; M. Dezotti (International Journal of Environmental Science and Technology, 2021)

Be quick or be dead: high temperatures reduce Aedes aegypti (Diptera: Culicidae) larval development time and pyriproxyfen larvicide efficiency in laboratory conditions - Lidia Moura; Barbara L. de Nadai; Aline C. Bernegossi; Mayara C. Felipe; Gleyson B. Castro; Juliano J. Corbi (International Journal of Tropical Insect Science, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Miconia albicans and Curcuma longa herbal medicines positively modulate joint pain, function and inflammation in patients with osteoarthritis: a clinical study - Thiago P. O. Gomes; Jonathan I. N. Souza; Lucas C. Somerlate; Vanessa A. Mendonça; Nerilson M. Lima; Gabriela P. Carli; Sandra B. R. Castro; Teresinha de Jesus A. S. Andrade; João V. L. Dias; Marcone A. L. Oliveira; Caio C. S. Alves; Alessandra P. Carli (Inflammopharmacology, 2021)

Pathological characteristics, survival, and risk of breast cancer associated with estrogen and xenobiotic metabolism polymorphisms in Mexican women with breast cancer - O. C. Martínez-Ramírez; C. Castro-Hernández; R. Pérez-Morales; L. Casas-Ávila; Ramos-García M. de Lorena; A. Salazar-Piña; J. Rubio (Cancer Causes & Control, 2021)

Application of rhamnolipid surfactant for remediation of toxic metals of long- and short-term contamination sites - C. S. C. Lopes; D. B. Teixeira; B. F. Braz; R. E. Santelli; L. V. A. de Castilho; J. G. C. Gomez; R. P. V. Castro; L. Seldin; D. M. G. Freire (International Journal of Environmental Science and Technology, 2021)

Molecular sexing of Xenarthra: a tool for genetic and ecological studies - Carmen Elena Barragán-Ruiz; Eliana Paviotti-Fischer; Karen Giselle Rodríguez-Castro; Arnaud L. J. Desbiez; Pedro Manoel Galetti (Conservation Genetics Resources, 2021)

Bacterial Nanocellulose Mulch as a Potential Greener Alternative for Urban Gardening in the Small-Scale Food Production of Onion Plants - L. Cárcamo; S. Sierra; M. Osorio; J. Velásquez-Cock; L. Vélez-Acosta; C. Gómez-Hoyos; C. Castro; R. Zuluaga; P. Gañán (Agricultural Research, 2021)

Effects of Environmental Variables and Habitat Integrity on the Structure of the Aquatic Insect Communities of Streams in the Cerrado-Caatinga Ecotone in Northeastern Brazil - E. R. Castro; D. S. Veras; G. S. Lustosa; C. A. S. Azevêdo; L. Juen (Neotropical Entomology, 2021)

Rutin improves glutamate uptake and inhibits glutamate excitotoxicity in rat brain slices - Rafael S. Ferreira; Jéssica Teles-Souza; Cleide dos Santos Souza; Érica P. L. Pereira; Fillipe M. de Araújo; Alessandra Bispo da Silva; Juliana H. Castro e Silva; Yasmine Nonose; Yanier Núñez-Figueredo; Adriano M. de Assis; Diogo O. Souza; Maria de Fátima D. Costa; et al. (Molecular Biology Reports, 2021)

Seismic stratigraphy of a deep water basin in the Brazilian equatorial margin: the eastern portion of Potiguar Basin and Touros High - Júlia C. L. G. Fonseca; Helenice Vital; Yoe A. R. Perez; David L. Castro; André G. Aquino da Silva; Moab P. Gomes (Geo-Marine Letters, 2020)

Barcoding helps threatened species: the case of Iris marsica (Iridaceae) from the protected areas of the Abruzzo (Central Italy) - O. De Castro; E. Del Guacchio; E. Di Iorio; A. Di Maio; L. Di Martino; F. Bartolucci; F. Conti (Plant Biosystems, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Losing Genes: The Evolutionary Remodeling of Cetacea Skin - Gonçalo Espregueira Themudo; Luís Q. Alves; André M. Machado; Mónica Lopes-Marques; Rute R. da Fonseca; Miguel Fonseca; Raquel Ruivo; L. Filipe C. Castro (Frontiers in Marine Science, 2020)

Delinted cottonseed in diets for finishing sheep - W. J. R. Castro; A. M. Zanine; D. J. Ferreira; A. L. Souza; R. M. A. Pinho; M. O. M. Parente; H. N. Parente; E. M. Santos (Tropical Animal Health and Production, 2020)

Retrospective study of porcine circovirus 3 (PCV3) in swine tissue from Brazil (1967–2018) - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; R. L. Silveira; T. X. Castro (Brazilian Journal of Microbiology, 2020)

Latitudinal patterns of species diversity on South American rocky shores: Local processes lead to contrasting trends in regional and local species diversity - Juan J. Cruz‐Motta; Patricia Miloslavich; Edlin Guerra‐Castro; Alejandra Hernández‐Agreda; Cesar Herrera; Francisco Barros; Sergio A. Navarrete; Roger D. Sepúlveda; Tim M. Glasby; Gregorio Bigatti; Maritza Cardenas‐Calle; Pedro B. M. Carneiro; et al. (Journal of Biogeography, 2020)
Aim We evaluated whether patterns of species diversity (α, β and γ) of rocky shore assemblages followed latitudinal gradients (i.e. LDGs) along the South American coasts, and tested hypotheses related to potential processes sustaining or disrupting the expected LDG pattern at various spatial scales. Location Coasts of South America. Taxon Macroalgae and sessile/slow‐moving macrofauna on intertidal rocky shores. Methods We evaluated changes in species composition across 143 sites. The degree of replacement and loss of species at different spatial scales (i.e. coasts, regions and sites) were estimated to help distinguish among ecological, historical and evolutionary hypotheses for explaining LDGs. Furthermore, components of diversity and taxonomic distinctness were measured, and variability in these measures was decomposed using analysis of covariance. Finally, we examined relationships between diversity and a suite of environmental and anthropogenic variables to identify potential mechanisms that may be responsible for the reported spatial relationships. Results Species composition varied with latitude, and this variability was relatively consistent on both coasts. At all spatial scales, replacement of species was the dominant phenomenon (>95%), rather than loss in the total number of species ( Main conclusions Species diversity of South American rocky shores followed, with interruptions, LDGs. The trend of those LDGs, however, depended on the scale and metric used to describe diversity. It is proposed that patterns of LDGs at various scales are not the result of a single overarching process but are strongly influenced by local and regional processes. Although the most evident environmental gradient was the decrease in SST towards the south, it was demonstrated that regional and local environmental variables were also important for understanding the increase in regional β‐diversity towards the tropics.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Nutritional evaluation and human health-promoting potential of compounds biosynthesized by native microalgae from the Peruvian Amazon - Marianela Cobos; Sheyla Pérez; Janeth Braga; Gabriel Vargas-Arana; Leenin Flores; Jae D. Paredes; J. Dylan Maddox; Jorge L. Marapara; Juan C. Castro (World Journal of Microbiology and Biotechnology, 2020)

Heat-related mortality at the beginning of the twenty-first century in Rio de Janeiro, Brazil - João L. Geirinhas; Ana Russo; Renata Libonati; Ricardo M. Trigo; Lucas C. O. Castro; Leonardo F. Peres; Mônica de Avelar F. M. Magalhães; Baltazar Nunes (International Journal of Biometeorology, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Characterization of the complete mitochondrial genome of Amblyomma ovale, comparative analyses and phylogenetic considerations - Juan E. Uribe; Santiago Nava; Katherine R. Murphy; Evelina L. Tarragona; Lyda R. Castro (Experimental and Applied Acarology, 2020)

The use of an Allonais inaequalis reproduction test as an ecotoxicological bioassay - M. C. Felipe; A. C. Bernegossi; G. B. Castro; F. R. Pinheiro; B. L. Nadai; B. N. Cardoso-Silva; J. J. Corbi (Ecotoxicology, 2020)

Special issue: Advances in convection-permitting climate modeling - Andreas F. Prein; Roy Rasmussen; Christopher L. Castro; Aiguo Dai; Justin Minder (Climate Dynamics, 2020)

Effects of combined 5-HT2A and cannabinoid receptor modulation on a schizophrenia-related prepulse inhibition deficit in mice - Adriana M. Marques; Michele V. Macena; Aline R. Cardoso; Camila S. O. Hammes; Fernanda M. L. Pinheiro; Newton G. Castro; Gilda A. Neves (Psychopharmacology, 2020)

Leuconostoc mesenteroides subsp. mesenteroides SD23 Prevents Metabolic Dysfunction Associated with High-Fat Diet–Induced Obesity in Male Mice - Diana C. Castro-Rodríguez; Luis A. Reyes-Castro; Claudia C. Vega; Guadalupe L. Rodríguez-González; Jorge Yáñez-Fernández; Elena Zambrano (Probiotics and Antimicrobial Proteins, 2020)

Taxonomic treatment of Connarus (Connaraceae) in the Brazilian Amazon - Cassio A. P. Toledo; Vinicius Castro Souza; Rubens L. G. Coelho (Brittonia, 2020)

Nitrogen flux into metabolites and microcystins changes in response to different nitrogen sources in Microcystis aeruginosa NIES ‐843 - Lauren E. Krausfeldt; Abigail T. Farmer; Hector F. Castro; Gregory L. Boyer; Shawn R. Campagna; Steven W. Wilhelm (Environmental Microbiology, 2020)
Summary The over‐enrichment of nitrogen (N) in the environment has contributed to severe and recurring harmful cyanobacterial blooms, especially by the non‐N 2 ‐fixing Microcystis spp. N chemical speciation influences cyanobacterial growth, persistence and the production of the hepatotoxin microcystin, but the physiological mechanisms to explain these observations remain unresolved. Stable‐labelled isotopes and metabolomics were employed to address the influence of nitrate, ammonium, and urea on cellular physiology and production of microcystins in Microcystis aeruginosa NIES‐843. Global metabolic changes were driven by both N speciation and diel cycling. Tracing 15 N‐labelled nitrate, ammonium, and urea through the metabolome revealed N uptake, regardless of species, was linked to C assimilation. The production of amino acids, like arginine, and other N‐rich compounds corresponded with greater turnover of microcystins in cells grown on urea compared to nitrate and ammonium. However, 15 N was incorporated into microcystins from all N sources. The differences in N flux were attributed to the energetic efficiency of growth on each N source. While N in general plays an important role in sustaining biomass, these data show that N‐speciation induces physiological changes that culminate in differences in global metabolism, cellular microcystin quotas and congener composition.

Molluscan genomics: the road so far and the way forward - André Gomes-dos-Santos; Manuel Lopes-Lima; L. Filipe C. Castro; Elsa Froufe (Hydrobiologia, 2020)

A comparison of machine and deep-learning algorithms applied to multisource data for a subtropical forest area classification - C. Sothe; C. M. De Almeida; M. B. Schimalski; V. Liesenberg; L. E. C. La Rosa; J. D. B. Castro; R. Q. Feitosa (International Journal of Remote Sensing, 2020)

Thirty days after anterior cruciate ligament transection is sufficient to induce signs of knee osteoarthritis in rats: pain, functional impairment, and synovial inflammation - Germanna M. Barbosa; Jonathan E. Cunha; Thiago L. Russo; Thiago M. Cunha; Paula A. T. S. Castro; Francisco F. B. Oliveira; Fernando Q. Cunha; Fernando S. Ramalho; Tania F. Salvini (Inflammation Research, 2020)

Do metal contamination and plant species affect microbial abundance and bacterial diversity in the rhizosphere of metallophytes growing in mining areas in a semiarid climate? - Leila Benidire; Sofia I. A. Pereira; Ahmed Naylo; Paula M. L. Castro; Ali Boularbah (Journal of Soils and Sediments, 2020)

Correction to: Numerical Modelling of Water Flow Through Granular Material for Isolated and Simultaneous Extractions in Block Caving - Katherine Sánchez; Sergio Palma; Raúl L. Castro (Rock Mechanics and Rock Engineering, 2020)

Role of inflammation, oxidative stress, and autonomic nervous system activation during the development of right and left cardiac remodeling in experimental pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; A. C. Bahr; P. Türck; A. L. de Castro; C. Campos-Carraro; F. Visioli; T. R. Fernandes-Piedras; K. R. Casali; C. M. C. Scassola; G. Baldo; et al. (Molecular and Cellular Biochemistry, 2020)

Evidence of a landlocked reproducing population of the marine pejerrey Odontesthes argentinensis (Actinopterygii; Atherinopsidae) - Darío C. Colautti; Leandro Miranda; Mariano Gonzalez‐Castro; Vanina Villanova; Carlos A. Strüssmann; Miguel Mancini; Tomas Maiztegui; Gustavo Berasain; Ricardo Hattori; Fabian Grosman; Pablo Sanzano; Ismael Lozano; et al. (Journal of Fish Biology, 2020)
In South America, the order Atheriniformes includes the monophyletic genus Odontesthes with 20 species that inhabit freshwater, estuarine and coastal environments. Pejerrey Odontesthes argentinensis is widely distributed in coastal and estuarine areas of the Atlantic Ocean and is known to foray into estuaries of river systems, particularly in conditions of elevated salinity. However, to our knowledge, a landlocked self‐sustaining population has never been recorded. In this study, we examined the pejerrey population of Salada de Pedro Luro Lake (south‐east of Buenos Aires Province, Argentina) to clarify its taxonomic identity. An integrative taxonomic analysis based on traditional meristic, landmark‐based morphometrics and genetic techniques suggests that the Salada de Pedro Luro pejerrey population represents a novel case of physiological and morphological adaptation of a marine pejerrey species to a landlocked environment and emphasises the environmental plasticity of this group of fishes.

The worm burden of tracer kids and lambs browsing heterogeneous vegetation is influenced by strata harvested and not total dry matter intake or plant life form - P. R. Jaimez-Rodríguez; P. G. González-Pech; J. Ventura-Cordero; D. R. B. Brito; L. M. Costa-Júnior; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

Neurocognitive Impairment in mdx Mice - Clarissa M. Comim; Letícia Ventura; Viviane Freiberger; Paula Dias; Daiane Bragagnolo; Matheus L. Dutra; Ricardo A. Amaral; Ana Lucia S. Camargo-Fagundes; Patrícia A. Reis; Hugo C. Castro-Faria-Neto; Mariz Vainzof; Maria I. Rosa (Molecular Neurobiology, 2019)

Identification of Susceptible Rainfall-Induced Landslide Areas Based on Field Experiments and Multi-criteria Analysis in GIS Environment: A Proposal for Non-inventoried Areas - Leonardo C. Assis; Maria L. Calijuri; Mateus M. Salvador; Jackeline de S. Castro; Carolina F. Carvalho (Geotechnical and Geological Engineering, 2019)

Identification and characterization of atypical enteropathogenic and Shiga toxin-producing Escherichia coli isolated from ground beef and poultry breast purchased in Botucatu, Brazil - Rodrigo H. S. Tanabe; Melissa A. Vieira; Noelle A. B. Mariano; Regiane C. B. Dias; Rafael Ventin da Silva; Caroline M. Castro; Luis F. dos Santos; Carlos H. Camargo; Ricardo S. Yamatogi; Vera L. M. Rall; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2019)

Novel choline analog 2-(4-((1-phenyl-1H-pyrazol-4-yl)methyl)piperazin-1-yl)ethan-1-ol produces sympathoinhibition, hypotension, and antihypertensive effects - Ricardo Menegatti; Flávio S. Carvalho; Luciano M. Lião; Bianca Villavicencio; Hugo Verli; Aline A. Mourão; Carlos H. Xavier; Carlos H. Castro; Gustavo R. Pedrino; Octavio L. Franco; Iransé Oliveira-Silva; Nicole M. Ashpole; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Metagenomic Analysis of the Bacterial and Fungal Community Associated to the Rhizosphere of Tabebuia chrysantha and T. billbergii - Luis X. Llacsa; Rosa L. Solis-Castro; Eric Mialhe; Ramón García-Seminario (Current Microbiology, 2019)

Optical properties of atmospheric particles over an urban site in Mexico City and a peri-urban site in Queretaro - Rafael N. Liñán-Abanto; O. Peralta; D. Salcedo; L. G. Ruiz-Suárez; P. Arnott; G. Paredes-Miranda; H. Alvarez-Ospina; T. Castro (Journal of Atmospheric Chemistry, 2019)

Current and Future Variations of the Monsoons of the Americas in a Warming Climate - Salvatore Pascale; Leila M. V. Carvalho; David K. Adams; Christopher L. Castro; Iracema F. A. Cavalcanti (Current Climate Change Reports, 2019)

Intra-inflorescence variation in reproductive traits of Conopholis alpina (Orobanchaceae): effect of flower maturation pattern and resource competition - Itzel L. Castillo-Sánchez; Dulce M. Figueroa-Castro (Plant Ecology, 2019)

Hippocampus and Prefrontal Cortex Modulation of Contextual Fear Memory Is Dissociated by Inhibiting De Novo Transcription During Late Consolidation - Luciana M. Pereira; Caio M. de Castro; Lorena T. L. Guerra; Thaís M. Queiroz; João T. Marques; Grace Schenatto Pereira (Molecular Neurobiology, 2019)

Skeletal muscle miR-34a/SIRT1:AMPK axis is activated in experimental and human non-alcoholic steatohepatitis - André L. Simão; Marta B. Afonso; Pedro M. Rodrigues; Margarida Gama-Carvalho; Mariana V. Machado; Helena Cortez-Pinto; Cecília M. P. Rodrigues; Rui E. Castro (Journal of Molecular Medicine, 2019)

Gymnopodium floribundum fodder as a model for the in vivo evaluation of nutraceutical value against Haemonchus contortus - F. A. Méndez-Ortiz; C. A. Sandoval-Castro; J. Ventura-Cordero; L. A. Sarmiento-Franco; R. H. Santos-Ricalde; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The acute phase response elicited by a viral-like molecular pattern increases energy expenditure in Artibeus lituratus - Camila Triana-Llanos; Adriana L. Guerrero-Chacón; David Rivera-Ruíz; Vladimir Rojas-Díaz; Andrea Niño-Castro (Biologia, 2019)

The Impact of the Right Coronary Artery Geometric Parameters on Hemodynamic Performance - N. Pinho; L. C. Sousa; C. F. Castro; C. C. António; M. Carvalho; W. Ferreira; R. Ladeiras-Lopes; N. D. Ferreira; P. Braga; N. Bettencourt; S. I. S. Pinto (Cardiovascular Engineering and Technology, 2019)

Humans and scavenging raptors facilitate Argentine ant invasion in Doñana National Park: no counter-effect of biotic resistance - Sara Castro-Cobo; Soledad Carpintero; Joaquín L. Reyes-López; Fabrizio Sergio; Elena Angulo (Biological Invasions, 2019)

Effects of alternative silvicultural systems on litter decomposition and nutrients dynamics in sub-Antarctic forests - N. Oro Castro; A. Moretto; L. J. Selzer; J. Escobar (Agroforestry Systems, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Speciation and periodic restricted environments. The case of genus Ononis L. (subsections Natrix and Viscosae ) - I. Castro; J. Rocha; C. Costa; G. Costa; R. Ramírez-Rodríguez; F. Amich; V. Carnide; A. L. Crespí (Plant Biosystems, 2019)

Citalopram Reduces Aggregation of ATXN3 in a YAC Transgenic Mouse Model of Machado-Joseph Disease - Naila S. Ashraf; Sara Duarte-Silva; Emily D. Shaw; Patrícia Maciel; Henry L. Paulson; Andreia Teixeira-Castro; Maria do Carmo Costa (Molecular Neurobiology, 2019)

Trace and major element contents, microbial communities, and enzymatic activities of urban soils of Marrakech city along an anthropization gradient - Ahmed Naylo; Sofia I. Almeida Pereira; Leila Benidire; Hicham El Khalil; Paula M. L. Castro; Stéphanie Ouvrard; Christophe Schwartz; Ali Boularbah (Journal of Soils and Sediments, 2019)

Convergent inactivation of the skin-specific C-C motif chemokine ligand 27 in mammalian evolution - Mónica Lopes-Marques; Luís Q. Alves; Miguel M. Fonseca; Giulia Secci-Petretto; André M. Machado; Raquel Ruivo; L. Filipe C. Castro (Immunogenetics, 2019)

Reproductive dynamics of the white shrimp Litopenaeus schmitti (Burkenroad 1936) in a beach seine fishery in northeastern Brazil - Cecília Craveiro; Silvio Peixoto; Emanuell F. Silva; Leandro N. Eduardo; Alex S. Lira; Hildemário Castro-Neto; Flávia L. Frédou; Roberta Soares (Invertebrate Reproduction & Development, 2019)

Porosity Estimation and Geometric Characterization of Fractured and Karstified Carbonate Rocks Using GPR Data in the Salitre Formation, Brazil - Iurianne M. M. Conti; David L. de Castro; Francisco H. R. Bezerra; Caroline L. Cazarin (Pure and Applied Geophysics, 2019)

Production of benzyl carbonyl (rose aroma) from whey and its effect on pollutant load removal - L. Conde Báez; J. Castro Rosas; J. R. Villagómez Ibarra; I. Palma Quiroz; J. B. Páez Lerma; C. A. Gómez Aldapa (Environment, Development and Sustainability, 2019)

Spatial assessment of the performance of multiple high‐resolution satellite‐based precipitation data sets over the Middle East - Ahmed M. El Kenawy; Matthew F. McCabe; Juan I. Lopez‐Moreno; Yossef Hathal; S. M. Robaa; Ahmed L. Al Budeiri; Khan Zaib Jadoon; Abdou Abouelmagd; Ali Eddenjal; Fernando Domínguez‐Castro; Ricardo M. Trigo; Sergio M. Vicente‐Serrano (International Journal of Climatology, 2019)
This study presents the first comprehensive evaluation of the performance of three globally high‐resolution remotely sensed products in replicating the main characteristics of rainfall over the Middle East, with special emphasis on extreme wet events. Specifically, we employed daily observational data from a network of rain gauges ( N = 217), spanning the retrospective period 1998–2013 and covering six countries in the Middle East (i.e., Egypt, Iraq, Jordan, Libya, Saudi Arabia, and Syria), against data derived from three global satellite‐based precipitation products: the Version 7 TRMM (Tropical Rainfall Measuring Mission) Multi‐satellite Precipitation Analysis 3B42 product (TRMM‐3B42), the Climate Prediction Center MORPHing technique (CMORPH), and the Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks (PERSIANN). Alongside a range of conventional statistical error measures (e.g., bias, normalized root‐mean‐square error [nRMSE] and Spearman's rho correlation coefficient), this study also gives priority to evaluate the skill of these products in reproducing characteristics of extreme wet events (e.g., frequency, intensity, duration, onset, anomaly). Results demonstrate that TRMM‐3B42 generally performs well in estimating rainfall totals during the rainy season (ONDJFMA), with a mean bias of 0.05 mm, nRMSE of 0.15 mm, and Spearman's rho of 0.74 for the whole Middle East. In contrast, PERSIANN‐CDR and CMORPH‐BLD underestimate the observed rainfall. Importantly, TRMM‐3B42 outperforms other products in reproducing the frequency and intensity of the most extreme wet events, while PERSIANN‐CDR and CMORPH‐BLD fail to reproduce these key characteristics. Notably, all products perform poorly in reproducing the climatology of the anomalous wet events in the region, indicating that careful scrutiny must be warranted before using these products, particularly for hydrological modelling. Considering the daily resolution of these remotely sensed precipitation products and their reasonable spatial resolution (0.25 × 0.25°) in comparison to available in situ data over the Middle East, results of this work provide a solid scientific reference for national stakeholders and policy makers to decide on the most useful product for their specific applications (e.g., hydrological modelling, streamflow forecasts, water resources management, and hydrometeorological hazard assessment and mitigation).

Correlation between geometric parameters of the left coronary artery and hemodynamic descriptors of atherosclerosis: FSI and statistical study - N. Pinho; C. F. Castro; C. C. António; N. Bettencourt; L. C. Sousa; S. I. S. Pinto (Medical & Biological Engineering & Computing, 2019)

Comparative Assessment of BGM and PLC/PRF/5 Cell Lines for Enteric Virus Detection in Biosolids - Sherif Abd-Elmaksoud; Nohelia Castro-del Campo; Charles P. Gerba; Ian L. Pepper; Kelly R. Bright (Food and Environmental Virology, 2019)

Two epizootic Perkinsus spp. events in commercial oyster farms at Santa Catarina, Brazil - Ana C. Luz Cunha; Vitor de A. Pontinha; Maria Alcina M. de Castro; Simone Sühnel; Sthefanie C. Medeiros; Ângela M. Moura da Luz; Ricardo Harakava; Leonardo Tachibana; Danielle F. Mello; Naissa M. Danielli; Alcir L. Dafre; Aimê R. M. Magalhães; et al. (Journal of Fish Diseases, 2019)
Perkinsus spp. have been detected in various bivalve species from north‐east Brazil. Santa Catarina is a South Brasil state with the highest national oyster production. Considering the pathogenicity of some Perkinsus spp., a study was carried out to survey perkinsosis in two oyster species cultured in this State, the mangrove oyster Crassostrea gasar and the Pacific oyster Crassostrea gigas . Sampling involved eight sites along the state coast, and oyster sampling was collected during the period between January 2013 and December 2014. For the detection of Perkinsus , Ray's fluid thioglycollate medium (RFTM) and histology were used, and for the identification of the species, PCR and DNA sequencing were used. Perkinsus spp. was found by RFTM in C. gigas and C. gasar from São Francisco do Sul. This pathology was also detected in C. gasar from Balneário Barra do Sul both, by RFTM and histology. Perkinsus marinus was identified in C. gigas and C. gasar from São Francisco do Sul and Perkinsus beihaiensis in C. gasar from Balneário Barra do Sul. This is the first report of P. marinus in C. gigas from South America. Results of this preliminary study suggest that both oyster species tolerate the species of Perkinsus identified, without suffering heavy lesions.

Cryopreserved potato shoot tips showed genotype-specific response to sucrose concentration in rewarming solution (RS) - Rainer Vollmer; Rosalva Villagaray; Mario Castro; Noelle L. Anglin; David Ellis (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Comparative Analysis of the Adhesive Proteins of the Adult Stalked Goose Barnacle Pollicipes pollicipes (Cirripedia: Pedunculata) - Miguel Rocha; Paulo Antas; L. Filipe C. Castro; Alexandre Campos; Vítor Vasconcelos; Filipe Pereira; Isabel Cunha (Marine Biotechnology, 2019)

Anti-obesity effects of kaempferol by inhibiting adipogenesis and increasing lipolysis in 3T3-L1 cells - D. Torres-Villarreal; A. Camacho; H. Castro; R. Ortiz-Lopez; A. L. de la Garza (Journal of Physiology and Biochemistry, 2019)

Sugar transport systems in Kluyveromyces marxianus CCT 7735 - Fernando Augusto da Silveira; Raphael Hermano S. Diniz; Geraldo M. S. Sampaio; Rogelio L. Brandão; Wendel B. da Silveira; Ieso M. Castro (Antonie van Leeuwenhoek, 2019)

Numerical Modelling of Water Flow Through Granular Material for Isolated and Simultaneous Extractions in Block Caving - Katherine Sánchez; Sergio Palma; Raúl L. Castro (Rock Mechanics and Rock Engineering, 2019)

Identification of a Novel Nucleobase-Ascorbate Transporter Family Member in Fish and Amphibians - Diogo Oliveira; André M. Machado; Tiago Cardoso; Mónica Lopes-Marques; L. Filipe C. Castro; Raquel Ruivo (Fishes, 2019)
Nucleobase-Ascorbate Transporter (NAT) family includes ascorbic acid, nucleobases, and uric acid transporters: With broad evolutionary distribution. In vertebrates, four members have been previously recognized, the ascorbate transporters Slc23a1 and Slc3a2, the nucleobase transporter Slc23a4 and an orphan transporter Slc23a3. Using phylogenetic and synteny analysis, we identify a fifth member of the vertebrate slc23 complement (slc23a5), present in neopterygians (gars and teleosts) and amphibians, and clarify the evolutionary relationships between the novel gene and known slc23 genes. Further comparative analysis puts forward uric acid as the preferred substrate for Slc23a5. Gene expression quantification, using available transcriptomic data, suggests kidney and testis as major expression sites in Xenopus tropicalis (western clawed frog) and Danio rerio (zebrafish). Additional expression in brain was detected in D. rerio, while in the Neoteleostei Oryzias latipes (medaka) slc23a5 expression is restricted to the brain. The biological relevance of the retention of an extra transporter in fish and amphibians is discussed.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Using floristics, modern systematics and phylogenetics for disentangling biodiversity hotspots across scales: a Mediterranean case study - V. I. Simón-Porcar; M. Escudero; L. Navarro; A. de Castro; J. Lorite; R. Molina-Venegas; J. Arroyo (Plant Biosystems, 2018)

Cetacea are natural knockouts for IL20 - Mónica Lopes-Marques; André M. Machado; Susana Barbosa; Miguel M. Fonseca; Raquel Ruivo; L. Filipe C. Castro (Immunogenetics, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Metabolic cost of acute phase response in the frugivorous bat, Artibeus lituratus - Adriana L. Guerrero-Chacón; David Rivera-Ruíz; Vladimir Rojas-Díaz; Camila Triana-Llanos; Andrea Niño-Castro (Mammal Research, 2018)

Aluminum fractionation in acidic soils and river sediments in the Upper Mero basin (Galicia, NW Spain) - L. Palleiro; C. Patinha; M. L. Rodríguez-Blanco; M. M. Taboada-Castro; M. T. Taboada-Castro (Environmental Geochemistry and Health, 2018)

Enzyme-linked immunosorbent assay and agar gel immunodiffusion assay for diagnosis of equine infectious anemia employing p26 protein fused to the maltose-binding protein - Karin F. L. P. Fontes; Luiz C. Silva-Júnior; Sérgio A. Nascimento; Daniel P. Chaves; Jose W. Pinheiro-Júnior; Antonio C. Freitas; Roberto S. Castro; André L. S. Jesus (Archives of Virology, 2018)

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Use of chemometric analyses to assess biological wastewater treatment plants by protozoa and metazoa monitoring - A. Luís Amaral; Cristiano S. Leal; A. Isabel Vaz; J. Carvalho Vieira; Andreia C. Quinteiro; M. Lourdes Costa; L. Miguel Castro (Environmental Monitoring and Assessment, 2018)

Characterization of esterase activity from an Acetomicrobium hydrogeniformans enzyme with high structural stability in extreme conditions - Patricia S. Kumagai; Raissa F. Gutierrez; Jose L. S. Lopes; Julia M. Martins; David M. Jameson; Aline M. Castro; Luiz F. Martins; Ricardo DeMarco; Nelma R. S. Bossolan; B. A. Wallace; Ana P. U. Araujo (Extremophiles, 2018)

Pacific sea surface temperature related influences on North American monsoon precipitation within North American Regional Climate Change Assessment Program models - Carlos M. Carrillo; Christopher L. Castro; Gregg Garfin; Hsin‐I Chang; Melissa S. Bukovsky; Linda O. Mearns (International Journal of Climatology, 2018)
Climate inter‐annual variability over the North American monsoon (NAM) region is associated with El Niño‐Southern Oscillation (ENSO) and Pacific decadal variability (PDV), which drive a warm season atmospheric teleconnection response. Using the North American Regional Climate Change Assessment Program (NARCCAP) simulations, previous studies have found that regional models forced with an atmospheric reanalysis (NARCCAP Phase I) represent the NAM reasonably well as a climatological feature. However, when these same regional models are forced with global climate model projections (NARCCAP Phase II), their ability to represent the NAM as a salient feature substantially degrades. The present study evaluates NAM inter‐annual climate variability through the continental‐scale patterns of summer precipitation within the NARCCAP simulations (Phases I and II), in relation to ENSO–PDV, and the presence of the driving atmospheric teleconnection response. Multivariate statistical analyses are applied to sea surface temperature and precipitation data sets to determine dominant variability at continental scale, with focus on the southwest. The analysis reveals that NARCCAP Phase I simulations are able to portray the spatial pattern of precipitation associated with ENSO–PDV in a similar way to observations. However, all NARCCAP Phase II simulations, with the exception of the HRM(Hadcm3) regional–global model pair, fail to reproduce this climate variability. Although including all possible NARCCAP model simulations to generate a multi‐model ensemble mean would increase the statistical degree of confidence in climate projections, this type of result would not increase confidence in the physical climatology of model representations of warm season climate variability. More physically based, process‐oriented metrics are needed to evaluate model quality in assessing the uncertainty of future climate change in multi‐model ensemble products used for climate change impacts assessments.

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

Polymorphism of the DRD2 Gene in a Mexican Population with Mental Deviations - M. Salas-Magaña; C. A. Tovilla-Zárate; A. Genis; T. B. González-Castro; I. E. Juárez-Rojop; M. L. López-Narvaez (Neurophysiology, 2018)

Morphotectonic development of the Ceará Terrace: a marginal ridge on the western side of the Romanche Fracture Zone in the Brazilian Equatorial Margin - João Fernando Pezza Andrade; M. P. Gomes; F. H. R. Bezerra; D. L. de Castro; H. Vital (Geo-Marine Letters, 2018)

Low salinity as a biosecurity tool for minimizing biofouling on ship sea chests - Maria Cecilia T. de Castro; Thomas Vance; Anna L. E. Yunnie; Timothy W. Fileman; Jason M. Hall-Spencer (Ocean Science, 2018)
Biofouling is a major vector in the transfer of non-native species around the world. Species can be transported on virtually all submerged areas of ships (e.g. hulls, sea chests, propellers) and so antifouling systems are used to reduce fouling. However, with increased regulation of biocides used in antifoulants (e.g. the International Maritime Organization tributyltin ban in 2008), there is a need to find efficient and sustainable alternatives. Here, we tested the hypothesis that short doses of low salinity water could be used to kill fouling species in sea chests. Settlement panels were suspended at 1.5 m depth in a Plymouth marina for 24 months by which time they had developed mature biofouling assemblages. We exposed these panels to three different salinities (7, 20 and 33) for 2 hours using a model sea chest placed in the marina and flushed with freshwater. Fouling organism diversity and abundance were assessed before panels were treated, immediately after treatment, and then 1 week and 1 month later. Some native ascidian Dendrodoa grossularia survived, but all other macrobenthos were killed by the salinity 7 treatment after 1 week. The salinity 20 treatment was not effective at killing the majority of fouling organisms. On the basis of these results, we propose that sea chests be flushed with freshwater for at least 2 hours before ships leave port. This would not cause unnecessary delays or costs and could be a major step forward in improving biosecurity.

Geostatistical Interplay Between Geophysical and Geochemical Data: Mapping Litho-Structural Assemblages of Mesozoic Igneous Activities in the Parnaíba Basin (NE Brazil) - David L. de Castro; Diógenes C. Oliveira; Maria Helena B. M. Hollanda (Surveys in Geophysics, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A morphological database for 606 Colombian bird species - Paola Montoya; Mailyn A. Gonzalez; Elkin A. Tenorio; Juan Pablo López‐Ordóñez; Alejandro Pinto Gómez; Diego Cueva; Aldemar A. Acevedo Rincón; Camilo Angarita Yanes; Héctor Manuel Arango Martínez; Orlando Armesto; Jefry S. Betancur; Angela Caguazango Castro; et al. (Ecology, 2018)
Colombia is the country with the highest bird diversity in the world. Despite active research in ornithology, compelling morphological information of most bird species is still sparse. However, morphological information is the baseline to understand how species respond to environmental variation and how ecosystems respond to species loss. As part of a national initiative, the Instituto Alexander von Humboldt in collaboration with 12 Colombian institutions and seven biological collections, measured up to 15 morphological traits of 9,892 individuals corresponding to 606 species: 3,492 from individuals captured in field and 6,400 from museum specimens. Species measured are mainly distributed in high Andean forest, páramo, and wetland ecosystems. Seven ornithological collections in Colombia and 18 páramo complexes throughout Colombia were visited from 2013 to 2015. The morphological traits involved measurements from bill (total and exposed culmen, bill width and depth), wing (length, area, wingspan, and the distance between longest primary and longest secondary), tail (length and shape), tarsus (length), hallux (length and claw hallux), and mass. The number of measured specimens per species was variable, ranging from 1 to 321 individuals with a median of four individuals per species. Overall, this database gathered morphological information for >30% of Colombian bird diversity. No copyright, proprietary, or cost restrictions apply; the data should be cited appropriately when used.

Plant-based chimeric HPV-virus-like particles bearing amyloid-β epitopes elicit antibodies able to recognize amyloid plaques in APP-tg mouse and Alzheimer’s disease brains - R. Gonzalez-Castro; G. Acero Galindo; Y. García Salcedo; L. Uribe Campero; V. Vazquez Perez; M. Carrillo-Tripp; G. Gevorkian; M. A. Gomez Lim (Inflammopharmacology, 2018)

Water-soluble inorganic ions of size-differentiated atmospheric particles from a suburban site of Mexico City - Telma Castro; Oscar Peralta; Dara Salcedo; José Santos; María I. Saavedra; María L. Espinoza; Alejandro Salcido; Ana-Teresa Celada-Murillo; Susana Carreón-Sierra; Harry Álvarez-Ospina; Giovanni Carabali; Valter Barrera; et al. (Journal of Atmospheric Chemistry, 2018)

A new computational model for the prediction of toxicity of phosphonate derivatives using QSPR - Rosa L. Camacho-Mendoza; Eliazar Aquino-Torres; Viviana Cordero-Pensado; Julián Cruz-Borbolla; José G. Alvarado-Rodríguez; Pandiyan Thangarasu; Carlos Z. Gómez-Castro (Molecular Diversity, 2018)

Atorvastatin Prevents Early Oxidative Events and Modulates Inflammatory Mediators in the Striatum Following Intranasal 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) Administration in Rats - Naiani F. Marques; Adalberto A. Castro; Gianni Mancini; Fernanda L. Rocha; Adair R. S. Santos; Rui D. Prediger; Andreza Fabro De Bem; Carla I. Tasca (Neurotoxicity Research, 2018)

Genotoxicity of spent pot liner as determined with the zebrafish (Danio rerio) experimental model - Tássia F. D. Castro; Isadora M. Paiva; Aline F. S. Carvalho; Isadora L. Assis; Marcel J. Palmieri; Larissa F. Andrade-Vieira; Silvana Marcussi; Luis D. Solis-Murgas (Environmental Science and Pollution Research, 2018)

Abnormalities in flatfishes of the south‐west Atlantic Ocean - D. L. Castellini; M. González‐Castro; A. Lopez‐Cazorla; J. M. Díaz De Astarloa (Journal of Fish Biology, 2018)
Five adult paralichthyid specimens with various kinds of abnormalities are reported from the south‐west Atlantic Ocean. These abnormal flatfish specimens represent the first records of wholly ambicoloured Paralichthys orbignyanus specimens having a deep notch between the eye and dorsal fin and a partially albinistic specimen having skeletal deformities and only the second record of an almost totally ambicoloured specimen. We also report the first observation of reversal in Paralichthys patagonicus and an almost totally ambicoloured, reversed Xystreurys rasile .

The cycling gonad: retinoic‐acid synthesis and degradation patterns during adult zebrafish Danio rerio oogenesis - R. Ruivo; A. Capitão; L. F. C. Castro; M. M. Santos (Journal of Fish Biology, 2018)
The expression pattern of genes coding for enzymes of the retinoic acid (RA) synthetic and degradation pathways was characterized in adult female zebrafish Danio rerio . Females were conditioned until maturation and post‐spawn expression dynamics were determined. A striking upregulation of cyp26b1 , but not cyp26a1 , was observed following egg deposition, decreasing to initial levels during recovery. A similar, yet lower, fluctuation was observed for aldh1a2 and rdh10a , the enzymes participating in the two‐step RA biosynthesis cascade. The present work highlights the dynamics of the adult D. rerio oogenesis and uncovers novel, yet elusive, metabolic contributors. Possible compartmentalized roles for the different gene paralogue isoforms are discussed.

Ascorbic acid toxicity is related to oxidative stress and enhanced by high light and knockdown of chloroplast ascorbate peroxidases in rice plants - Jamyla L. S. Castro; Yugo Lima-Melo; Fabricio E. L. Carvalho; Antonio G. S. Feitosa; Milton C. Lima Neto; Andréia Caverzan; Marcia Margis-Pinheiro; Joaquim A. G. Silveira (Theoretical and Experimental Plant Physiology, 2018)

Micropropagation of Asparagus macrorrhizus, a Spanish endemic species in extreme extinction risk - J. J. Regalado; E. Carmona-Martin; M. López-Granero; A. Jiménez-Araujo; P. Castro; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Comparison of four modeling tools for the prediction of potential distribution for non-indigenous weeds in the United States - Roger Magarey; Leslie Newton; Seung Cheon Hong; Yu Takeuchi; David Christie; Catherine S. Jarnevich; Lisa Kohl; Martin Damus; Steven I. Higgins; Leah Millar; Karen Castro; Amanda West; et al. (Biological Invasions, 2018)

First evidence of viral and bacterial oyster pathogens in the Brazilian coast - D F Mello; N M Danielli; F Curbani; V A Pontinha; S Suhnel; M A M Castro; S C Medeiros; N C Wendt; R Trevisan; A R M Magalhães; A L Dafre (Journal of Fish Diseases, 2018)

Morpho-environmental strategies in the genus Ononis L. (subsections Natrix and Viscosae ) in Western Mediterranean - J. Rocha; R. Ramírez; M. Díaz; M. Martins; I. García-Cabral; F. Amich; R. Almeida; V. Carnide; I. Castro; A. L. Crespí (Plant Biosystems, 2018)

An integrated analysis (microfacies and ichnology) of a shallow carbonate-platform succession: upper Aptian, Lower Cretaceous, Betic Cordillera - L. M. Nieto; M. Reolid; F. J. Rodríguez-Tovar; J. M. Castro; J. M. Molina; P. A. Ruiz-Ortiz (Facies, 2018)

Magnetic nanoparticles as a novel strategy for marine toxins mitigation - Jesús González-Jartín; Inés Rodríguez; Amparo Alfonso; María Sainz; M. Vieytes; Z. Vargas Osorio; L. De Castro Alves; Y. Y. Piñeiro-Redondo; J. Rivas; Luis Botana (Frontiers in Marine Science, 2018)

Substrate influence on aromatic plant growth in extensive green roofs in a Mediterranean climate - Cristina M. Monteiro; Cristina S. C. Calheiros; João P. Martins; Francisco M. Costa; Paulo Palha; Sara de Freitas; Nuno M. M. Ramos; Paula M. L. Castro (Urban Ecosystems, 2017)

Multi-year climate variability in the Southwestern United States within a context of a dynamically downscaled twentieth century reanalysis - Carlos M. Carrillo; Christopher L. Castro; Hsin-I Chang; Thang M. Luong (Climate Dynamics, 2017)

Plume composition and volatile flux of Nyamulagira volcano, Democratic Republic of Congo, during birth and evolution of the lava lake, 2014–2015 - N. Bobrowski; G. B. Giuffrida; S. Arellano; M. Yalire; M. Liotta; L. Brusca; S. Calabrese; S. Scaglione; J. Rüdiger; J. M. Castro; B. Galle; D. Tedesco (Bulletin of Volcanology, 2017)

A Comminution Model for Secondary Fragmentation Assessment for Block Caving - René Gómez; Raúl L. Castro; Aldo Casali; Sergio Palma; Asieh Hekmat (Rock Mechanics and Rock Engineering, 2017)

Arsenic in the health of ecosystems: spatial distribution in water, sediment and aquatic biota of Pampean streams - M. C. Rodríguez Castro; L Marcó P; M. C. Ranieri; C. Vázquez; A. Giorgi (Environmental Monitoring and Assessment, 2017)

Structure of the N-glycans from the chlorovirus NE-JV-1 - Immacolata Speciale; Irina Agarkova; Garry A. Duncan; James L. Van Etten; Cristina De Castro (Antonie van Leeuwenhoek, 2017)

Short-term and long-term effects of diazepam on the memory for discrimination and generalization of scopolamine - C. Casasola-Castro; L. Weissmann-Sánchez; E. Calixto-González; A. Aguayo-Del Castillo; D. N. Velázquez-Martínez (Psychopharmacology, 2017)

New Species of Tenuisvalvae (Duverger) (Coleoptera: Coccinellidae) Feeding on Parthenolecanium perlatum (Cockerell) (Hemiptera: Coccidae) in Citrus Crop - P B Santos; C F Castro-Guedes; A L B G Peronti; L M Almeida (Neotropical Entomology, 2017)

Asparagus macrorrhizus Pedrol, Regalado et López-Encina, an endemic species from Spain in extreme extinction risk, is a valuable genetic resource for asparagus breeding - J. J. Regalado; R. Moreno; P. Castro; E. Carmona-Martin; R. Rodríguez; J. Pedrol; N. Larrañaga; R. Guillén; J. Gil; C. L. Encina (Genetic Resources and Crop Evolution, 2017)

Influence of drinking water salinity on carcass characteristics and meat quality of Santa Inês lambs - Daniela P. V. Castro; Sandra M. Yamamoto; Gherman G. L. Araújo; Rafael S. B. Pinheiro; Mario A. A. Queiroz; Ítalo R. R. Albuquerque; José H. A. Moura (Tropical Animal Health and Production, 2017)

A large-scale viability assessment of the potato cryobank at the International Potato Center (CIP) - Rainer Vollmer; Rosalva Villagaray; José Cárdenas; Mario Castro; Oswaldo Chávez; Noelle L. Anglin; David Ellis (In Vitro Cellular & Developmental Biology - Plant, 2017)

Preparation of Activated Carbon from Sugarcane Bagasse Soot and Methylene Blue Adsorption - Luana A. R. Giusto; Fábio L. Pissetti; Talita S. Castro; Fabiano Magalhães (Water, Air, & Soil Pollution, 2017)

Ecology and recovery plans for the four Spanish endangered endemic butterfly species - M. L. Munguira; J. M. Barea-Azcón; S. Castro-Cobo; E. García-Barros; S. Miteva; J. Olivares; H. Romo (Journal of Insect Conservation, 2017)

Quantitative image analysis of polyhydroxyalkanoates inclusions from microbial mixed cultures under different SBR operation strategies - António L. Amaral; Hugo Abreu; Cristiano Leal; Daniela P. Mesquita; Luís M. Castro; Eugénio C. Ferreira (Environmental Science and Pollution Research, 2017)

Acer binzayedii (Sapindaceae), a new maple species from Mexico - Yalma L. Vargas-Rodriguez; Lowell E. Urbatsch; Vesna Karaman-Castro; Blanca L. Figueroa-Rangel (Brittonia, 2017)

The role of epigenetic modifiers in extended cultures of functional hepatocyte-like cells derived from human neonatal mesenchymal stem cells - M. Cipriano; J. C. Correia; S. P. Camões; N. G. Oliveira; P. Cruz; H. Cruz; M. Castro; J. L. Ruas; J. M. Santos; J. P. Miranda (Archives of Toxicology, 2017)

RA Differentiation Enhances Dopaminergic Features, Changes Redox Parameters, and Increases Dopamine Transporter Dependency in 6-Hydroxydopamine-Induced Neurotoxicity in SH-SY5Y Cells - Fernanda M. Lopes; Leonardo Lisbôa da Motta; Marco A. De Bastiani; Bianca Pfaffenseller; Bianca W. Aguiar; Luiz F. de Souza; Geancarlo Zanatta; Daiani M. Vargas; Patrícia Schönhofen; Giovana F. Londero; Liana M. de Medeiros; Valder N. Freire; et al. (Neurotoxicity Research, 2017)

Energy Dissipating Devices in Falling Rock Protection Barriers - L. Castanon-Jano; E. Blanco-Fernandez; D. Castro-Fresno; F. Ballester-Muñoz (Rock Mechanics and Rock Engineering, 2017)

Productivity of a Continuous Mining System for Block Caving Mines - L. F. Orellana; R. Castro; A. Hekmat; E. Arancibia (Rock Mechanics and Rock Engineering, 2017)

Exploring genetic variation, oil and α-tocopherol content in avocado (Persea americana) from northwestern Mexico - Ayesha Y. Peraza-Magallanes; Marco A. Pereyra-Camacho; Eduardo Sandoval-Castro; Sergio Medina-Godoy; Maribel Valdez-Morales; Michael T. Clegg; Carlos L. Calderón-Vázquez (Genetic Resources and Crop Evolution, 2017)

Inactivation, lysis and degradation by-products of Saccharomyces cerevisiae by electrooxidation using DSA - Lyliane F. Trigueiro; Larissa M. Silva; Luciana A. B. D. Itto; Thiago M. B. F. Oliveira; Artur J. Motheo; Carlos A. Martínez-Huitle; Janete J. F. Alves; Suely S. L. Castro (Environmental Science and Pollution Research, 2017)

Identification and genetic characterization of classical swine fever virus isolates in Brazil: a new subgenotype - Marta N. F. Silva; Diogo M. F. Silva; Adriana S. Leite; Ana L. V. Gomes; Antonio C. Freitas; Jose W. Pinheiro-Junior; Roberto S. Castro; Andre L. S. Jesus (Archives of Virology, 2017)

Hepatocyte spheroids as a competent in vitro system for drug biotransformation studies: nevirapine as a bioactivation case study - Pedro F. Pinheiro; Sofia A. Pereira; Shrika G. Harjivan; Inês L. Martins; Aline T. Marinho; Madalena Cipriano; Cristina C. Jacob; Nuno G. Oliveira; Matilde F. Castro; M. Matilde Marques; Alexandra M. M. Antunes; Joana P. Miranda (Archives of Toxicology, 2017)

Integrated proteomics and metabolomics suggests symbiotic metabolism and multimodal regulation in a fungal‐endobacterial system - Zhou Li; Qiuming Yao; Stephen P. Dearth; Matthew R. Entler; Hector F. Castro Gonzalez; Jessie K. Uehling; Rytas J. Vilgalys; Gregory B. Hurst; Shawn R. Campagna; Jessy L. Labbé; Chongle Pan (Environmental Microbiology, 2017)
Summary Many plant‐associated fungi host endosymbiotic endobacteria with reduced genomes. While endobacteria play important roles in these tri‐partite plant–fungal–endobacterial systems, the active physiology of fungal endobacteria has not been characterized extensively by systems biology approaches. Here, we use integrated proteomics and metabolomics to characterize the relationship between the endobacterium Mycoavidus sp. and the root‐associated fungus Mortierella elongata . In nitrogen‐poor media, M. elongata had decreased growth but hosted a large and growing endobacterial population. The active endobacterium likely extracted malate from the fungal host as the primary carbon substrate for energy production and biosynthesis of phospho‐sugars, nucleobases, peptidoglycan and some amino acids. The endobacterium obtained nitrogen by importing a variety of nitrogen‐containing compounds. Further, nitrogen limitation significantly perturbed the carbon and nitrogen flows in the fungal metabolic network. M. elongata regulated many pathways by concordant changes on enzyme abundances, post‐translational modifications, reactant concentrations and allosteric effectors. Such multimodal regulations may be a general mechanism for metabolic modulation.

Erratum to: Physiological differences and changes in global DNA methylation levels in Agave angustifolia Haw. albino variant somaclones during the micropropagation process - Fátima Duarte-Aké; Eduardo Castillo-Castro; Felipe Barredo Pool; Francisco Espadas; Jorge M. Santamaría; Manuel L. Robert; Clelia De-la-Peña (Plant Cell Reports, 2017)

Differential impact of hotter drought on seedling performance of five ecologically distinct pine species - Luis Matías; Jorge Castro; Pedro Villar-Salvador; José L. Quero; Alistair S. Jump (Plant Ecology, 2017)

Life cycle inference and phylogeny of Ortholinea labracis n. sp. (Myxosporea: Ortholineidae), a parasite of the European seabass Dicentrarchus labrax (Teleostei: Moronidae), in a Portuguese fish farm - L F Rangel; S Rocha; G Casal; R Castro; R Severino; C Azevedo; F Cavaleiro; M J Santos (Journal of Fish Diseases, 2017)
Ortholinea labracis n. sp. is described and its life cycle is inferred from a Southern Portuguese fish farm, with basis on microscopic and molecular procedures. This myxosporean parasite infects the urinary bladder of the European seabass Dicentrarchus labrax and the intestinal epithelium of a marine oligochaete of the genus Tectidrilus . Myxospores subspherical in valvular view and ellipsoidal in sutural view measuring 7.6 ± 0.3 (6.8–8.7) μm in length, 7.2 ± 0.2 (6.7–7.7) μm in width and 6.5 ± 0.4 (5.8–7.7) μm in thickness. Two polar capsules, 3.0 ± 0.2 (2.6–3.4) μm long and 2.4 ± 0.1 (2.0–2.9) μm wide, located at the same level, but with divergent orientation and opening to opposite sides of the suture line. Sequencing of the SSU rRNA gene revealed a similarity of 100% between the analysed myxospores and triactinomyxon actinospores. The phylogenetic setting of O. labracis n. sp. shows subgrouping in correlation with tissue tropism, but identifies this parasite as another exception to the main division of Myxosporea into the main freshwater and marine lineages.

Diabetes and breast cancer mortality in Black women - Marjory Charlot; Nelsy Castro-Webb; Traci N. Bethea; Kimberly Bertrand; Deborah A. Boggs; Gerald V. Denis; Lucile L. Adams-Campbell; Lynn Rosenberg; Julie R. Palmer (Cancer Causes & Control, 2017)

Characterization of hepatitis B virus infection in illicit drug users in the Marajó Archipelago, northern Brazil - Andréia P. Andrade; Suzy D. B. Pacheco; Fabricio Q. Silva; Luiz M. L. Pinheiro; Jairo A. A. Castro; Carlos E. M. Amaral; Renata B. Hermes; Benedikt Fischer; João R. R. Pinho; José Alexandre R. Lemos; Aldemir B. Oliveira-Filho (Archives of Virology, 2017)

Performance and health of Holstein calves fed different levels of milk fortified with symbiotic complex containing pre- and probiotics - M. I. Marcondes; T. R. Pereira; J. C. C. Chagas; E. A. Filgueiras; M. M. D. Castro; G. P. Costa; A. L. L. Sguizzato; R. D. Sainz (Tropical Animal Health and Production, 2016)

Physiological differences and changes in global DNA methylation levels in Agave angustifolia Haw. albino variant somaclones during the micropropagation process - Fátima Duarte-Aké; Eduardo Castillo-Castro; Felipe Barredo Pool; Francisco Espadas; Jorge M. Santamaría; Manuel L. Robert; Clelia De-la-Peña (Plant Cell Reports, 2016)

Evidence of oxidative stress in brain and liver of young rats submitted to experimental galactosemia - Márcia B. Castro; Bruna K. Ferreira; José Henrique Cararo; Adália E. Chipindo; Marina L. Magenis; Monique Michels; Lucinéia G. Danielski; Marcos R. de Oliveira; Gustavo C. Ferreira; Emilio L. Streck; Fabricia Petronilho; Patrícia F. Schuck (Metabolic Brain Disease, 2016)

IFITM3 and severe influenza virus infection. No evidence of genetic association - M. López-Rodríguez; E. Herrera-Ramos; J. Solé-Violán; J. J. Ruíz-Hernández; L. Borderías; J. P. Horcajada; E. Lerma-Chippirraz; O. Rajas; M. Briones; M. C. Pérez-González; M. A. García-Bello; E. López-Granados; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Assessment of plant growth promoting bacterial populations in the rhizosphere of metallophytes from the Kettara mine, Marrakech - L. Benidire; S. I. A. Pereira; P. M. L. Castro; A. Boularbah (Environmental Science and Pollution Research, 2016)

Assessing the extent and nature of wildlife trade on the dark web - Joseph R. Harrison; David L. Roberts; Julio Hernandez‐Castro (Conservation Biology, 2016)
Use of the internet as a trade platform has resulted in a shift in the illegal wildlife trade. Increased scrutiny of illegal wildlife trade has led to concerns that online trade of wildlife will move onto the dark web. To provide a baseline of illegal wildlife trade on the dark web, we downloaded and archived 9852 items (individual posts) from the dark web, then searched these based on a list of 121 keywords associated with illegal online wildlife trade, including 30 keywords associated with illegally traded elephant ivory on the surface web. Results were compared with items known to be illegally traded on the dark web, specifically cannabis, cocaine, and heroin, to compare the extent of the trade. Of these 121 keywords, 4 resulted in hits, of which only one was potentially linked to illegal wildlife trade. This sole case was the sale and discussion of Echinopsis pachanoi (San Pedro cactus), which has hallucinogenic properties. This negligible level of activity related to the illegal trade of wildlife on the dark web relative to the open and increasing trade on the surface web may indicate a lack of successful enforcement against illegal wildlife trade on the surface web.

Radial and tangential migration of telencephalic somatostatin neurons originated from the mouse diagonal area - Luis Puelles; N. Morales-Delgado; P. Merchán; B. Castro-Robles; M. Martínez-de-la-Torre; C. Díaz; J. L. Ferran (Brain Structure and Function, 2016)

Quality of the Solimões River water for domestic use by the riverine community situated in Manacapuru-Amazonas-Brazil - N. G. P. Pantoja; L. M. Castro; S. D. Rocha; J. A. Silva; J. S. P. Ribeiro; A. R. Donald; L. M. Silva; T. C. S. Oliveira (Environmental Science and Pollution Research, 2016)

Trophic models and short-term dynamic simulations for benthic-pelagic communities at Banco Chinchorro Biosphere Reserve (Mexican Caribbean): a conservation case - F.A. Rodríguez-Zaragoza; M. Ortiz; F. Berrios; L. Campos; A. de Jesús-Navarrete; J. Castro-Pérez; A. Hernández-Flores; M. García-Rivas; F. Fonseca-Peralta; E. Gallegos-Aguilar (Community Ecology, 2016)

Efficacy of Cinnamaldehyde Against Enteric Viruses and Its Activity After Incorporation Into Biodegradable Multilayer Systems of Interest in Food Packaging - M. J. Fabra; J. L. Castro-Mayorga; W. Randazzo; J. M. Lagarón; A. López-Rubio; R. Aznar; G. Sánchez (Food and Environmental Virology, 2016)

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

Sex steroid imbalances in the muricid Stramonita haemastoma from TBT contaminated sites - M. Rossato; I. B. Castro; C. L. Paganini; E. P. Colares; G. Fillmann; G. L. L. Pinho (Environmental Science and Pollution Research, 2016)

Mine land valorization through energy maize production enhanced by the application of plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi - Helena Moreira; Sofia I. A. Pereira; Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Environmental Science and Pollution Research, 2016)

Low‐frequency variability of precipitation in the North American monsoon region as diagnosed through earlywood and latewood tree‐ring chronologies in the southwestern US - Carlos M. Carrillo; Christopher L. Castro; Connie A. Woodhouse; Daniel Griffin (International Journal of Climatology, 2016)
Recent studies have pointed out the statistical occurrence of dual‐season droughts detected in tree‐ring chronologies over the southwestern US region that is not well described by instrumental observed records of the 20th century. In this study, a multi‐statistical approach that evaluates persistent dual‐season drought using a mode‐of‐variability oriented approach is proposed, considering a new network of tree‐ring earlywood ( EW )‐ and latewood‐adjusted ( LW adj ) chronologies from throughout southwestern North America. To determine dominant patterns of spatiotemporal variability, empirical, orthogonal functions, canonical correlation analysis, and multi‐taper‐method singular value decomposition analyses were applied, with focus on variability from inter‐annual to centennial periods and highlighting the multi‐decadal signals inherent to proxy record network. During the instrumental period, we demonstrate that EW and LW adj networks of tree‐ring chronologies are able to capture the associated precipitation responses of cool and warm season atmospheric teleconnections. Considering the four‐century period of the complete tree‐ring network, we explore the possibility of a dual summer–winter variability signal in the low‐frequency climate regime. EW and LW adj seem to be coherent in‐phase at the very low‐frequency scale (50–100 years spectral band). This provocative result is supported by major historic documented multi‐year droughts of the region since 1650. Thus, the temporal variation of these chronologies time series and its associated spatial pattern strongly suggest that this low‐frequency mode might represents an important spatiotemporal variation of droughts in the Southwest; however, the source of this signal is still an open question and of great interest for drought planning and resource management in the region.

Acyl-coenzyme A oxidases 1 and 3 in brown trout (Salmo trutta f. fario): Can peroxisomal fatty acid β-oxidation be regulated by estrogen signaling? - Tânia Vieira Madureira; L. Filipe C. Castro; Eduardo Rocha (Fish Physiology and Biochemistry, 2016)

Flower and fruit structure of the endangered species Petagnaea gussonei (Sprengel) Rauschert (Saniculoideae, Apiaceae) and implications for its reproductive biology - O. De Castro; P. Colombo; L. Gianguzzi; R. Perrone (Plant Biosystems, 2015)

Expression of myostatin in the spotted rose snapper Lutjanus guttatus during larval and juvenile development under cultured conditions - J. Torres‐Velarde; L. Ibarra‐Castro; E. Rodríguez‐Ibarra; I. Sifuentes‐Romero; R. Hernández‐Cornejo; A. García‐Gasca (Journal of Fish Biology, 2015)
In this study, the developmental expression pattern of myostatin ( mstn ) in the spotted rose snapper Lutjanus guttatus under culture conditions is presented. The full coding sequence of mstn from L. guttatus was isolated from muscle tissue, obtaining 1134 nucleotides which encode a peptide of 377 amino acids. The phylogenetic analysis indicated that this sequence corresponds to mstn‐1 . mstn expression was detected in embryonic stages, and maintained at low levels until 28 days post‐hatch, when it showed a significant increase, coinciding with the onset of metamorphosis. After that, expression was fluctuating, coinciding probably with periods of rapid and slow muscle growth or individual growth rates. mstn expression was also analysed by body mass with higher levels detected in smaller animals, irrespective of age. mstn was also expressed in other tissues from L. guttatus , presenting higher levels in brain, eye and gill. In brain for instance, two variants of mstn were isolated, both coding sequences were identical to muscle, except that one of them contained a 75 nucleotide deletion in exon 1, maintaining the reading frame but deleting two conserved cysteine residues. Phylogenetic analysis indicated that this brain variant was also mstn‐1 . The function of this variant is not clear and needs further investigation. These results indicate that mstn‐1 participates in different physiological processes other than muscle growth in fishes.

T3 and T4 decrease ROS levels and increase endothelial nitric oxide synthase expression in the myocardium of infarcted rats - Alexandre Luz de Castro; Angela Vicente Tavares; Rafael Oliveira Fernandes; Cristina Campos; Adriana Conzatti; Rafaela Siqueira; Tânia Regina G. Fernandes; Paulo Cavalheiro Schenkel; Carmem L. Sartório; Susana Llesuy; Adriane Belló-Klein; Alex Sander da Rosa Araujo (Molecular and Cellular Biochemistry, 2015)

Impact of freshwater inputs on the spatial structure of benthic macroinvertebrate communities in two landlocked coastal lagoons - P. M. Félix; M. J. Correia; P. Chainho; J. L. Costa; M. L. Chaves; T. Cruz; J. J. Castro; C. Mirra; I. Domingos; A. C. F. Silva; L. Cancela da Fonseca (Hydrobiologia, 2015)

Impact of HIV infection on sustained virological response to treatment against hepatitis C virus with pegylated interferon plus ribavirin - P. Monje-Agudo; A. Castro-Iglesias; A. Rivero-Juárez; F. Martínez-Marcos; E. Ortega-González; L. M. Real; B. Pernas; N. Merchante; P. Cid; J. Macías; M. D. Merino; A. Rivero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Regional climate modelling in CLARIS-LPB: a concerted approach towards twentyfirst century projections of regional temperature and precipitation over South America - E. Sánchez; S. Solman; A. R. C. Remedio; H. Berbery; P. Samuelsson; R. P. Da Rocha; C. Mourão; L. Li; J. Marengo; M. de Castro; D. Jacob (Climate Dynamics, 2015)

C-phycocyanin prevents cisplatin-induced mitochondrial dysfunction and oxidative stress - Berenice Fernández-Rojas; Daniela Sarai Rodríguez-Rangel; Luis Fernando Granados-Castro; Mario Negrette-Guzmán; Juan Carlos León-Contreras; Rogelio Hernández-Pando; Eduardo Molina-Jijón; José L. Reyes; Cecilia Zazueta; José Pedraza-Chaverri (Molecular and Cellular Biochemistry, 2015)

Maternal deprivation disrupts mitochondrial energy homeostasis in the brain of rats subjected to ketamine-induced schizophrenia - Alexandra Ioppi Zugno; Felipe Damázio Pacheco; Josiane Budni; Mariana Bittencourt de Oliveira; Lara Canever; Alexandra Stephanie Heylmann; Patrícia Gomes Wessler; Flávia da Rosa Silveira; Gustavo Antunes Mastella; Cinara Ludwig Gonçalves; Karoline V. Freitas; Adalberto Alves de Castro; et al. (Metabolic Brain Disease, 2015)

Expression of intercellular lipid transport and cholesterol metabolism genes in eggs and early larvae stages of turbot, Scophthalmus maximus, a marine aquaculture species - I. Cunha; S. Galante-Oliveira; E. Rocha; R. Urbatzka; L. F. C. Castro (Marine Biology, 2015)

Study of the somaclonal variation produced by different methods of polyploidization in Asparagus officinalis L. - J. J. Regalado; E. Carmona Martín; P. Castro; R. Moreno; J. Gil; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Rhizobacteria isolated from a metal-polluted area enhance plant growth in zinc and cadmium-contaminated soil - S. I. A. Pereira; L. Barbosa; P. M. L. Castro (International Journal of Environmental Science and Technology, 2015)

Detection of a new QTL/gene for growth habit in chickpea CaLG1 using wide and narrow crosses - L. Ali; S. Azam; J. Rubio; H. Kudapa; E. Madrid; R. K. Varshney; P. Castro; W. Chen; J. Gil; T. Millan (Euphytica, 2015)

Evaluation of the use of Olivella minuta (Gastropoda, Olividae) and Hastula cinerea (Gastropoda, Terebridae) as TBT sentinels for sandy coastal habitats - Marcelo Petracco; Rita Monteiro Camargo; Thayana Amorim Berenguel; Noelle C. L. Patrício de Arruda; Lygia A. del Matto; Lílian Lund Amado; Thais Navajas Corbisier; Ítalo Braga Castro; Alexander Turra (Environmental Monitoring and Assessment, 2015)

Dispersive liquid–liquid microextraction and HPLC to analyse fluoxetine and metoprolol enantiomers in wastewaters - Ana R. Ribeiro; Virgínia M. F. Gonçalves; Alexandra S. Maia; Cláudia Ribeiro; Paula M. L. Castro; Maria E. Tiritan (Environmental Chemistry Letters, 2015)

Micropropagation of wild species of the genus Asparagus L. and their interspecific hybrids with cultivated A. officinalis L., and verification of genetic stability using EST-SSRs - J. J. Regalado; E. Carmona-Martín; P. Castro; R. Moreno; J. Gil; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Modulation of apoptosis by sulforaphane is associated with PGC-1α stimulation and decreased oxidative stress in cardiac myoblasts - Rafael O. Fernandes; Jéssica H. P. Bonetto; Boran Baregzay; Alexandre L. de Castro; Stephanie Puukila; Heidi Forsyth; Paulo C. Schenkel; Susana F. Llesuy; Ilma Simoni Brum; Alex Sander R. Araujo; Neelam Khaper; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2015)

Synthesis and biological evaluation of ( − )-13,14-dihydroxy-8,11,13-podocarpatrien-7-one and derivatives from (+)-manool - María L. Novoa; Yelisbeth Escalante; Liliana Maldonado; Iván Galindo-Castro; Annamil Álvarez; Katherine Figarella; Sabrina Marsiccobetre; Irina Arocha; Jais Nieves; Franklin Salazar; Carlos Gámez; Nieves Canudas; et al. (Natural Product Research, 2015)

Inoculation of Pinus pinea seedlings with Pisolithus tinctorius and Suillus bellinii promotes plant growth in benfluralin contaminated soil - Albina R. Franco; Paula M. L. Castro (Plant and Soil, 2015)

Carbon Flows Through the Pelagic Sub-food Web in Two Basins of the Chilean Patagonian Coastal Ecosystem: the Significance of Coastal–Ocean Connection on Ecosystem Parameters - Héctor J. Pavés; Humberto E. González; Leonardo Castro; José L. Iriarte (Estuaries and Coasts, 2015)

Reassessing global change research priorities in mediterranean terrestrial ecosystems: how far have we come and where do we go from here? - E. Doblas‐Miranda; J. Martínez‐Vilalta; F. Lloret; A. Álvarez; A. Ávila; F. J. Bonet; L. Brotons; J. Castro; J. Curiel Yuste; M. Díaz; P. Ferrandis; E. García‐Hurtado; et al. (Global Ecology and Biogeography, 2015)
Aim Mediterranean terrestrial ecosystems serve as reference laboratories for the investigation of global change because of their transitional climate, the high spatiotemporal variability of their environmental conditions, a rich and unique biodiversity and a wide range of socio‐economic conditions. As scientific development and environmental pressures increase, it is increasingly necessary to evaluate recent progress and to challenge research priorities in the face of global change. Location Mediterranean terrestrial ecosystems. Methods This article revisits the research priorities proposed in a 1998 assessment. Results A new set of research priorities is proposed: (1) to establish the role of the landscape mosaic on fire‐spread; (2) to further research the combined effect of different drivers on pest expansion; (3) to address the interaction between drivers of global change and recent forest management practices; (4) to obtain more realistic information on the impacts of global change and ecosystem services; (5) to assess forest mortality events associated with climatic extremes; (6) to focus global change research on identifying and managing vulnerable areas; (7) to use the functional traits concept to study resilience after disturbance; (8) to study the relationship between genotypic and phenotypic diversity as a source of forest resilience; (9) to understand the balance between C storage and water resources; (10) to analyse the interplay between landscape‐scale processes and biodiversity conservation; (11) to refine models by including interactions between drivers and socio‐economic contexts; (12) to understand forest–atmosphere feedbacks; (13) to represent key mechanisms linking plant hydraulics with landscape hydrology. Main conclusions (1) The interactive nature of different global change drivers remains poorly understood. (2) There is a critical need for the rapid development of regional‐ and global‐scale models that are more tightly connected with large‐scale experiments, data networks and management practice. (3) More attention should be directed to drought‐related forest decline and the current relevance of historical land use.

Characterization of antibiosis to the silverleaf whitefly Bemisia tabaci biotype B (Hemiptera: Aleyrodidae) in cowpea entries - Patrícia L. Cruz; Edson L. L. Baldin; Maria de Jesus P. de Castro (Journal of Pest Science, 2014)

Diversity and characterization of culturable bacterial endophytes from Zea mays and their potential as plant growth-promoting agents in metal-degraded soils - S. I. A. Pereira; P. M. L. Castro (Environmental Science and Pollution Research, 2014)

Thermal Stratification Effects on Flow Over a Generic Urban Canopy - V. B. L. Boppana; Z.-T. Xie; I. P. Castro (Boundary-Layer Meteorology, 2014)

Reference genes for RT-qPCR studies in Corynebacterium pseudotuberculosis identified through analysis of RNA-seq data - Daiane M. Carvalho; Pablo H. de Sá; Thiago L. P. Castro; Rodrigo D. Carvalho; Anne Pinto; Danilo J. P. Gil; Priscilla Bagano; Bruno Bastos; Lilia F. M. Costa; Roberto Meyer; Artur Silva; Vasco Azevedo; et al. (Antonie van Leeuwenhoek, 2014)

Exploring N-Acylhydrazone Derivatives Against Clinical Resistant Bacterial Strains - Andressa C. Lannes; Bruno Leal; Juliana S. Novais; Viviane Lione; Georgia C. T. S. Monteiro; André L. Lourenço; Plínio C. Sathler; Alessandro K. Jordão; Carlos R. Rodrigues; Lúcio M. Cabral; Anna Claudia Cunha; Vinicius Campos; et al. (Current Microbiology, 2014)

Electrochemical removal of synthetic textile dyes from aqueous solutions using Ti/Pt anode: role of dye structure - Cynthia K. C. Araújo; Gustavo R. Oliveira; Nedja S. Fernandes; Carmem L. P. S. Zanta; Suely Souza Leal Castro; Djalma R. da Silva; Carlos A. Martínez-Huitle (Environmental Science and Pollution Research, 2014)

Phytomanagement of Cd-contaminated soils using maize (Zea mays L.) assisted by plant growth-promoting rhizobacteria - Helena Moreira; Ana P. G. C. Marques; Albina R. Franco; António O. S. S. Rangel; Paula M. L. Castro (Environmental Science and Pollution Research, 2014)

A software solution for point counting. Petrographic thin section analysis as a case study - Martín L. Larrea; Silvia M. Castro; Ernesto A. Bjerg (Arabian Journal of Geosciences, 2014)

Kinetics and regulation of lactose transport and metabolism in Kluyveromyces lactis JA6 - A. M. Santos; W. B. Silveira; L. G. Fietto; R. L. Brandão; I. M. Castro (World Journal of Microbiology and Biotechnology, 2014)

Mycoses and Antifungals: reviewing the basis of a current problem that still is a biotechnological target for marine products - Luciana Terra; Paula A. Abreu; Valéria L. Teixeira; Izabel C. P. Paixão; Rebeca Pereira; Bruno Leal; André Luiz Lourenço; Pabulo H. Rampelotto; Helena C. Castro (Frontiers in Marine Science, 2014)

Environmental Factors Affecting Germination and Seedling Survival of Carolina Willow (Salix Caroliniana) - Luz M. Castro-Morales; Pedro F. Quintana-Ascencio; John E. Fauth; Kimberli J. Ponzio; Dianne L. Hall (Wetlands, 2014)

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

Environmental and mechanical aspects of an anchored mesh for stabilisation of a cliff at La Alhambra - José L. Justo; Daniel Castro; José M. Azañón; Juan Saura; Percy Durand; Enrique Romero; Narciso Vázquez-Carretero; Antonio Morales-Esteban; Manuel Vázquez-Boza; Enrique Justo (Bulletin of Engineering Geology and the Environment, 2014)

Regionalized differentiation of CRH, TRH, and GHRH peptidergic neurons in the mouse hypothalamus - Nicanor Morales-Delgado; Beatriz Castro-Robles; José L. Ferrán; Margaret Martinez-de-la-Torre; Luis Puelles; Carmen Díaz (Brain Structure and Function, 2014)

Safety and Health Hazard Observations in Hmong Farming Operations - R. L. Neitzel; J. Krenz; A. B. de Castro (Journal of Agromedicine, 2014)

Acquisition of resistant microorganisms and infections in HIV-infected patients admitted to the ICU - N. Cobos-Trigueros; M. Rinaudo; M. Solé; P. Castro; J. Pumarol; C. Hernández; S. Fernández; J. M. Nicolás; J. Mallolas; J. Vila; L. Morata; J. M. Gatell; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Dominant patterns of US warm season precipitation variability in a fine resolution observational record, with focus on the southwest - Brittany Ciancarelli; Christopher L. Castro; Connie Woodhouse; Francina Dominguez; Hsin‐I Chang; Carlos Carrillo; Daniel Griffin (International Journal of Climatology, 2014)
Spatial patterns of interannual variability in US precipitation and their forcing mechanisms are very different between the cool and warm seasons, as determined by the recent observational record. In this work, the dominant continental scale patterns of warm season precipitation variability, in the form of the standardized precipitation index ( SPI ), are related to their large‐scale atmospheric teleconnection forcing patterns. To account for intraseasonal differences in atmospheric teleconnection patterns, the 2‐month SPI is considered for the separate periods of early, June–July ( JJ ), and late, August–September ( AS ), periods, as well as the 6‐month SPI for the cool season (November–April). Rotated empirical orthogonal function analysis and canonical correlation analysis are applied to determine the dominant spatial modes of SPI , their relationship to large‐scale teleconnection patterns, and their possible forcing mechanisms, as seen in anomalies of 500‐mb geopotential height, sea surface temperature ( SST ), and outgoing longwave radiation (OLR). Two dominant quasi‐stationary Rossby wavetrain teleconnections appear to govern US warm season precipitation variability: (1) a mode that reflects the well‐known out‐of‐phase relationship in summer precipitation between the central United States and southwest, which is related to Pacific SST forcing in early summer and Indian monsoon convection in later summer, and (2) Two phases of the Circumglobal Teleconnection pattern that are more related to precipitation variability in the south central and eastern United States The southwest United States region relating to the variability of the North American Monsoon is considered within the continental scale variability patterns associated with the warm season. This work is a subset of a larger project to determine if tree‐ring records from the southwest United States are reliable proxies for extending the warm season climate record. It also provides a benchmark for assessing how US warm season climate patterns may be assessed in regional climate models used for seasonal forecast or climate change projection purposes.

Effect of water restriction on total phenolics and antioxidant properties of Amburana cearensis (Fr. Allem) A.C. Smith cotyledons during seed imbibition - Erica P. L. Pereira; Paulo R. Ribeiro; Marta B. Loureiro; Renato D. de Castro; Luzimar G. Fernandez (Acta Physiologiae Plantarum, 2014)

Advances in surfactants for agrochemicals - Mariano J. L. Castro; Carlos Ojeda; Alicia Fernández Cirelli (Environmental Chemistry Letters, 2014)

Myofibroblasts and the extracellular matrix network in post-myocardial infarction cardiac remodeling - Yonggang Ma; Lisandra E. de Castro Brás; Hiroe Toba; Rugmani Padmanabhan Iyer; Michael E. Hall; Michael D. Winniford; Richard A. Lange; Suresh C. Tyagi; Merry L. Lindsey (Pflügers Archiv - European Journal of Physiology, 2014)

Leptospirosis seroprevalence and risk factors for sheep in Maranhão state, Brazil - Sônia Maria de Carvalho; Ana Lys B. B. Mineiro; Vanessa Castro; Margareth E. Genovez; Sérgio Santos Azevedo; Francisco A. L. Costa (Tropical Animal Health and Production, 2014)

Oxidative stress parameters in blood, liver, and kidney of diabetic rats treated with curcumin and/or insulin - Heloisa Einloft Palma; Patrícia Wolkmer; Miguel Gallio; Marcos M. B. Corrêa; Roberta Schmatz; Gustavo R. Thomé; Luciane B. Pereira; Verônica S. P. Castro; Andréia B. Pereira; Andressa Bueno; Lizielle S. de Oliveira; Debora Rosolen; et al. (Molecular and Cellular Biochemistry, 2014)

Analysis of various physiological salines for heart rate, CNS function, and synaptic transmission at neuromuscular junctions in Drosophila melanogaster larvae - Clara de Castro; Josh Titlow; Zana R. Majeed; Robin L. Cooper (Journal of Comparative Physiology A, 2014)

Isolation of key retinoid signalling and metabolic modules in invertebrates - André Ana; Castro L. Filipe; Ruivo Raquel; Santos Miguel (Frontiers in Marine Science, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Genetic variability in Sambucus nigra L. clones : a preliminary molecular approach - J. LIMA-BRITO; L. CASTRO; J. COUTINHO; F. MORAIS; L. GOMES; H. GUEDES-PINTO; A. CARVALHO (Journal of Genetics, 2013)

Unintended consequences and trade‐offs of fish passage - Robert L McLaughlin; Eric R B Smyth; Theodore Castro‐Santos; Michael L Jones; Marten A Koops; Thomas C Pratt; Luis‐Antonio Vélez‐Espino (Fish and Fisheries, 2013)
We synthesized evidence for unintended consequences and trade‐offs associated with the passage of fishes. Provisioning of fish passageways at dams and dam removals are being carried out increasingly as resource managers seek ways to reduce fragmentation of migratory fish populations and restore biodiversity and nature‐like ecosystem services in tributaries altered by dams. The benefits of provisioning upstream passage are highlighted widely. Possible unwanted consequences and trade‐offs of upstream passage are coming to light, but remain poorly examined and underappreciated. Unintended consequences arise when passage of native and desirable introduced fishes is delayed, undone (fallback), results in patterns of movement and habitat use that reduce D arwinian fitness (e.g. ecological traps), or is highly selective taxonomically and numerically. Trade‐offs arise when passage decisions intended to benefit native species interfere with management decisions intended to control the unwanted spread of non‐native fishes and aquatic invertebrates, or genes, diseases and contaminants carried by hatchery and wild fishes. These consequences and trade‐offs will vary in importance from system to system and can result in large economic and environmental costs. For some river systems, decisions about how to manage fish passage involve substantial risks and could benefit from use of a formal, structured process that allows transparent, objective and, where possible, quantitative evaluation of these risks. Such a process can also facilitate the design of an adaptive framework that provides valuable insights into future decisions.

Generating anatomical models of the heart and the aorta from medical images for personalized physiological simulations - J. Weese; A. Groth; H. Nickisch; H. Barschdorf; F. M. Weber; J. Velut; M. Castro; C. Toumoulin; J. L. Coatrieux; M. De Craene; G. Piella; C. Tobón-Gomez; et al. (Medical & Biological Engineering & Computing, 2013)

Morphophysiology, morphoanatomy, and grain yield under field conditions for two maize hybrids with contrasting response to drought stress - T. Corrêa de Souza; E. Mauro de Castro; P. César Magalhães; L. De Oliveira Lino; E. Trindade Alves; P. Emílio Pereira de Albuquerque (Acta Physiologiae Plantarum, 2013)

Detection of a new Os HV ‐1 DNA strain in the healthy P acific oyster, C rassostrea gigas Thunberg, from the G ulf of C alifornia - J M Grijalva‐Chon; R Castro‐Longoria; J Ramos‐Paredes; T L Enríquez‐Espinoza; F Mendoza‐Cano (Journal of Fish Diseases, 2013)

Differential Exoproteome Analysis of Two Corynebacterium pseudotuberculosis Biovar Ovis Strains Isolated from Goat (1002) and Sheep (C231) - Wanderson M. Silva; Núbia Seyffert; Alessandra Ciprandi; Agenor V. Santos; Thiago L. P. Castro; Luis G. C. Pacheco; Debmalya Barh; Yves Le Loir; Adriano M. C. Pimenta; Anderson Miyoshi; Artur Silva; Vasco Azevedo (Current Microbiology, 2013)

Sequential foraging of dusky dolphins with an inspection of their prey distribution - Mariana Degrati; Silvana L. Dans; Griselda V. Garaffo; Ariel G. Cabreira; Federico Castro Machado; Enrique A. Crespo (Marine Mammal Science, 2013)
The aim of this work was to analyze the sequential foraging behavior of dusky dolphins ( Lagenorhynchus obscurus ). Foraging sequences were defined when more than two feeding bouts occur with a traveling bout between them. We hypothesized that traveling costs of searching for prey patches were related to the time spent feeding on a patch. In addition, the distribution and seasonal variation of anchovy schools were studied in the area to better understand dolphins' behavior. We observed dolphins from a research vessel from 2001 to 2007, and recorded their location and behavior. Anchovy data were collected during two hydro‐acoustic surveys. Dusky dolphin behaviors varied seasonally; they spent a greater proportion of time traveling and feeding in the warm season (Kruskal‐Wallis: H = 172.07, P 0.01). During the cold season dolphin groups were more likely to exhibit diving behavior and less surface feeding. We found a positive correlation between searching and foraging time ( r = 0.88, P = 0.019), suggesting that the costs associated with searching were compensated by an increase in the energy intake during the foraging bout. There was an association between dusky dolphin and anchovy distribution, in that they co‐varied spatially and seasonally.

Evaluation of an ensemble of regional climate model simulations over South America driven by the ERA-Interim reanalysis: model performance and uncertainties - Silvina A. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; J. Marengo; N. L. Pessacg; A. R. C. Remedio; S. C. Chou; H. Berbery; H. Le Treut; M. de Castro; et al. (Climate Dynamics, 2013)

Identification and genetic diversity of Rosellinia spp. associated with root rot of coffee in Colombia - Bertha L. Castro; Angela J. Carreño; Narmer F. Galeano; Jolanda Roux; Michael J. Wingfield; Álvaro L. Gaitán (Australasian Plant Pathology, 2013)

The Influence of Discharge, pH, Dissolved Organic Carbon, and Suspended Solids on the Variability of Concentration and Partitioning of Metals in a Rural Catchment - L. Palleiro; M. L. Rodríguez-Blanco; M. M. Taboada-Castro; M. T. Taboada-Castro (Water, Air, & Soil Pollution, 2013)

Tissue expression of PPAR-alpha isoforms in Scophthalmus maximus and transcriptional response of target genes in the heart after exposure to WY-14643 - R. Urbatzka; S. Galante-Oliveira; E. Rocha; L. F. C. Castro; I. Cunha (Fish Physiology and Biochemistry, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

23Na multiple quantum filtered NMR characterisation of Na+ binding and dynamics in animal cells: a comparative study and effect of Na+/Li+ competition - Carla P. Fonseca; Luís L. Fonseca; Liliana P. Montezinho; Paula M. Alves; Helena Santos; M. Margarida C. A. Castro; Carlos F. G. C. Geraldes (European Biophysics Journal, 2013)

Induction of capsaicinoid accumulation in placental tissues of Capsicum chinense Jacq. requires primary ammonia assimilation - Wendy del R. Ancona-Escalante; Fray M. Baas-Espinola; Lizbeth A. Castro-Concha; Felipe A. Vázquez-Flota; Marcela Zamudio-Maya; María L. de Miranda-Ham (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Large-Eddy Simulation of Heat Transfer from a Single Cube Mounted on a Very Rough Wall - V. B. L. Boppana; Zheng-Tong Xie; Ian P. Castro (Boundary-Layer Meteorology, 2013)

Concentration of ascorbic acid and antioxidant response in early life stages of Engraulis ringens and zooplankton during the spawning seasons of 2006–2009 off central Chile - M. C. Krautz; L. R. Castro; M. González; A. Llanos-Rivera; I. Montes; H. González; R. R. González; J. C. Vera (Marine Biology, 2013)

Metabolic responses of the squat lobster (Pleuroncodes monodon) larvae to low oxygen concentration - B. Yannicelli; K. Paschke; R. R. González; L. R. Castro (Marine Biology, 2013)

Effect of the metals iron, copper and silver on fluorobenzene biodegradation by Labrys portucalensis - Irina S. Moreira; Catarina L. Amorim; Maria F. Carvalho; António C. Ferreira; Carlos M. Afonso; Paula M. L. Castro (Biodegradation, 2013)

Enantioselective HPLC analysis and biodegradation of atenolol, metoprolol and fluoxetine - Ana Rita Ribeiro; Carlos Magalhães Afonso; Paula M. L. Castro; Maria Elizabeth Tiritan (Environmental Chemistry Letters, 2013)

Effect of diflubenzuron on the development of Pinus pinaster seedlings inoculated with the ectomycorrhizal fungus Pisolithus tinctorius - Miguel A. Ramos; Nadine R. Sousa; Albina R. Franco; Vítor Costa; Rui S. Oliveira; Paula M. L. Castro (Environmental Science and Pollution Research, 2013)

Can the red palm mite threaten the Amazon vegetation? - Manoel G. C. Gondim; Tatiane M. M. G. Castro; Alberto L. Marsaro; Denise Navia; José W. S. Melo; Peterson R. Demite; Gilberto J. de Moraes (Systematics and Biodiversity, 2012)

Stunting delays maturation of triceps surae mechanical properties and motor performance in prepubertal children - Maria das Graças Paiva; Thaysa O. L. Souza; Francis Canon; Chantal Pérot; Luciana C. C. Xavier; Karla M. Ferraz; Mônica M. Osório; Raul Manhães-de-Castro; Daniel Lambertz (European Journal of Applied Physiology, 2012)

Performance of a multi-RCM ensemble for South Eastern South America - A. F. Carril; C. G. Menéndez; A. R. C. Remedio; F. Robledo; A. Sörensson; B. Tencer; J.-P. Boulanger; M. de Castro; D. Jacob; H. Le Treut; L. Z. X. Li; O. Penalba; et al. (Climate Dynamics, 2012)

Synoptic-scale physical mechanisms associated with the Mei-yu front: A numerical case study in 1999 - Nguyen Minh Truong; Vu Thanh Hang; Roger A. Pielke; Christopher L. Castro; Koji Dairaku (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Mycorrhizal symbiosis affected by different genotypes of Pinus pinaster - Nadine R. Sousa; Miguel A. Ramos; Albina R. Franco; Rui S. Oliveira; Paula M. L. Castro (Plant and Soil, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Diet and exercise training reduce blood pressure and improve autonomic modulation in women with prehypertension - Allan R. K. Sales; Bruno M. Silva; Fabricia J. Neves; Natália G. Rocha; Renata F. Medeiros; Renata R. T. Castro; Antonio C. L. Nóbrega (European Journal of Applied Physiology, 2012)

Chiral pharmaceuticals in the environment - Ana R. Ribeiro; Paula M. L. Castro; Maria E. Tiritan (Environmental Chemistry Letters, 2012)

Degradation of difluorobenzenes by the wild strain Labrys portucalensis - Irina S. Moreira; Catarina L. Amorim; Maria F. Carvalho; Paula M. L. Castro (Biodegradation, 2012)

Net primary productivity, upwelling and coastal currents in the Gulf of Ulloa, Baja California, México - E. González-Rodríguez; A. Trasviña-Castro; G. Gaxiola-Castro; L. Zamudio; R. Cervantes-Duarte (Ocean Science, 2012)
The Gulf of Ulloa, a highly productive area off the western coast of the Baja California Peninsula, is examined for five successive years (2003–2007) by using satellite data and seasonal net primary productivity (NPP) estimates obtained from a vertical generalised production model. The results identify that northwestern winds blow parallel to the coast throughout the year. However, highest NPP occurs from March to June. During this period, an equatorward coastal current transports water from neighbouring upwelling areas to the northern Gulf of Ulloa and in combination with local upwelling, which injects nutrients into the euphotic zone, produce the observed increase in NPP. The opposite situation occurs in late summer when a warm poleward current of tropical characteristics arrives and inhibits the productivity in the whole region and generates the yearly lowest NPP levels. Our findings reveal the importance of lateral advection in the modulation of the primary productivity in this subtropical upwelling region.

Application of selected microbial consortia combined with inorganic and oleophilic fertilizers to recuperate oil-polluted soil using land farming technology - G. A. Silva-Castro; I. Uad; J. Gónzalez-López; C. G. Fandiño; F. L. Toledo; Concepción Calvo (Clean Technologies and Environmental Policy, 2012)

Climate Variability in NW Spain and its Relationship with Water Balance and Streamflow in a Small Headwater Catchment: Preliminary Results - M. L. Rodríguez-Blanco; M. M. Taboada-Castro; M. T. Taboada-Castro (Pure and Applied Geophysics, 2012)

Further Studies on the Hypothesis of PARP-1 Inhibition as a Strategy for Lessening the Long-Term Effects Produced by Perinatal Asphyxia: Effects of Nicotinamide and Theophylline on PARP-1 Activity in Brain and Peripheral Tissue - C. Allende-Castro; P. Espina-Marchant; D. Bustamante; E. Rojas-Mancilla; T. Neira; M. A. Gutierrez-Hernandez; D. Esmar; J. L. Valdes; P. Morales; P. J. Gebicke-Haerter; M. Herrera-Marschitz (Neurotoxicity Research, 2012)

Adenosine Deaminase Activity in Serum and Lymphocytes of Rats Infected with Sporothrix schenckii - Verônica S. P. Castro; Victor C. Pimentel; Aleksandro S. Da Silva; Gustavo R. Thomé; Patrícia Wolkmer; Jorge L. C. Castro; Márcio M. Costa; Cássia B. da Silva; Daniele C. Oliveira; Sydney H. Alves; Maria R. C. Schetinger; Sonia T. A. Lopes; et al. (Mycopathologia, 2012)

Treatment of diesel-polluted clay soil employing combined biostimulation in microcosms - G. A. Silva-Castro; L. SantaCruz-Calvo; I. Uad; C. Perucha; J. Laguna; J. Gónzalez-López; C. Calvo (International Journal of Environmental Science and Technology, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Zebrafish (Danio rerio) life-cycle exposure to chronic low doses of ethinylestradiol modulates p53 gene transcription within the gonads, but not NER pathways - J. Soares; L. Filipe C. Castro; M. A. Reis-Henriques; N. M. Monteiro; M. M. Santos (Ecotoxicology, 2012)

Bioconversion of oleuropein to hydroxytyrosol by lactic acid bacteria - M. M. Santos; C. Piccirillo; P. M. L. Castro; N. Kalogerakis; M. E. Pintado (World Journal of Microbiology and Biotechnology, 2012)

Obstructive Sleep Apnea Severity Correlates with Cellular and Plasma Oxidative Stress Parameters and Affective Symptoms - C. M. R. Franco; A. M. J. Lima; L. Ataíde; O. G. Lins; C. M. M. Castro; A. A. Bezerra; M. F. de Oliveira; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

Population genetics of the nurse shark (Ginglymostoma cirratum) in the western Atlantic - Stephen A. Karl; Andrey L. F. Castro; Ricardo C. Garla (Marine Biology, 2012)

Matayba obovata, a new species of Matayba sect. Matayba (Sapindaceae) from Brazil - Rubens L. Gayoso Coelho; Vinicius Castro Souza; María S. Ferrucci (Brittonia, 2012)

Concentration of ascorbic acid and innate immune effectors in Engraulis ringens and Strangomera bentincki during their main spawning period (2007–2008) in the Humboldt current system off Chile - M. C. Krautz; L. R. Castro; M. González; J. C. Vera; H. E. González (Marine Biology, 2012)

Capacity of simultaneous removal of zinc and cadmium from contaminated media, by two microalgae isolated from a polluted site - Cristina M. Monteiro; Paula M. L. Castro; F. Xavier Malcata (Environmental Chemistry Letters, 2011)

Identification and sequence analysis of the Condylorrhiza vestigialis MNPV p74 gene - Maria Elita B. Castro; Débora P. Paula; Geraldo F. Almeida; Zilda Maria A. Ribeiro; Marlinda L. Souza; Peter W. Inglis; Bergmann M. Ribeiro (Virus Genes, 2011)

New contributions to the study of common double mutants in the human LDL receptor gene - M. Teresa Tejedor; Ana Cenarro; Diego Tejedor; Marianne Stef; Lourdes Palacios; Isabel de Castro; Ángel L. García-Otín; Luis V. Monteagudo; Fernando Civeira; Miguel Pocovi (The Science of Nature, 2011)

Microsatellites reveal widespread predominance of an invasive over an indigenous Bemisia tabaci in Venezuela - G. Romay; F. Geraud-Pouey; D. T. Chirinos; M. A. Santana; I. Galindo-Castro; L. M. Márquez (Phytoparasitica, 2011)

Construction and validation of two metagenomic DNA libraries from Cerrado soil with high clay content - Alinne Pereira de Castro; Betania Ferraz Quirino; Heather Allen; Lynn L. Williamson; Jo Handelsman; Ricardo Henrique Krüger (Biotechnology Letters, 2011)

Predicting Acacia invasive success in South Africa on the basis of functional traits, native climatic niche and human use - P. Castro-Díez; T. Langendoen; L. Poorter; A. Saldaña-López (Biodiversity and Conservation, 2011)

Heavy Metal Accumulation in Plant Species Indigenous to a Contaminated Portuguese Site: Prospects for Phytoremediation - Helena Moreira; Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Water, Air, & Soil Pollution, 2011)

Frequency response of Pinus Pinea L. for selective cone harvesting by vibration - Sergio Castro-García; Gregorio L. Blanco-Roldán; Jesús A. Gil-Ribes (Trees, 2011)

Fisheries and trade of seahorses in Brazil: historical perspective, current trends, and future directions - Ierecê L. Rosa; Tacyana P. R. Oliveira; Frederico M. Osório; Luiz E. Moraes; André L. C. Castro; Glaura M. L. Barros; Rômulo R. N. Alves (Biodiversity and Conservation, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Biosorption of zinc ions from aqueous solution by the microalga Scenedesmus obliquus - Cristina M. Monteiro; Paula M. L. Castro; F. Xavier Malcata (Environmental Chemistry Letters, 2011)

Morphological, morphometric, meristic and osteological evidence for two species of hake (Actinopterygii: Gadiformes: Merluccius ) in Argentinean waters - J. M. Díaz de Astarloa; S. I. Bezzi; M. González Castro; E. Mabragaña; D. Hernández; S. M. Delpiani; D. E. Figueroa; M. B. Cousseau; M. Y. Deli Antoni; L. Tringali (Journal of Fish Biology, 2011)
Morphologically, both classic and landmark‐based morphometry and meristic analyses of 241 specimens of Merluccius , along with the re‐examination of six paratype specimens of Merluccius hubbsi , the holotype and three paratypes of Merluccius patagonicus and the syntype of Merluccius australis revealed the presence of only two species of Merluccius in Argentinean waters. Internal structures (hyomandibula, urohyal and sagitta otolith) of M. hubbsi were compared to those reported for M. patagonicus and were shown to have identical morphology. Type specimens of M. patagonicus showed a complete overlap in morphometric and meristic characters with M. hubbsi , whereas M. australis had a greater number of second dorsal and anal‐fin rays, and more lateral‐line scales. In addition, M. australis had a smaller eye and longer snout than M. hubbsi and M. patagonicus . The results indicate that there is no evidence for a third hake species in Argentinean waters. Merluccius patagonicus is a synonym of M. hubbsi .

RETRACTED: Remediation of Heavy Metal Contaminated Soils: An Overview of Site Remediation Techniques - Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Critical Reviews in Environmental Science and Technology, 2011)

Mitochondrial Quality Control and Parkinson’s Disease: A Pathway Unfolds - Inês Pimenta de Castro; L. Miguel Martins; Samantha Hui Yong Loh (Molecular Neurobiology, 2011)

Spinal cord direct current stimulation: finite element analysis of the electric field and current density - Gabriel R. Hernández-Labrado; José L. Polo; Elisa López-Dolado; Jorge E. Collazos-Castro (Medical & Biological Engineering & Computing, 2011)

Anti-inflammatory properties of Doxycycline and Minocycline in experimental models: an in vivo and in vitro comparative study - Liz M. Leite; Antônio Germano G. Carvalho; Pollyanna L. F. Tavares Ferreira; Igor Xavier Pessoa; Danilo O. Gonçalves; Amanda de Araújo Lopes; Jean Guilherme dos Santos Góes; Victor Costa de Castro Alves; Luzia Kalyne A. M. Leal; Gerly Anne Brito; Glauce S. B. Viana (Inflammopharmacology, 2011)

Phylogeography and conservation of the bull shark (Carcharhinus leucas) inferred from mitochondrial and microsatellite DNA - S. A. Karl; A. L. F. Castro; J. A. Lopez; P. Charvet; G. H. Burgess (Conservation Genetics, 2011)

Principal components analysis to evaluate ventilatory variability: comparison of athletes and sedentary men - R. R. T. Castro; M. Magini; S. Pedrosa; A. R. K. Sales; A. C. L. Nóbrega (Medical & Biological Engineering & Computing, 2011)

Toxicity of cadmium and zinc on two microalgae, Scenedesmus obliquus and Desmodesmus pleiomorphus, from Northern Portugal - Cristina M. Monteiro; Susana C. Fonseca; Paula M. L. Castro; F. Xavier Malcata (Journal of Applied Phycology, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Management of nursery practices for efficient ectomycorrhizal fungi application in the production of Quercus ilex - Rui S. Oliveira; Albina R. Franco; Miroslav Vosátka; Paula M. L. Castro (Symbiosis, 2010)

Cytogenetics of Alismataceae and Limnocharitaceae: CMA/DAPI banding and 45S rDNA sites - L. L. Feitoza; M. I. G. Martins; A. A. J. F. Castro; L. P. Félix; R. Carvalho (Plant Systematics and Evolution, 2010)

Haplotype analyses, mechanism and evolution of common double mutants in the human LDL receptor gene - M. T. Tejedor; A. Cenarro; D. Tejedor; M. Stef; R. Mateo-Gallego; I. de Castro; A. L. García-Otin; L. V. Monteagudo; F. Civeira; M. Pocovi (Molecular Genetics and Genomics, 2010)

Large-Eddy Simulation of Dispersion from Surface Sources in Arrays of Obstacles - V. B. L. Boppana; Zheng-Tong Xie; Ian P. Castro (Boundary-Layer Meteorology, 2010)

Cadmium Removal by Two Strains of Desmodesmus pleiomorphus Cells - Cristina M. Monteiro; Paula M. L. Castro; F. Xavier Malcata (Water, Air, & Soil Pollution, 2010)

Changes in metabolic substrates during early development in anchoveta Engraulis ringens (Jenyns 1842) in the Humboldt Current - M. C. Krautz; S. Vásquez; L. R. Castro; M. González; A. Llanos-Rivera; S. Pantoja (Marine Biology, 2010)

Antioxidant system activation by mercury in Pfaffia glomerata plantlets - N. S. Calgaroto; G. Y. Castro; D. Cargnelutti; L. B. Pereira; J. F. Gonçalves; L. V. Rossato; F. G. Antes; V. L. Dressler; E. M. M. Flores; M. R. C. Schetinger; F. T. Nicoloso (BioMetals, 2010)

Is zinniol a true phytotoxin? Evaluation of its activity at the cellular level against Tagetes erecta - Joaquín A. Qui; Lizbeth A. Castro-Concha; Karlina García-Sosa; María L. Miranda-Ham; Luis M. Peña-Rodríguez (Journal of General Plant Pathology, 2010)

Biotreatment of Industrial Wastewaters under Transient-State Conditions: Process Stability with Fluctuations of Organic Load, Substrates, Toxicants, and Environmental Parameters - Jan Sipma; M. Begoña Osuna; Maria A. E. Emanuelsson; Paula M. L. Castro (Critical Reviews in Environmental Science and Technology, 2010)

Frequency distribution of XbaIG > T and HaeIIIT > C GLUT1 polymorphisms among different Brazilian ethnic groups - G. C. S. Costa; L. C. J. Alcantara; R. Azevedo; G. Muricy; S. H. Kashima; D. T. Covas; B. Galvão-Castro; S. R. Gadelha (Molecular Biology Reports, 2010)

Polychlorinated Biphenyls and Biotransformation Enzymes in Three Species of Sea Turtles from the Baja California Peninsula of Mexico - K. L. Richardson; M. Lopez Castro; S. C. Gardner; D. Schlenk (Archives of Environmental Contamination and Toxicology, 2010)

Genotoxic activity of Eucalyptus globulus essential oil in Aspergillus nidulans diploid cells - C. T. Miyamoto; J. Rocha De Sant’anna; C. C. Da Silva Franco; M. M. Cunico; O. G. Miguel; L. C. Côcco; C. I. Yamamoto; C. Corrêa; M. A. A. De Castro-Prado (Folia Microbiologica, 2009)

Effects of ECF-Kraft pulp mill effluent treated with fungi (Rhizopus oryzae) on reproductive steroids and liver CYP1A of exposed goldfish (Carassius auratus) - M. S. Diniz; I. Peres; L. Castro; A. C. Freitas; T. A. P. Rocha-Santos; P. M. Costa; R. Pereira; A. C. Duarte (Ecotoxicology, 2009)

Differential effects of phytotoxic metabolites from Alternaria tagetica on Tagetes erecta cell cultures - Joaquin A. Qui; Lizbeth A. Castro-Concha; Karlina García-Sosa; Luis Manuel Peña-Rodríguez; María L. Miranda-Ham (Journal of General Plant Pathology, 2009)

Effects of exotic invasive trees on nitrogen cycling: a case study in Central Spain - P. Castro-Díez; N. González-Muñoz; A. Alonso; A. Gallardo; L. Poorter (Biological Invasions, 2009)

Use of the microalga Scenedesmus obliquus to remove cadmium cations from aqueous solutions - Cristina M. Monteiro; Paula M. L. Castro; F. Xavier Malcata (World Journal of Microbiology and Biotechnology, 2009)

Characterization of Desmodesmus pleiomorphus isolated from a heavy metal-contaminated site: biosorption of zinc - Cristina M. Monteiro; Ana P. G. C. Marques; Paula M. L. Castro; F. Xavier Malcata (Biodegradation, 2009)

Remediation of Heavy Metal Contaminated Soils: Phytoremediation as a Potentially Promising Clean-Up Technology - Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Critical Reviews in Environmental Science and Technology, 2009)

2D versus 3D in the kinematic analysis of the horse at the trot - F. Miró; R. Santos; J. L. Garrido-Castro; A. M. Galisteo; R. Medina-Carnicer (Veterinary Research Communications, 2009)

A New Developmental Toxicity Test for Pelagic Fish Using Anchoveta (Engraulis ringens J.) - A. Llanos-Rivera; L. R. Castro; J. Silva; E. Bay-Schmith (Bulletin of Environmental Contamination and Toxicology, 2009)

Cytogenetics of Alismatales s.s.: chromosomal evolution and C-banding - L. L. Feitoza; L. P. Felix; A. A. J. F. Castro; R. Carvalho (Plant Systematics and Evolution, 2009)

High frequency of hemolytic and cytotoxic activity in Aeromonas spp. isolated from clinical, food and environmental in Rio de Janeiro, Brazil - Magda C. B. Castilho; Tatiana L. A. Castro; Viviane S. Araújo; Rosemere S. Trajano; Paula A. Santos; Paula M. C. Pimenta; Kely Lucheze; Janyne T. B. Melo; Aline M. Gonçalves; Raquel T. Nogueira; Maria Graças de Luna; Angela C. Freitas-Almeida (Antonie van Leeuwenhoek, 2009)

Toxicity evaluation of three pesticides on non-target aquatic and soil organisms: commercial formulation versus active ingredient - Joana L. Pereira; Sara C. Antunes; Bruno B. Castro; Catarina R. Marques; Ana M. M. Gonçalves; Fernando Gonçalves; Ruth Pereira (Ecotoxicology, 2009)

Expression of the yggE gene protects Escherichia coli from potassium tellurite-generated oxidative stress - Lillian G. Acuña; Iván L. Calderón; Alex O. Elías; Miguel E. Castro; Claudio C. Vásquez (Archives of Microbiology, 2009)

Digestive enzymes of eight Amazonian teleosts with different feeding habits - K. López‐Vásquez; C. A. Castro‐Pérez; A. L. Val (Journal of Fish Biology, 2009)
The levels of amylase, maltase, lipase and alkaline protease from eight fish species of the Amazon were analysed. The enzyme levels are not related to fish feeding habits, reflecting their ever‐changing habitats and their opportunistic feeding behaviour.

Isolation of a Xanthobacter sp. degrading dichloromethane and characterization of the gene involved in the degradation - Maria A. E. Emanuelsson; M. Begoña Osuna; Ruben M. Ferreira Jorge; Paula M. L. Castro (Biodegradation, 2009)

Dynamic analysis of olive trees in intensive orchards under forced vibration - Sergio Castro-García; Gregorio L. Blanco-Roldán; Jesús A. Gil-Ribes; Juan Agüera-Vega (Trees, 2008)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

The Effects of Tannery Wastewater on the Development of Different Plant Species and Chromium Accumulation in Phragmites australis - Cristina S. C. Calheiros; António O. S. S. Rangel; Paula M. L. Castro (Archives of Environmental Contamination and Toxicology, 2008)

Surfactants in sludge-amended agricultural soils: a review - Alicia Fernández Cirelli; Carlos Ojeda; Mariano J. L. Castro; Miquel Salgot (Environmental Chemistry Letters, 2008)

Temperature effects on the anchoveta Engraulis ringens egg development: do latitudinal differences occur? - E. Tarifeño; M. Carmona; A. Llanos-Rivera; L. R. Castro (Environmental Biology of Fishes, 2008)

Cloning and expression of trypanothione reductase from a New World Leishmania species - Denise Barçante Castro-Pinto; Marcelo Genestra; Gustavo B. Menezes; Mariana Waghabi; Antonio Gonçalves; Catarina De Nigris Del Cistia; Carlos Mauricio R. Sant’Anna; Leonor L. Leon; Leila Mendonça-Lima (Archives of Microbiology, 2008)

Vaccination of turbot, Psetta maxima (L.), against the protozoan parasite Philasterides dicentrarchi : effects on antibody production and protection - M L Sanmartín; A Paramá; R Castro; S Cabaleiro; J Leiro; J Lamas; J L Barja (Journal of Fish Diseases, 2008)
The efficacy of a vaccine against the fish pathogen Philasterides dicentrarchi was evaluated in turbot by measuring the production of specific antibodies and duration of protection. Four groups of turbot were vaccinated twice, on days 0 and 30, with phosphate‐buffered saline, mineral oil adjuvant, antigen or antigen plus adjuvant. Specific serum antibodies were determined on day 0 and 1 month after the first and the second vaccinations. Protection was evaluated 1 month after the first vaccination and 1 and 5 months after the second vaccination. Serum antibody titres, measured by enzyme‐linked immunosorbent assay, and protection, assessed by challenges, increased significantly 1 month after the second vaccination in the group injected with antigen plus adjuvant and the protection lasted for at least a further 5 months in this group. The relative protection was 77% and 66% 1 and 5 months after the second vaccination, respectively. Administration of antigen or adjuvant separately had no effect on antibody response or protection. The results indicate that emulsion containing antigen plus adjuvant induced durable protection against P. dicentrarchi after the administration of the two vaccinations, and that this preparation can be used as a vaccine against the pathogen.

Detection of Alpha and Gamma-Proteobacteria in Amblyomma triste (Acari: Ixodidae) from Uruguay - José Manuel Venzal; Agustín Estrada-Peña; Aránzazu Portillo; Atilio J. Mangold; Oscar Castro; Carlos G. de Souza; María L. Félix; Laura Pérez-Martínez; Sonia Santibánez; José A. Oteo (Experimental and Applied Acarology, 2008)

Population genetic structure of Earth's largest fish, the whale shark ( Rhincodon typus ) - A. L. F. CASTRO; B. S. STEWART; S. G. WILSON; R. E. HUETER; M. G. MEEKAN; P. J. MOTTA; B. W. BOWEN; S. A. KARL (Molecular Ecology, 2007)
Large pelagic vertebrates pose special conservation challenges because their movements generally exceed the boundaries of any single jurisdiction. To assess the population structure of whale sharks ( Rhincodon typus ), we sequenced complete mitochondrial DNA control regions from individuals collected across a global distribution. We observed 51 single site polymorphisms and 8 regions with indels comprising 44 haplotypes in 70 individuals, with high haplotype ( h = 0.974 ± 0.008) and nucleotide diversity (π = 0.011 ± 0.006). The control region has the largest length variation yet reported for an elasmobranch (1143–1332 bp). Phylogenetic analyses reveal no geographical clustering of lineages and the most common haplotype was distributed globally. The absence of population structure across the Indian and Pacific basins indicates that oceanic expanses and land barriers in Southeast Asia are not impediments to whale shark dispersal. We did, however, find significant haplotype frequency differences (amova, F ST = 0.107, P

Analysis of a secondary contact between divergent lineages of brown trout Salmo trutta L. from Duero basin using microsatellites and mtDNA RFLPs - P. Martínez; C. Bouza; J. Castro; M. Hermida; B. G. Pardo; L. Sánchez (Journal of Fish Biology, 2007)
The analysis of 12 microsatellite loci in 16 native populations of Salmo trutta from Duero basin evidenced a strong genetic differentiation in accordance with the existence of two divergent Atlantic mtDNA lineages, Atlantic (AT) and Duero (DU). These lineages were observed spatially segregated mainly in the Lower‐course and in the inner part of the basin. Unlike previous isozyme information, microsatellite data suggested a more downstream location of the sharpest genetic divergence in Duero basin and a more complex structure in the inward area. Putative hybrid populations evidenced higher Hardy–Weinberg and gametic disequilibria than pure ones (Pisuerga, Lower‐course), not explained by mixture due to differential immigration pattern across the basin. Hybridization indexes suggested a bimodal pattern of hybridization and a higher weight of Pisuerga region in the genetic composition of hybrid samples in accordance with mtDNA data. The results suggested a limited introgression between AT and DU lineages. Taking into account the time of divergence between both lineages, selection and/or genetic incompatibility appeared necessary to explain the genetic structure observed and the ancient location of DU lineage restricted to this area.

Non-linear function model of voice pitch dependency on physical and mental load - Bernd Johannes; Peter Wittels; Robert Enne; Günter Eisinger; Carl A. Castro; Jeffrey L. Thomas; Amy B. Adler; Rupert Gerzer (European Journal of Applied Physiology, 2007)

Assessment of the spread of chestnut ink disease using remote sensing and geostatistical methods - L. Martins; J. Castro; W. Macedo; C. Marques; C. Abreu (European Journal of Plant Pathology, 2007)

Simulation of the Askervein flow. Part 2: Large-eddy simulations - A. Silva Lopes; J. M. L. M. Palma; F. A. Castro (Boundary-Layer Meteorology, 2007)

A linearization technique for multi-species transport problems - Neyva M. L. Romeiro; Rigoberto G. S. Castro; Sandra M. C. Malta; Luiz Landau (Transport in Porous Media, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genetic diversity of Brazilian strains of porcine circovirus type 2 (PCV-2) revealed by analysis of the cap gene (ORF-2) - A. M. Martins Gomes de Castro; A. Cortez; M. B. Heinemann; P. E. Brandão; L. J. Richtzenhain (Archives of Virology, 2007)

Culture of the histophagous ciliate Philasterides dicentrarchi (Ciliophora: Scuticociliatia) in fish tissues - R Castro; A Paramá; J L Barja; J Leiro; M L Sanmartin; J Lamas (Journal of Fish Diseases, 2007)

Glutamate Is Involved in Acid Stress Response in Bradyrhizobium sp. SEMIA 6144 (Arachis hypogaea L.) Microsymbiont - V. Natera; L. Sobrevals; A. Fabra; S. Castro (Current Microbiology, 2006)

Interspecific differentiation and intraspecific substructure in two closely related clupeids with extensive hybridization, Alosa alosa and Alosa fallax - P. Alexandrino; R. Faria; D. Linhares; F. Castro; M. Le Corre; R. Sabatié; J. L. Baglinière; S. Weiss (Journal of Fish Biology, 2006)
In this study, the evolutionary relationships within and among populations of European shads, Alosa alosa and Alosa fallax , was investigated. Screening of allelic variation across eight allozyme loci and sequencing 448 bp of the mtDNA cytochrome b gene in 14 rivers throughout the range of the species supported that the two taxa were independent lineages (1·3% net nucleotide divergence) despite extensive hybridization. Genetic diversity and structure was considerably higher in A. fallax than A. alosa and the former species revealed evidence of distinct lineages in the Mediterranean and Atlantic basins. A Bayesian clustering approach combined with gill raker counts verified that individuals of the two species could be assigned to their parent group with relatively high confidence. Evaluation of hybridization in the Lima and Mondego Rivers in Portugal provided evidence that introgression is extensive but is not currently obscuring (through hybrid swarming) the diagnosability of the two species.

Different native arbuscular mycorrhizal fungi influence the coexistence of two plant species in a highly alkaline anthropogenic sediment - Rui S. Oliveira; Paula M. L. Castro; John C. Dodd; Miroslav Vosátka (Plant and Soil, 2006)

Sensitivity studies of the RegCM3 simulation of summer precipitation, temperature and local wind field in the Caribbean Region - D. Martínez-Castro; R. Porfirio da Rocha; A. Bezanilla-Morlot; L. Alvarez-Escudero; J. P. Reyes-Fernández; Y. Silva-Vidal; R. W. Arritt (Theoretical and Applied Climatology, 2006)

Characterization of Edwardsiella tarda strains isolated from turbot, Psetta maxima (L.) - N Castro; A E Toranzo; J L Barja; S Núñez; B Magariños (Journal of Fish Diseases, 2006)
The biochemical, serological and molecular characteristics of a group of 21 Edwardsiella tarda strains isolated from turbot, Psetta maxima , in two different areas of Europe were analysed and compared with a total of 13 strains of this bacterial species with different geographical and host origins. All the turbot isolates were biochemically identical to the E. tarda strains included as reference. The use of different techniques including microagglutination, dot blot and Western blot of lipopolysaccharides allowed us to determine that all the turbot isolates constitute an homogeneous and distinctive serological group. Genetic analysis by randomly amplified polymorphic DNA (RAPD) analysis demonstrated that although the E. tarda strains from turbot were compiled in a unique group using the primers P3 and P6, two clonal lineages could be detected when oligonucleotides P4 and P5 were employed.

Evolutionary analysis of genetic variation observed in citrus tristeza virus (CTV) after host passage - V. Sentandreu; J. A. Castro; M. A. Ayllón; L. Rubio; J. Guerri; F. González-Candelas; P. Moreno; A. Moya (Archives of Virology, 2006)

Coat protein gene sequence of a Mexican isolate of Sugarcane mosaic virus and its infectivity in maize and sugarcane plants - F. Espejel; D. Jeffers; J. C. Noa-Carrazana; S. Ruiz-Castro; L. Silva-Rosales (Archives of Virology, 2006)

Apoptotic effect of fludarabine is independent of expression of IAPs in B-cell chronic lymphocytic leukemia - K. L. Silva; D. V. Vasconcellos; E. D. de Paula Castro; A. M. Coelho; R. Linden; R. C. Maia (Apoptosis, 2006)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Studies on the diversity of arbuscular mycorrhizal fungi and the efficacy of two native isolates in a highly alkaline anthropogenic sediment - R. S. Oliveira; M. Vosátka; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2005)

Geotechnical Site Characterisation in the Umbria-Marche Area and Evaluation of Earthquake Site-Response - L. Luzi; D. Bindi; G. Franceschina; F. Pacor; R. R. Castro (Pure and Applied Geophysics, 2005)

Geochemical evolution of groundwater in the Maneadero coastal aquifer during a dry year in Baja California, Mexico - L. Walter Daesslé; Edith C. Sánchez; Victor F. Camacho-Ibar; Leopoldo G. Mendoza-Espinosa; José D. Carriquiry; Victor A. Macias; Pedro G. Castro (Hydrogeology Journal, 2005)

Potential use of a Yersinia ruckeri O1 auxotrophic aroA mutant as a live attenuated vaccine - A Temprano; J Riaño; J Yugueros; P González; L de Castro; A Villena; J M Luengo; G Naharro (Journal of Fish Diseases, 2005)
The aroA gene of Yersinia ruckeri , which encodes 5‐enolpyruvylshikimate 3‐phosphate synthase, was insertionally inactivated with a DNA fragment containing a kanamycin resistance determinant and reintroduced by allelic exchange into the chromosome of Y. ruckeri 21102 O1 by means of the suicide vector pIVET8. The Y. ruckeri aroA ::Kan r mutant was highly attenuated when inoculated intraperitoneally into rainbow trout, with a 50% lethal dose of >5 × 10 7 CFU. The mutants were not recoverable from the internal organs 48 h post‐inoculation or later. The vaccination of rainbow trout with the AroA mutant as a live vaccine conferred significant protection (relative percentage survival = 90%) against the pathogenic wild‐type strain of Y. ruckeri.

Isolation of lymphocystis disease virus from sole, Solea senegalensis Kaup, and blackspot sea bream, Pagellus bogaraveo (Brünnich) - M C Alonso; I Cano; E Garcia‐Rosado; D Castro; J Lamas; J L Barja; J J Borrego (Journal of Fish Diseases, 2005)
Two viruses were isolated from cultured sole, Solea senegalensis , and wild blackspot sea bream, Pagellus bogaraveo , and preliminarily characterized as lymphocystis disease viruses (LCDVs). Viral isolates were characterized by morphological, biochemical and biophysical properties. In addition, the susceptibility of four fish cell lines was also tested. LCDV isolates developed cytopathic effects on the SAF‐1 cell line at 5 and 6 days post‐infection and reached titres of 10 6 TCID 50 mL −1 . The antigenic and structural protein analysis of the two new LCDV isolates showed identical profiles to that obtained for LCDV strain Leetown NFH (ATCC VR‐342), used as a reference viral strain, and for an LCDV isolate collected from gilt‐head sea bream, Sparus aurata , cultured in southern Spain. Molecular confirmation was performed by polymerase chain reaction. Specific primers for LCDV produced a 270‐bp DNA fragment, the expected size for LCDV.

Plant species richness and spatial organization at different small scales in western Mediterranean landscapes - J. M. De. Miguel; L. Ramírez-Sanz; I. Castro; M. Costa-Tenorio; M. A. Casado; F. D. Pineda (Plant Ecology, 2005)

Use of natural marks on population estimates of the nurse shark,Ginglymostoma cirratum, at Atol das Rocas Biological Reserve, Brazil - Andrey L. F. Castro; Ricardo S. Rosa (Environmental Biology of Fishes, 2005)

Isolation and properties of a pure bacterial strain capable of fluorobenzene degradation as sole carbon and energy source - M. F. Carvalho; R. Ferreira Jorge; C. C. Pacheco; P. De Marco; P. M. L. Castro (Environmental Microbiology, 2005)
Summary A pure bacterial strain capable of aerobic biodegradation of fluorobenzene (FB) as the sole carbon and energy source was isolated by selective enrichment from sediments collected from a polluted site. 16S rRNA and fatty acid analyses support that strain F11 belongs to a novel genus within the α‐2 subgroup of the Proteobacteria, possibly within a new clade related to the order Rhizobiales . In batch cultures, growth of strain F11 on FB led to stoichiometric release of fluoride ion. Maximum experimental growth rate of 0.04 h −1 was obtained at FB concentration of 0.4 mM. Growth kinetics were described by the Luong model. An inhibitory effect with increasing FB concentrations was observed, with no growth occurring at concentrations higher than 3.9 mM. Strain F11 was shown to be able to use a range of other organic compounds, including other fluorinated compounds such as 2‐fluorobenzoate, 4‐fluorobenzoate and 4‐fluorophenol. To our knowledge, this is the first time biodegradation of FB, as the sole carbon and energy source, by a pure bacterium has been reported.

Limited nucleotide divergence over large spatial scales in the asterinid sea star Patiriella exigua - D. J. Colgan; M. Byrne; E. Rickard; L. R. Castro (Marine Biology, 2005)

High prevalence of hepatitis B virus infection among tuberculosis patients with and without HIV in Rio de Janeiro, Brazil - C. A. Blal; S. R. L. Passos; C. Horn; I. Georg; M. G. Bonecini-Almeida; V. C. Rolla; L. Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Larvae of Crystallodytes pauciradiatus (Perciformes: Creediidae) from Easter Island, South Pacific - M. F. Landaeta; G. Herrera; L. R. Castro (Journal of Fish Biology, 2005)
Larvae of Crystallodytes pauciradiatus (Creediidae) are described from 47 individuals (2·9–21·3 mm). They are elongate, slender, lightly pigmented, have prominent preopercular spines and unique small spines on the lower jaw. Early stages are restricted to the nearshore water around Easter Island, South Pacific.

A case of eumycetoma due to Madurella grisea in northern Brazil - Raquel Vilela; Olga M. V. Duarte; Carlos A. Rosa; Joao G. F. Castro; Sandra Lyon; Roberta L. Motta; Ana C. L. Moura (Mycopathologia, 2004)

An In Situ Bioassay Integrating Individual and Biochemical Responses Using Small Fish Species - Bruno Branco Castro; Olmpia Sobral; Lcia Guilhermino; Rui Ribeiro (Ecotoxicology, 2004)

High CO2 Levels in Boreholes at El Teide Volcano Complex (Tenerife, Canary Islands): Implications for Volcanic Activity Monitoring - V. Soler; J. A. Castro-Almazán; R. T. Viñas; A. Eff-Darwich; S. Sánchez-Moral; C. Hillaire-Marcel; I. Farrujia; J. Coello; J. de la Nuez; M. C. Martín; M. L. Quesada; E. Santana (Pure and Applied Geophysics, 2004)

Decline in Assayable Progesterone in Bovine Serum under Different Storage Conditions - T. de Castro; L. Valdez; M. Rodriguez; N. Benquet; E. Rubianes (Tropical Animal Health and Production, 2004)

Divergence of two forms of Triphoturus in the eastern Pacific based on mtDNA cytochrome b gene sequences and larval morphology - L. Rodríguez‐Graña; G. Herrera; L. Herrera; L. R. Castro (Journal of Fish Biology, 2004)
Divergence between two eastern Pacific forms of Triphoturus , currently considered to belong to the same species was tested by DNA sequences of the cytochrome b gene (DNA obtained from larvae collected in northern Chile and from adults in the Southern California Bight) and examination of larval characters. The number of apparently fixed substitutions (12 among 31 variable sites, out of 1001 bases) was high and the pattern of mid‐lateral trunk pigmentation in larvae also differed consistently between the two forms. The results support the separate species status for T. mexicanus (North America) and T. oculeus (Central‐South America).

Multiple Paternity in Norway Lobster ( Nephrops norvegicus L.) Assessed with Microsatellite Markers - M. L. Cancela; R. Streiff; S. Mira; M. Castro (Marine Biotechnology, 2004)

An antecedent of the MHC-linked genomic region in amphioxus - L. Filipe C. Castro; Rebecca F. Furlong; Peter W. H. Holland (Immunogenetics, 2004)

Input-Output Budgets of Inorganic Nitrogen for 24 Forest Watersheds in the Northeastern United States: A Review - John L. Campbell; James W. Hornbeck; Myron J. Mitchell; Mary Beth Adams; Mark S. Castro; Charles T. Driscoll; Jeffrey S. Kahl; James N. Kochenderfer; Gene E. Likens; James A. Lynch; Peter S. Murdoch; Sarah J. Nelson; et al. (Water, Air, & Soil Pollution, 2004)

Gynogenesis Assessment Using Microsatellite Genetic Markers in Turbot ( Scophthalmus maximus ) - J. Castro; C. Bouza; L. Snchez; R. M. Cal; F. Piferrer; P. Martnez (Marine Biotechnology, 2003)

Epifluorescence microscope methods for bacterial enumeration in a 4-chlorophenol degrading consortium - C.C. Pacheco; C.C. Alves; L. Barreiros; P.M.L. Castro; P.C.M. Teixeira (Biotechnology Letters, 2003)

Assessment of regional seasonal rainfall predictability using the CPTEC/COLA atmospheric GCM - J. A. Marengo; I. F. A. Cavalcanti; P. Satyamurty; I. Trosnikov; C. A. Nobre; J. P. Bonatti; H. Camargo; G. Sampaio; M. B. Sanches; A. O. Manzi; C. A. C. Castro; C. D'Almeida; et al. (Climate Dynamics, 2003)

Distribution of virulence genes in clinical and environmental isolates of Aeromonas spp. - M.R. Chacón; M.J. Figueras; G. Castro-Escarpulli; L. Soler; J. Guarro (Antonie van Leeuwenhoek, 2003)

Sequencing and Characterization of Plasmid pUIBI-1 from Bacillus thuringiensis Serovar entomocidus LBIT-113 - Joel E. Lpez-Meza; J. Eleazar Barboza-Corona; M. Cristina Del Rincn-Castro; Jorge E. Ibarra (Current Microbiology, 2003)

Myocardin mRNA is augmented in the failing myocardium: expression profiling in the porcine model and human dilated cardiomyopathy - Mario Torrado; Eduardo Lpez; Alberto Centeno; Constancio Medrano; Alfonso Castro-Beiras; Alexander T. Mikhailov (Journal of Molecular Medicine, 2003)

Nesting characteristics of the olive ridley turtle ( Lepidochelys olivacea ) in Cabo Pulmo, southern Baja California - M. C. Lpez-Castro; R. Carmona; W. J. Nichols (Marine Biology, 2003)

Simulation of the Askervein Flow. Part 1: Reynolds Averaged Navier–Stokes Equations (k ∈ Turbulence Model) - F. A. Castro; J. M. L. M. Palma; A. Silva Lopes (Boundary-Layer Meteorology, 2003)

Accumulation of fumonisins B1 and B2 in freshly harvested Brazilian commercial maize at three locations during two nonconsecutive seasons - Simone M. Camargos; Lucia M. Valente Soares; Eduardo Sawazaki; Denizart Bolonhezi; Jairo L. Castro; Nelson Bortolleto (Mycopathologia, 2003)

Frequent Mitochondrial Gene Rearrangements at the Hymenopteran nad3-nad5 Junction - Mark Dowton; Lyda R. Castro; Sarah L. Campbell; Sharmilla D. Bargon; Andrew D. Austin (Journal of Molecular Evolution, 2003)

Dermal Exposure to Pesticides in Greenhouses Workers: Discrimination and Selection of Variables for the Design of Monitoring Programs - A. Garrido Frenich; P. A. Aguilera; F. Egea Gonzalez; M. L. Castro Cano; M. Martinez Galera; J. L. Martinez Vidal; M. Soler (Environmental Monitoring and Assessment, 2002)

Molecular epidemiology of hepatitis B virus in Afro-Venezuelan populations - A. Quintero; D. Martínez; B. Alarcón de Noya; A. Costagliola; L. Urbina; N. González; F. Liprandi; D. Castro de Guerra; F. H. Pujol (Archives of Virology, 2002)

First record of the paedomorphic goby Schindleria praematura , Easter Island, South Pacific - M. F. Landaeta; R. Veas; L. R. Castro (Journal of Fish Biology, 2002)
Thirty‐five larvae and adults of the paedomophic goby Schindleria praematura were collected around Easter Island, during November 1999. Mean abundance from the five stations where they were caught ( n =26) was 10.2 ± 6.1 individuals 1000 m −3 . They occurred only in shallow areas. Oocyte counts ranged from 70 to 110. Otolith examination suggests that adults appear to live no longer than 3 months.

Total Mercury Concentrations in Lakes and Fish of Western Maryland, USA - M. S. Castro; E. N. McLaughlin; S. L. Davis; R. P. Morgan, II (Archives of Environmental Contamination and Toxicology, 2002)

Molecular relationships in Genista L. Sect. Spartocarpus Spach (Fabaceae) - O. De Castro; S. Cozzolino; S. L. Jury; P. Caputo (Plant Systematics and Evolution, 2002)

Preservation methods for the storage of anaerobic sludges - H. Castro; M. Queirolo; M. Quevedo; L. Muxí (Biotechnology Letters, 2002)

Phytoremediation of polyaromatic hydrocarbons, anilines and phenols - Patricia J. Harvey; Bruno F. Campanella; Paula M. L. Castro; Hans Harms; Eric Lichtfouse; Anton R. Schäffner; Stanislav Smrcek; Daniele Werck-Reichhart (Environmental Science and Pollution Research, 2002)

A geochemical and geophysical approach to derive a conceptual circulation model of CO 2 -rich mineral waters: A case study of Vilarelho da Raia, northern Portugal - Marques J.; Monteiro Santos; Graa R.; Castro R.; Aires-Barros L.; L. Mendes Victor (Hydrogeology Journal, 2001)

Allozymic evidence of parapatric differentiation of brown trout ( Salmo trutta L.) within an Atlantic river basin of the Iberian Peninsula - C. Bouza; J. Castro; L. Sánchez; P. Martínez (Molecular Ecology, 2001)
The genetic variation of brown trout from Duero, one of the main Atlantic Iberian river basins, was assessed at 34 enzymatic loci in 62 native populations. A strong intrabasin differentiation was detected ( G ST = 0.46; range D : 0–0.066), mainly attributable to the existence of two divergent groups of populations within Duero: southern and northern groups. This divergence was mainly a consequence of the unequal distribution of *75 and *100 alleles at s MDH ‐B1,2* isoloci, which were correlated with substantial differences in genetic diversity among regions. The Lower Course region (nearly fixed for the *100 allele) and Pisuerga River (nearly fixed for the *75 allele) showed lower heterozygosities ( H ≈ 0.8%) in contrast with adjacent areas, which evidenced intermediate frequencies for both alleles and higher heterozygosities ( H : 2.2–3.1%). Vicariance appeared as the more probable explanation for the significant positive correlation detected between genetic and geographical distances in Duero Basin. Genetic relationships with adjacent Iberian drainages indicate a close similarity between the southern group and Cantabric trout, whereas the northern group constitutes an ancient form from this basin. This study confirmed complex genetic relationships in brown trout from northwest Iberia, reasserting the existence of clines at several loci and for genetic diversity. The interaction between Cantabric and Duero trout , as well as the location of the limit of the anadromous form around the 42° N parallel, are both required to understand the genetic characteristics of brown trout from this area.

The mycorrhizal status of Phragmites australis in several polluted soils and sediments of an industrialised region of Northern Portugal - R.S. Oliveira; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2001)

Biological responses of microflora to treatment with CA and/or fumigation - J. L. Zettler; S. Navarro; Maria Fernanda Penteado M. de Castro; J. O. do Vale; Neura Bragnolo; M. F. F. Leitao; Eliane Salvadego Anichiareo; K. A. Mills (Phytoparasitica, 2001)

Brown trout 5S rDNA maps to chromosome 38 - B. G. Pardo; J. Castro; P. Martínez; L. Sánchez (Chromosome Research, 2000)

Nosocomial Spread of Hepatitis B Virus in Two Hemodialysis Units, Investigated by Restriction Fragment Length Polymorphism Analysis - L. De Castro; N. M. Araujo; R. R. Sabino; F. Alvarenga; C. F. T. Yoshida; S. A. Gomes (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Floristic relationship between scrubland and grassland patches in the Mediterranean landscape of the Iberian Peninsula - L. Ramírez-Sanz; M.A. Casado; J.M. de Miguel; I. Castro; M. Costa; F.D. Pineda (Plant Ecology, 2000)

Morphological comparison of the buccal apparatus in two bivalve commensal Teleostei, Encheliophis dubius and Onuxodon fowleri (Ophidiiformes, Carapidae) - E. Parmentier; J. L. Castro-Aguirre; P. Vandewalle (Zoomorphology, 2000)

PLS and PCR Methods in the Assessment of Coastal Water Quality - P. A. Aguilera; A. Garrido Frenich; H. Castro; J. L. Martinez Vidal (Environmental Monitoring and Assessment, 2000)

Coat protein sequence comparisons of three Mexican isolates of papaya ringspot virus with other geographical isolates reveal a close relationship to American and Australian isolates - L. Silva-Rosales; N. Becerra-Leor; S. Ruiz-Castro; D. Téliz-Ortiz; J. C. Noa-Carrazana (Archives of Virology, 2000)

A high incidence of Shigella -induced arthritis in a primate species: major histocompatibility complex class I molecules associated with resistance and susceptiblity, and their relationship to HLA-B27 - J. A. Urvater; S. N. McAdam; J. H. Loehrke; T. M. Allen; J. L. Moran; T. J. Rowell; S. Rojo; J.A. López de Castro; J. D. Taurog; D. I. Watkins (Immunogenetics, 2000)

Genetic structure of brown trout, Salmo trutta L., at the southern limit of the distribution range of the anadromous form - C. Bouza; J. Arias; J. Castro; L. Sánchez; P. Martínez (Molecular Ecology, 1999)
Genetic variation at 33 protein loci was investigated in 41 wild brown trout populations from four river basins in Galicia (northwest Spain) to analyse the amount and distribution of genetic diversity in a marginal area, located in the distribution limit of the anadromous form of this species. The genetic diversity detected within populations ( H between 0 and 6%) lies within the range quoted for this species in previous reports. The Miño, the most southern river basin analysed, showed a significantly lower genetic diversity and the highest genetic differentiation among the river basins studied. The hierarchical gene diversity analysis showed high population differentiation in a restricted area ( G ST = 27%), mostly due to differences among populations within basins ( G SC = 22%). The reduction of G ST observed when the isolated samples were excluded from the analysis ( G ST = 17%) showed the importance of habitat fragmentation on the heterogeneity detected. Gene flow among populations was comparatively evaluated by three indirect methods, which in general revealed low figures of absolute number of migrants per generation, slightly higher than 1. The gene flow among basins reflected a positive relationship with geographical distance. This trend was confirmed by the significant correlation observed between geographical and genetic distances, including all population pairs, which suggests a component of isolation by distance in brown trout genetic structure. Nevertheless, the nonsignificant intrabasin correlation demonstrates the complexity of genetic relationships among populations in this species. The model of genetic structure in brown trout is discussed in the light of the results obtained.

Opioid consumption in Spain - the significance of a regulatory measure - J. García del Pozo; A. Carvajal García-Pando; A. M. Rueda de Castro; M. I. Cano del Pozo; L. H. Martín Arias (European Journal of Clinical Pharmacology, 1999)

Some Results from the Hailpad Network in León (Spain): Noteworthy Correlations among Hailfall Parameters - R. Fraile; J. L. Sánchez; J. L. de la Madrid; A. Castro; J. L. Marcos (Theoretical and Applied Climatology, 1999)

rDNA RFLPs as genetic markers for resource management in brown trout - J. Castro; B. G. Pardo; L. Sánchez; P. Martínez (Journal of Fish Biology, 1999)
Interesting population‐specific rDNA markers were detected for microgeographical analysis of brown trout Salmo trutta as well as for monitoring stocking practices.

Host-specific transcription of nucleopolyhedrovirus gene homologues in productive and abortive Anticarsia gemmatalis MNPV infections - M. E. B. Castro; M. L. Souza; S. L. Bilimoria (Archives of Virology, 1999)

Origin of peraluminous granites and granodiorites, Iberian massif, Spain: an experimental test of granite petrogenesis - Antonio Castro; Alberto E. Patiño Douce; L. Guillermo Corretgé; Jesús D. de la Rosa; Mohammed El-Biad; Hassan El-Hmidi (Contributions to Mineralogy and Petrology, 1999)

Differentiation of Clams from Fishing Areas as an Approximation to Coastal Quality Assessment - H. Castro; P. A. Aguilera; J. L. Martinez Vidal; E. L. Carrique (Environmental Monitoring and Assessment, 1999)

An objective method for partitioning dendrograms based on entropy parameters - M. A. Casado; L. Ramírez-Sanz; I. Castro; J. M. de Miguel; C. L. de Pablo (Plant Ecology, 1997)

Identification and partial characterization of three chitinase forms in Entamoeba invadens with emphasis on their inhibition by allosamidin - Julio C. Villagmez-Castro; Everardo Lpez-Romero (Antonie van Leeuwenhoek, 1996)

Evaluation of prenatal aldrin intoxication in rats - V. L. Castro; M. M. Bernardi; J. Palermo-Neto (Archives of Toxicology, 1992)

A diagnostic method to detect alcelaphine herpesvirus-1 of malignant catarrhal fever using the polymerase chain reaction - D. Hsu; L. M. Shih; A. E. Castro; Y. C. Zee (Archives of Virology, 1990)

Comparison of genomes of malignant catarrhal fever-associated herpesviruses by restriction endonuclease analysis - L. M. Shih; Y. C. Zee; A. E. Castro (Archives of Virology, 1989)

Early biochemical changes produced by malathion on toad embryos - E. A. Rosenbaum; A. Caballero de Castro; L. Gauna; A. M. Pechen de D'Angelo (Archives of Environmental Contamination and Toxicology, 1988)

African swine fever virus - R. C. Wardley; C. de M. Andrade; D. N. Black; F. L. de Castro Portugal; L. Enjuanes; W. R. Hess; C. Mebus; A. Ordas; D. Rutili; J. Sanchez Vizcaino; J. D. Vigario; P. J. Wilkinson; et al. (Archives of Virology, 1983)

Reduction of iron oxide minerals by a marine Bacillus - Aurora F. de Castro; H. L. Ehrlich (Antonie van Leeuwenhoek, 1970)

Developmental genetics of the alcohol dehydrogenase locus of the Japanese quail - S. Ohno; L. Christian; C. Stenius; E. Castro-Sierra; J. Muramoto (Biochemical Genetics, 1969)

Schwere Gold-Dermatitis bei Orosanil-Behandlung einer Lungentuberkulösen - M. sebastian Herrador; L. Castro García (Archives of Toxicology, 1936)